Mass balance of the Greenland ice sheet (2003–2008) from ICESat data – the impact of interpolation, sampling and firn density - Sørensen, L. S.; Simonsen, S. B.; Nielsen, K.; Lucas-Picher, P.; Spada, G.; Adalgeirsdottir, G.; Forsberg, R.; Hvidberg, C. S. (The Cryosphere, 2011)
Abstract. ICESat has provided surface elevation measurements of the ice sheets since the launch in January 2003, resulting in a unique dataset for monitoring the changes of the cryosphere. Here, we present a novel method for determining the mass balance of the Greenland ice sheet, derived from ICESat altimetry data. Three different methods for deriving elevation changes from the ICESat altimetry dataset are used. This multi-method approach provides a method to assess the complexity of deriving elevation changes from this dataset. The altimetry alone can not provide an estimate of the mass balance of the Greenland ice sheet. Firn dynamics and surface densities are important factors that contribute to the mass change derived from remote-sensing altimetry. The volume change derived from ICESat data is corrected for changes in firn compaction over the observation period, vertical bedrock movement and an intercampaign elevation bias in the ICESat data. Subsequently, the corrected volume change is converted into mass change by the application of a simple surface density model, in which some of the ice dynamics are accounted for. The firn compaction and density models are driven by the HIRHAM5 regional climate model, forced by the ERA-Interim re-analysis product, at the lateral boundaries. We find annual mass loss estimates of the Greenland ice sheet in the range of 191 ± 23 Gt yr−1 to 240 ± 28 Gt yr−1 for the period October 2003 to March 2008. These results are in good agreement with several other studies of the Greenland ice sheet mass balance, based on different remote-sensing techniques.

Greenland ice sheet surface mass balance: evaluating simulations and making projections with regional climate models - Rae, J. G. L.; Aðalgeirsdóttir, G.; Edwards, T. L.; Fettweis, X.; Gregory, J. M.; Hewitt, H. T.; Lowe, J. A.; Lucas-Picher, P.; Mottram, R. H.; Payne, A. J.; Ridley, J. K.; Shannon, S. R.; et al. (The Cryosphere, 2012)
Abstract. Four high-resolution regional climate models (RCMs) have been set up for the area of Greenland, with the aim of providing future projections of Greenland ice sheet surface mass balance (SMB), and its contribution to sea level rise, with greater accuracy than is possible from coarser-resolution general circulation models (GCMs). This is the first time an intercomparison has been carried out of RCM results for Greenland climate and SMB. Output from RCM simulations for the recent past with the four RCMs is evaluated against available observations. The evaluation highlights the importance of using a detailed snow physics scheme, especially regarding the representations of albedo and meltwater refreezing. Simulations with three of the RCMs for the 21st century using SRES scenario A1B from two GCMs produce trends of between −5.5 and −1.1 Gt yr−2 in SMB (equivalent to +0.015 and +0.003 mm sea level equivalent yr−2), with trends of smaller magnitude for scenario E1, in which emissions are mitigated. Results from one of the RCMs whose present-day simulation is most realistic indicate that an annual mean near-surface air temperature increase over Greenland of ~ 2°C would be required for the mass loss to increase such that it exceeds accumulation, thereby causing the SMB to become negative, which has been suggested as a threshold beyond which the ice sheet would eventually be eliminated.

Very high resolution regional climate model simulations over Greenland: Identifying added value - Lucas‐Picher, Philippe; Wulff‐Nielsen, Maria; Christensen, Jens H.; Aðalgeirsdóttir, Guðfinna; Mottram, Ruth; Simonsen, Sebastian B. (Journal of Geophysical Research: Atmospheres, 2012)
This study presents two simulations of the climate over Greenland with the regional climate model (RCM) HIRHAM5 at 0.05° and 0.25° resolution driven at the lateral boundaries by the ERA‐Interim reanalysis for the period 1989–2009. These simulations are validated against observations from meteorological stations (Danish Meteorological Institute) at the coast and automatic weather stations on the ice sheet (Greenland Climate Network). Generally, the temperature and precipitation biases are small, indicating a realistic simulation of the climate over Greenland that is suitable to drive ice sheet models. However, the bias between the simulations and the few available observations does not reduce with higher resolution. This is partly explained by the lack of observations in regions where the higher resolution is expected to improve the simulated climate. The RCM simulations show that the temperature has increased the most in the northern part of Greenland and at lower elevations over the period 1989–2009. Higher resolution increases the relief variability in the model topography and causes the simulated precipitation to be larger on the coast and smaller over the main ice sheet compared to the lower‐resolution simulation. The higher‐resolution simulation likely represents the Greenlandic climate better, but the lack of observations makes it difficult to validate fully. The detailed temperature and precipitation fields that are generated with the higher resolution are recommended for producing adequate forcing fields for ice sheet models, particularly for their improved simulation of the processes occurring at the steep margins of the ice sheet. , Key Points Validation of regional climate model simulations over Greenland Description of the climate over Greenland Assessment of added value

Assessing a multilayered dynamic firn-compaction model for Greenland with ASIRAS radar measurements - Simonsen, Sebastian B.; Stenseng, Lars; Ađalgeirsdóttir, Guðfinna; Fausto, Robert S.; Hvidberg, Christine S.; Lucas-Picher, Philippe (Journal of Glaciology, 2013)
Abstract A method to assess firn compaction using data collected with the Airborne SAR (Synthetic Aperture Radar)/Interferometric Radar Altimeter System (ASIRAS) is developed. For this, we develop a dynamical firn-compaction model that includes meltwater retention. Based on the ASIRAS data, which show internal layers as annual horizons in the uppermost firn, the method relies on inferring the age/ depth (internal layers) information from the radar data using a Monte Carlo inversion technique to tune in parallel both the firn model and the atmospheric forcing parameters (temperature and accumulation). The model is validated against two firn cores, and it is shown that applying both firn densities and age/ depth information for the inversion gives the most accurate understanding of model biases. The method is then applied to a 67 km section of the EGIG line forced by atmospheric output from a regional climate model using only age/depth information in the inversion step. The layers traced by the ASIRAS data are modeled with a root-mean-square error of 9 cm, which is within the estimated error of the layer tracing. This gives us confidence in applying observed annual layering from firn radar data to assess firn compaction; however, the study also indicates that our firn-model-tuning parameters are site-dependent and cannot be parameterized by temperature and accumulation alone.

Dynamical Downscaling with Reinitializations: A Method to Generate Finescale Climate Datasets Suitable for Impact Studies - Lucas-Picher, Philippe; Boberg, Fredrik; Christensen, Jens H.; Berg, Peter (Journal of Hydrometeorology, 2013)
Abstract To retain the sequence of events of a regional climate model (RCM) simulation driven by a reanalysis, a method that has not been widely adopted uses an RCM with frequent reinitializations toward its driving field. In this regard, this study highlights the benefits of an RCM simulation with frequent (daily) reinitializations compared to a standard continuous RCM simulation. Both simulations are carried out with the RCM HIRHAM5, driven with the European Centre for Medium-Range Weather Forecasts (ECMWF) Interim Re-Analysis (ERA-Interim) data, over the 12-km-resolution European Coordinated Regional Climate Downscaling Experiment (CORDEX) domain covering the period 1989–2009. The analysis of daily precipitation shows improvements in the sequence of events and the maintenance of the added value from the standard continuous RCM simulation. The validation of the two RCM simulations with observations reveals that the simulation with reinitializations indeed improves the temporal correlation. Furthermore, the RCM simulation with reinitializations has lower systematic errors compared to the continuous simulation, which has a tendency to be too wet. A comparison of the distribution of wet day precipitation intensities shows similar added value in the continuous and reinitialized simulations with higher variability and extremes compared to the driving field ERA-Interim. Overall, the results suggest that the finescale climate dataset of the RCM simulation with reinitializations better suits the needs of impact studies by providing a sequence of events matching closely the observations, while limiting systematic errors and generating reliable added value. Downsides of the method with reinitializations are increased computational costs and the introduction of temporal discontinuities that are similar to those of a reanalysis.

Downscaled climate change projections with uncertainty assessment over India using a high resolution multi-model approach - Kumar, Pankaj; Wiltshire, Andrew; Mathison, Camilla; Asharaf, Shakeel; Ahrens, Bodo; Lucas-Picher, Philippe; Christensen, Jens H.; Gobiet, Andreas; Saeed, Fahad; Hagemann, Stefan; Jacob, Daniela (Science of The Total Environment, 2013)

Evaluation of the regional climate model ALADIN to simulate the climate over North America in the CORDEX framework - Lucas-Picher, Philippe; Somot, Samuel; Déqué, Michel; Decharme, Bertrand; Alias, Antoinette (Climate Dynamics, 2013)

Effects of Irrigation in India on the Atmospheric Water Budget - Tuinenburg, O. A.; Hutjes, R. W. A.; Stacke, T.; Wiltshire, A.; Lucas-Picher, P. (Journal of Hydrometeorology, 2014)
Abstract The effect of large-scale irrigation in India on the moisture budget of the atmosphere was investigated using three regional climate models and one global climate model, all of which performed an irrigated run and a natural run without irrigation. Using a common irrigation map, year-round irrigation was represented by adding water to the soil moisture to keep it at 90% of the maximum soil moisture storage capacity, regardless of water availability. For two focus regions, the seasonal cycle of irrigation matched that of the reference dataset, but irrigation application varied between the models by up to 0.8 mm day−1. Because of the irrigation, evaporation increased in all models, but precipitation decreased because of a strong decrease in atmospheric moisture convergence. A moisture tracking scheme was used to track individual evaporated moisture parcels through the atmosphere to determine where these lead to precipitation. Up to 35% of the evaporation moisture from the Ganges basin is recycling within the river basin. However, because of a decreased moisture convergence into the river basin, the total amount of precipitation in the Ganges basin decreases. Although a significant fraction of the evaporation moisture recycles within the river basin, the changes in large-scale wind patterns due to irrigation shift the precipitation from the eastern parts of India and Nepal to the northern and western parts of India and Pakistan. In these areas where precipitation increases, the relative precipitation increase is larger than the relative decrease in the areas where precipitation decreases. It is concluded 1) that the direct effects of irrigation on precipitation are small and are not uniform across the models; 2) that a fraction of up to 35% of any marginal evaporation increase (for example, due to irrigation) will recycle within the river basin; and 3) that when irrigation is applied on a large scale, the dominant effect will be a change in large-scale atmospheric flow that decreases precipitation in eastern India and increases it in western and northern India.

Role of model initialization for projections of 21st-century Greenland ice sheet mass loss - Ađalgeirsdóttir, G.; Aschwanden, A.; Khroulev, C.; Boberg, F.; Mottram, R.; Lucas-Picher, P.; Christensen, J.H. (Journal of Glaciology, 2014)
Abstract Model simulations of the Greenland ice sheet contribution to 21st-century sea-level rise are performed with a state-of-the-art ice-sheet model (Parallel Ice Sheet Model (PISM)). The climate-forcing fields are obtained from the European Union’s Seventh Framework Programme project ice2sea, in which three regional climate models are used to dynamically downscale two scenarios (A1B and E1) from two general circulation models (ECHAM5 and HadCM3). To assess the sensitivity of the projections to the model initial state, four initialization methods are applied. In these experiments, the simulated contribution to sea-level rise by 2100 ranges from an equivalent of 0.2 to 6.8 cm. The largest uncertainties arise from different formulations of the regional climate models (0.8–3.9 cm) and applied scenarios (0.65–1.9 cm), but an important source of uncertainty is the initialization method (0.1–0.8 cm). These model simulations do not account for the recently observed acceleration of ice streams and consequent thinning rates, the changing ice discharge that may result from the spatial and temporal variability of ocean forcing, or the feedback occurring between ice-sheet elevation changes and climate forcing. Thus the results should be considered the lower limit of Greenland ice sheet contributions to sea-level rise, until such processes have been integrated into large-scale ice-sheet models.

Reconstruction of the Spring 2011 Richelieu River Flood by Two Regional Climate Models and a Hydrological Model - Lucas-Picher, Philippe; Riboust, Philippe; Somot, Samuel; Laprise, René (Journal of Hydrometeorology, 2015)
Abstract Climate simulations made with two regional climate models (RCMs), the French Aire Limitée Adaptation Dynamique Développement International (ALADIN) and the Canadian Regional Climate Model, version 5 (CRCM5), operating on 10-km meshes for the period 1989–2011, and the Hydro-Québec hydrological model (HSAMI), are used to reconstruct the spring 2011 Richelieu River flood in the southern region of the province of Québec, Canada. The analysis shows that the simulated fields of 2-m air temperature, precipitation, and snow water equivalent by the RCMs closely match the observations with similar multiyear means and a high correlation of the monthly anomalies. The climatic conditions responsible for the 2011 flood are generally well simulated by the RCMs. The use of multidecadal RCM simulations facilitates the identification of anomalies that contributed to the flood. The flood was linked to a combination of factors: the 2010/11 winter was cold and snowy, the snowmelt in spring was fast, and there was a record amount of precipitation in April and May. Driven by outputs from the RCMs, HSAMI was able to reproduce the mean hydrograph of the Richelieu River, but it underestimated the peak of the 2011 flood. HSAMI adequately computes the water transport from the mountains to the river mouth and the storage effect of Lake Champlain, which dampens the flood over a long period. Overall, the results suggest that RCM simulations can be useful for reconstructing high-resolution climate information and providing new variables that can help better understand the causes of extreme climatic events.

Assessing the limits of bias‐correcting climate model outputs for climate change impact studies - Chen, Jie; Brissette, François P.; Lucas‐Picher, Philippe (Journal of Geophysical Research: Atmospheres, 2015)
Abstract Bias correction of climate model outputs has emerged as a standard procedure in most recent climate change impact studies. A crucial assumption of all bias correction approaches is that climate model biases are constant over time. The validity of this assumption has important implications for impact studies and needs to be verified to properly address uncertainty in future climate projections. Using 10 climate model simulations, this study specifically tests the bias stationarity of climate model outputs over Canada and the contiguous United States (U.S.) by comparing model outputs with corresponding observations over two 20 year historical periods (1961–1980 and 1981–2000). The results show that precipitation biases are clearly nonstationary over much of Canada and the contiguous U.S. and where they vary over much shorter time scales than those normally considered in climate change impact studies. In particular, the difference in biases over two very close periods of the recent past are, in fact, comparable to the climate change signal between future (2061–2080) and historical (1961–1980) periods for precipitation over large parts of Canada and the contiguous U.S., indicating that the uncertainty of future impacts may have been underestimated in most impact studies. In comparison, temperature bias can be considered to be approximately stationary for most of Canada and the contiguous U.S. when compared with the magnitude of the climate change signal. Given the reality that precipitation is usually considered to be more important than temperature for many impact studies, it is advisable that natural climate variability and climate model sensitivity be better emphasized in future impact studies. , Key Points Climate model biases are nonstationary over much of North America The difference in biases is comparable to the climate change signal The uncertainty of impacts may have been underestimated in most impact studies

Transferability of optimally-selected climate models in the quantification of climate change impacts on hydrology - Chen, Jie; Brissette, François P.; Lucas-Picher, Philippe (Climate Dynamics, 2016)

Using Natural Variability as a Baseline to Evaluate the Performance of Bias Correction Methods in Hydrological Climate Change Impact Studies - Chen, Jie; St-Denis, Blaise Gauvin; Brissette, François P.; Lucas-Picher, Philippe (Journal of Hydrometeorology, 2016)
Abstract Postprocessing of climate model outputs is usually performed to remove biases prior to performing climate change impact studies. The evaluation of the performance of bias correction methods is routinely done by comparing postprocessed outputs to observed data. However, such an approach does not take into account the inherent uncertainty linked to natural climate variability and may end up recommending unnecessary complex postprocessing methods. This study evaluates the performance of bias correction methods using natural variability as a baseline. This baseline implies that any bias between model simulations and observations is only significant if it is larger than the natural climate variability. Four bias correction methods are evaluated with respect to reproducing a set of climatic and hydrological statistics. When using natural variability as a baseline, complex bias correction methods still outperform the simplest ones for precipitation and temperature time series, although the differences are much smaller than in all previous studies. However, after driving a hydrological model using the bias-corrected precipitation and temperature, all bias correction methods perform similarly with respect to reproducing 46 hydrological metrics over two watersheds in different climatic zones. The sophisticated distribution mapping correction methods show little advantage over the simplest scaling method. The main conclusion is that simple bias correction methods appear to be just as good as other more complex methods for hydrological climate change impact studies. While sophisticated methods may appear more theoretically sound, this additional complexity appears to be unjustified in hydrological impact studies when taking into account the uncertainty linked to natural climate variability.

Use of Four Reanalysis Datasets to Assess the Terrestrial Branch of the Water Cycle over Quebec, Canada - Sabarly, Florent; Essou, Gilles; Lucas-Picher, Philippe; Poulin, Annie; Brissette, François (Journal of Hydrometeorology, 2016)
Abstract Reanalyses have the potential to provide meteorological information in areas where few or no traditional observation records are available. The terrestrial branch of the water cycle of CFSR, MERRA, ERA-Interim, and NARR is examined over Quebec, Canada, for the 1979–2008 time period. Precipitation, evaporation, runoff, and water balance are studied using observed precipitation and streamflows, according to three spatial scales: 1) the entire province of Quebec, 2) five regions derived from a climate classification, and 3) 11 river basins. The results reveal that MERRA provides a relatively closed water balance, while a significant residual was found for the other three reanalyses. MERRA and ERA-Interim seem to provide the most reliable precipitation over the province. On the other hand, precipitation from CFSR and NARR do not appear to be particularly reliable, especially over southern Quebec, as they almost systematically showed the highest and the lowest values, respectively. Moreover, the partitioning of precipitation into evaporation and runoff from MERRA and NARR does not agree with what was expected, particularly over southern, central, and eastern Quebec. Despite the weaknesses identified, the ability of reanalyses to reproduce the terrestrial water cycle of the recent past (i.e., 1979–2008) remains globally satisfactory. Nonetheless, their potential to provide reliable information must be validated by comparing reanalyses directly with weather stations, especially in remote areas.

How does large-scale nudging in a regional climate model contribute to improving the simulation of weather regimes and seasonal extremes over North America? - Lucas-Picher, Philippe; Cattiaux, Julien; Bougie, Alexandre; Laprise, René (Climate Dynamics, 2016)

Evidence of added value in North American regional climate model hindcast simulations using ever-increasing horizontal resolutions - Lucas-Picher, Philippe; Laprise, René; Winger, Katja (Climate Dynamics, 2017)

The Use of Reanalyses and Gridded Observations as Weather Input Data for a Hydrological Model: Comparison of Performances of Simulated River Flows Based on the Density of Weather Stations - Essou, Gilles R. C.; Brissette, François; Lucas-Picher, Philippe (Journal of Hydrometeorology, 2017)
Abstract Precipitation forcing is critical for hydrological modeling as it has a strong impact on the accuracy of simulated river flows. In general, precipitation data used in hydrological modeling are provided by weather stations. However, in regions with sparse weather station coverage, the spatial interpolation of the individual weather stations provides a rough approximation of the real precipitation fields. In such regions, precipitation from interpolated weather stations is generally considered unreliable for hydrological modeling. Precipitation estimates from reanalyses could represent an interesting alternative in regions where the weather station density is low. This article compares the performances of river flows simulated by a watershed model using precipitation and temperature estimates from reanalyses and gridded observations. The comparison was carried out based on the density of surface weather stations for 316 Canadian watersheds located in three climatic regions. Three state-of-the-art atmospheric reanalyses—ERA-Interim, CFSR, and MERRA—and one gridded observations database over Canada—Natural Resources Canada (NRCan)—were used. Results showed that the Nash–Sutcliffe values of simulated river flows using precipitation and temperature data from CFSR and NRCan were generally equivalent regardless of the weather station density. ERA-Interim and MERRA performed significantly better than NRCan for watersheds with weather station densities of less than 1 station per 1000 km2 in the mountainous region. Overall, these results indicate that for hydrological modeling in regions with high spatial variability of precipitation such as mountainous regions, reanalyses perform better than gridded observations when the weather station density is low.

Impacts of weighting climate models for hydro-meteorological climate change studies - Chen, Jie; Brissette, François P.; Lucas-Picher, Philippe; Caya, Daniel (Journal of Hydrology, 2017)

Impacts of combining reanalyses and weather station data on the accuracy of discharge modelling - Essou, Gilles R.C.; Brissette, François; Lucas-Picher, Philippe (Journal of Hydrology, 2017)

Application of artificial neural networks in global climate change and ecological research: An overview - Liu, ZeLin; Peng, ChangHui; Xiang, WenHua; Tian, DaLun; Deng, XiangWen; Zhao, MeiFang (Chinese Science Bulletin, 2010)

Soil respiration dynamics in Cinnamomum camphora forest and a nearby Liquidambar formosana forest in Subtropical China - Tian, DaLun; Wang, GuangJun; Yan, WenDe; Xiang, WenHua; Peng, ChangHui (Chinese Science Bulletin, 2010)

A model‐data intercomparison of CO_2 exchange across North America: Results from the North American Carbon Program site synthesis - Schwalm, Christopher R.; Williams, Christopher A.; Schaefer, Kevin; Anderson, Ryan; Arain, M. Altaf; Baker, Ian; Barr, Alan; Black, T. Andrew; Chen, Guangsheng; Chen, Jing Ming; Ciais, Philippe; Davis, Kenneth J.; et al. (Journal of Geophysical Research: Biogeosciences, 2010)
Our current understanding of terrestrial carbon processes is represented in various models used to integrate and scale measurements of CO 2 exchange from remote sensing and other spatiotemporal data. Yet assessments are rarely conducted to determine how well models simulate carbon processes across vegetation types and environmental conditions. Using standardized data from the North American Carbon Program we compare observed and simulated monthly CO 2 exchange from 44 eddy covariance flux towers in North America and 22 terrestrial biosphere models. The analysis period spans ∼220 site‐years, 10 biomes, and includes two large‐scale drought events, providing a natural experiment to evaluate model skill as a function of drought and seasonality. We evaluate models' ability to simulate the seasonal cycle of CO 2 exchange using multiple model skill metrics and analyze links between model characteristics, site history, and model skill. Overall model performance was poor; the difference between observations and simulations was ∼10 times observational uncertainty, with forested ecosystems better predicted than nonforested. Model‐data agreement was highest in summer and in temperate evergreen forests. In contrast, model performance declined in spring and fall, especially in ecosystems with large deciduous components, and in dry periods during the growing season. Models used across multiple biomes and sites, the mean model ensemble, and a model using assimilated parameter values showed high consistency with observations. Models with the highest skill across all biomes all used prescribed canopy phenology, calculated NEE as the difference between GPP and ecosystem respiration, and did not use a daily time step.

Toward dynamic global vegetation models for simulating vegetation–climate interactions and feedbacks: recent developments, limitations, and future challenges - Quillet, Anne; Peng, Changhui; Garneau, Michelle (Environmental Reviews, 2010)
There is a lack in representation of biosphere–atmosphere interactions in current climate models. To fill this gap, one may introduce vegetation dynamics in surface transfer schemes or couple global climate models (GCMs) with vegetation dynamics models. As these vegetation dynamics models were not designed to be included in GCMs, how are the latest generation dynamic global vegetation models (DGVMs) suitable for use in global climate studies? This paper reviews the latest developments in DGVM modelling as well as the development of DGVM–GCM coupling in the framework of global climate studies. Limitations of DGVM and coupling are shown and the challenges of these methods are highlighted. During the last decade, DGVMs underwent major changes in the representation of physical and biogeochemical mechanisms such as photosynthesis and respiration processes as well as in the representation of regional properties of vegetation. However, several limitations such as carbon and nitrogen cycles, competition, land-use and land-use changes, and disturbances have been identified. In addition, recent advances in model coupling techniques allow the simulation of the vegetation–atmosphere interactions in GCMs with the help of DGVMs. Though DGVMs represent a good alternative to investigate vegetation–atmosphere interactions at a large scale, some weaknesses in evaluation methodology and model design need to be further investigated to improve the results.

Evaluating the spatiotemporal variations of water budget across China over 1951–2006 using IBIS model - Zhu, Qiuan; Jiang, Hong; Liu, Jinxun; Wei, Xiaohua; Peng, Changhui; Fang, Xiuqing; Liu, Shirong; Zhou, Guomo; Yu, Shuquan; Ju, Weiming (Hydrological Processes, 2010)
Abstract The Integrated Biosphere Simulator is used to evaluate the spatial and temporal patterns of the crucial hydrological variables [run‐off and actual evapotranspiration (AET)] of the water balance across China for the period 1951–2006 including a precipitation analysis. Results suggest three major findings. First, simulated run‐off captured 85% of the spatial variability and 80% of the temporal variability for 85 hydrological gauges across China. The mean relative errors were within 20% for 66% of the studied stations and within 30% for 86% of the stations. The Nash–Sutcliffe coefficients indicated that the quantity pattern of run‐off was also captured acceptably except for some watersheds in southwestern and northwestern China. The possible reasons for underestimation of run‐off in the Tibetan plateau include underestimation of precipitation and uncertainties in other meteorological data due to complex topography, and simplified representations of the soil depth attribute and snow processes in the model. Second, simulated AET matched reasonably with estimated values calculated as the residual of precipitation and run‐off for watersheds controlled by the hydrological gauges. Finally, trend analysis based on the Mann–Kendall method indicated that significant increasing and decreasing patterns in precipitation appeared in the northwest part of China and the Yellow River region, respectively. Significant increasing and decreasing trends in AET were detected in the Southwest region and the Yangtze River region, respectively. In addition, the Southwest region, northern China (including the Heilongjiang, Liaohe, and Haihe Basins), and the Yellow River Basin showed significant decreasing trends in run‐off, and the Zhemin hydrological region showed a significant increasing trend. Copyright © 2009 John Wiley & Sons, Ltd.

Altitudinal changes in carbon storage of temperate forests on Mt Changbai, Northeast China - Zhu, Biao; Wang, Xiangping; Fang, Jingyun; Piao, Shilong; Shen, Haihua; Zhao, Shuqing; Peng, Changhui (Journal of Plant Research, 2010)

Nitrous oxide fluxes from the littoral zone of a lake on the Qinghai-Tibetan Plateau - Chen, Huai; Wang, Meng; Wu, Ning; Wang, Yanfen; Zhu, Dan; Gao, Yongheng; Peng, Changhui (Environmental Monitoring and Assessment, 2011)

A long-term evaluation of biomass production in first and second rotations of Chinese fir plantations at the same site - Tian, D.; Xiang, W.; Chen, X.; Yan, W.; Fang, X.; Kang, W.; Dan, X.; Peng, C.; Peng, Y. (Forestry, 2011)

Quantification of provincial-level carbon emissions from energy consumption in China - Geng, Yuhuan; Tian, Mingzhong; Zhu, Qiuan; Zhang, Jianjun; Peng, Changhui (Renewable and Sustainable Energy Reviews, 2011)

Weak indirect effects inherent to nitrogen biogeochemical cycling within anthropogenic ecosystems: A network environ analysis - Min, Yong; Jin, Xiaogang; Chang, Jie; Peng, Changhui; Gu, Baojing; Ge, Ying; Zhong, Yang (Ecological Modelling, 2011)

Leaf respiration/photosynthesis relationship and variation: an investigation of 39 woody and herbaceous species in east subtropical China - Chu, Ziyan; Lu, Yijun; Chang, Jie; Wang, Meng; Jiang, Hong; He, Jinsheng; Peng, Changhui; Ge, Ying (Trees, 2011)

Detecting One-Hundred-Year Environmental Changes in Western China Using Seven-Year Repeat Photography - Chen, Huai; Yin, Kaipu; Wang, Haiyan; Zhong, Shenxian; Wu, Ning; Shi, Fusun; Zhu, Dan; Zhu, Qiuan; Wang, Weifeng; Ma, Zhihai; Fang, Xiuqin; Li, Weizhong; et al. (PLoS ONE, 2011)

Assessment of net ecosystem services of plastic greenhouse vegetable cultivation in China - Chang, Jie; Wu, Xu; Liu, Anqin; Wang, Yan; Xu, Bin; Yang, Wu; Meyerson, Laura A.; Gu, Baojing; Peng, Changhui; Ge, Ying (Ecological Economics, 2011)

Evaluating the effects of future climate change and elevated CO2 on the water use efficiency in terrestrial ecosystems of China - Zhu, Qiuan; Jiang, Hong; Peng, Changhui; Liu, Jinxun; Wei, Xiaohua; Fang, Xiuqin; Liu, Shirong; Zhou, Guomo; Yu, Shuquan (Ecological Modelling, 2011)

Selected papers presented in symposia organized at the 2009 conference of the International Society for Ecological Modelling (ISEM) in Quebec City, Canada, October 6–9, 2009 - Larocque, Guy R.; Yue, Tian-Xiang; Peng, Changhui; Bhatti, Jagtar; Etterson, Matthew A.; Kazanci, Caner; Goethals, Peter (Ecological Modelling, 2011)

Focus on quality, not just quantity - Peng, Changhui (Nature, 2011)

General allometric equations and biomass allocation of Pinus massoniana trees on a regional scale in southern China - Xiang, Wenhua; Liu, Shaohui; Deng, Xiangwen; Shen, Aihua; Lei, Xiangdong; Tian, Dalun; Zhao, Meifang; Peng, Changhui (Ecological Research, 2011)
Abstract Applying allometric equations in combination with forest inventory data is an effective approach to use when qualifying forest biomass and carbon storage on a regional scale. The objectives of this study were to (1) develop general allometric tree component biomass equations and (2) investigate tree biomass allocation patterns for Pinus massoniana , a principal tree species native to southern China, by applying 197 samples across 20 site locations. The additive allometric equations utilized to compute stem, branch, needle, root, aboveground, and total tree biomass were developed by nonlinear seemingly unrelated regression. Results show that the relative proportion of stem biomass to tree biomass increased while the contribution of canopy biomass to tree biomass decreased as trees continued to grow through time. Total root biomass was a large biomass pool in itself, and its relative proportion to tree biomass exhibited a slight increase with tree growth. Although equations employing stem diameter at breast height (dbh) alone as a predictor could accurately predict stem, aboveground, root, and total tree biomass, they were poorly fitted to predict the canopy biomass component. The inclusion of the tree height ( H ) variable either slightly improved or did not in any way increase model fitness. Validation results demonstrate that these equations are suitable to estimate stem, aboveground, and total tree biomass across a broad range of P . massoniana stands on a regional scale.

Integrating models with data in ecology and palaeoecology: advances towards a model-data fusion approach: Model-data fusion in ecology - Peng, Changhui; Guiot, Joel; Wu, Haibin; Jiang, Hong; Luo, Yiqi (Ecology Letters, 2011)

Quantification of net carbon flux from plastic greenhouse vegetable cultivation: A full carbon cycle analysis - Wang, Yan; Xu, Hao; Wu, Xu; Zhu, Yimei; Gu, Baojing; Niu, Xiaoyin; Liu, Anqin; Peng, Changhui; Ge, Ying; Chang, Jie (Environmental Pollution, 2011)

Quantifying carbon storage for tea plantations in China - Li, Shiyu; Wu, Xu; Xue, Hui; Gu, Baojng; Cheng, Hao; Zeng, Jianming; Peng, Changhui; Ge, Ying; Chang, Jie (Agriculture, Ecosystems & Environment, 2011)

Methane emissions from the surface of the Three Gorges Reservoir: CH_4 EMISSIONS FROM TGR - Chen, Huai; Yuan, Xingzhong; Chen, Zhongli; Wu, Yuyuan; Liu, Xianshu; Zhu, Dan; Wu, Ning; Zhu, Qiu'an; Peng, Changhui; Li, Weizhong (Journal of Geophysical Research: Atmospheres, 2011)

Delayed spring phenology on the Tibetan Plateau may also be attributable to other factors than winter and spring warming - Chen, Huai; Zhu, Qiuan; Wu, Ning; Wang, Yanfen; Peng, Chang-Hui (Proceedings of the National Academy of Sciences, 2011)

Positive Relationship between Aboveground Carbon Stocks and Structural Diversity in Spruce-Dominated Forest Stands in New Brunswick, Canada - Wang, Weifeng; Lei, Xiangdong; Ma, Zhihai; Kneeshaw, Daniel D.; Peng, Changhui (Forest Science, 2011)
Abstract Maintaining both the structure and functionality of forest ecosystems is a primary goal of forest management. In this study, relationships between structural diversity and aboveground stand carbon (C) stocks were examined in spruce-dominated forests in New Brunswick, Canada. Tree species, size, and height diversity indices as well as a combination of these diversity indices were used to correlate aboveground C stocks. Multiple linear regressions were subsequently used to quantify the relationships between these indices and aboveground C stocks, and partial correlation analysis was also adopted to remove the effects of other explanatory variables. Results show that stand structural diversity has a significant positive effect on aboveground C stocks even though the relationship is weak overall. Positive relationships observed between the diversity indices and aboveground C stocks support the hypothesis that increased structural diversity enhances aboveground C storage capacity. This occurs because complex forest structures allow for greater light infiltration and promote a more efficient resource use by trees, leading to an increase in biomass and C production. Mixed tolerant species composition and uneven-aged stand management in conjunction with selection or partial cutting to maintain high structural diversity is therefore recommended to preserve biodiversity and C stocks in spruce-dominated forests.

Common challenges for ecological modelling: Synthesis of facilitated discussions held at the symposia organized for the 2009 conference of the International Society for Ecological Modelling in Quebec City, Canada, (October 6–9, 2009) - Larocque, G.R.; Mailly, D.; Yue, T.-X.; Anand, M.; Peng, C.; Kazanci, C.; Etterson, M.; Goethals, P.; Jørgensen, S.E.; Schramski, J.R.; McIntire, E.J.B.; Marceau, D.J.; et al. (Ecological Modelling, 2011)

Characterizing the performance of ecosystem models across time scales: A spectral analysis of the North American Carbon Program site-level synthesis - Dietze, Michael C.; Vargas, Rodrigo; Richardson, Andrew D.; Stoy, Paul C.; Barr, Alan G.; Anderson, Ryan S.; Arain, M. Altaf; Baker, Ian T.; Black, T. Andrew; Chen, Jing M.; Ciais, Philippe; Flanagan, Lawrence B.; et al. (Journal of Geophysical Research, 2011)

Carbon sequestration by Chinese bamboo forests and their ecological benefits: assessment of potential, problems, and future challenges - Song, Xinzhang; Zhou, Guomo; Jiang, Hong; Yu, Shuquan; Fu, Jinhe; Li, Weizhong; Wang, Weifeng; Ma, Zhihai; Peng, Changhui (Environmental Reviews, 2011)

Development of TRIPLEX-Management model for simulating the response of forest growth to pre-commercial thinning - Wang, Weifeng; Peng, Changhui; Zhang, S.Y.; Zhou, Xiaolu; Larocque, Guy R.; Kneeshaw, Daniel D.; Lei, Xiangdong (Ecological Modelling, 2011)

A drought-induced pervasive increase in tree mortality across Canada's boreal forests - Peng, Changhui; Ma, Zhihai; Lei, Xiangdong; Zhu, Qiuan; Chen, Huai; Wang, Weifeng; Liu, Shirong; Li, Weizhong; Fang, Xiuqin; Zhou, Xiaolu (Nature Climate Change, 2011)

Overyielding of fine root biomass as increasing plant species richness in subtropical forests in central southern China: Overyielding of fine root biomass as increasing plant species richness in subtropical forests in central southern China - Liu, Cong; Xiang, Wen-Hua; Tian, Da-Lun; Fang, Xi; Peng, Chang-Hui (Chinese Journal of Plant Ecology, 2011)

Elevated UV-B radiation did not affect decomposition rates of needles of two coniferous species in subtropical China - Song, Xin-zhang; Jiang, Hong; Zhang, Hui-ling; Peng, Chang-hui; Yu, Shu-quan (European Journal of Soil Biology, 2011)

Methane Fluxes from Alpine Wetlands of Zoige Plateau in Relation to Water Regime and Vegetation under Two Scales - Chen, Huai; Wu, Ning; Wang, Yanfen; Gao, Yongheng; Peng, Changhui (Water, Air, & Soil Pollution, 2011)

N-fertilization has different effects on the growth, carbon and nitrogen physiology, and wood properties of slow- and fast-growing Populus species - Li, Hong; Li, Mengchun; Luo, Jie; Cao, Xu; Qu, Long; Gai, Ying; Jiang, Xiangning; Liu, Tongxian; Bai, Hua; Janz, Dennis; Polle, Andrea; Peng, Changhui; et al. (Journal of Experimental Botany, 2012)

Drought-induced tree mortality: ecological consequences, causes, and modeling - Wang, Weifeng; Peng, Changhui; Kneeshaw, Daniel D.; Larocque, Guy R.; Luo, Zhibin (Environmental Reviews, 2012)
Drought-induced tree mortality, which rapidly alters forest ecosystem composition, structure, and function, as well as the feedbacks between the biosphere and climate, has occurred worldwide over the past few decades, and is expected to increase pervasively as climate change progresses. The objectives of this review are to (1) highlight the likely ecological consequences of drought-induced tree mortality, (2) synthesize the hypotheses related to drought-induced tree mortality, (3) discuss the implications of current knowledge for modeling tree mortality processes under climate change, and (4) highlight future research needs. First, we emphasize the likely ecological consequences of tree mortality from ecosystem to biome to continental scales. We then document and criticize multiple non-exclusive tree mortality hypotheses (e.g., carbon starvation — carbon supply is less than carbon demand; and hydraulic failure — desiccation from failed water transport) from a more comprehensive ecological perspective. Next, we extend a forest decline concept model, Manion’s framework, by considering new emerging environmental conditions, for a more thorough understanding of the effects of climate change on forest decline. We find that an increase in drought frequency and (or) climate-change-type droughts may trigger increased background tree mortality rates and severe forest dieback events, accelerating species turnover and ecological regime shifts. The contribution of CO 2 fertilization, rising temperature within the optimal growth range, and increased nitrogen deposition may defer or reduce this trend in tree mortality, but such contributions will vary between locations, species, and tree sizes. Multiple hypotheses proposed for drought-induced tree mortality are discussed, but coupling carbon and water cycles could help resolve the debate. The absence of a physiological understanding of tree mortality mechanisms limits the predictive ability of current models from stand-level process-based models to dynamic global vegetation models. We thus suggest that long-term observations, experiments, and models should be tightly interwoven during the research process to better forecast future climate changes and evaluate their impacts on forests.

Quantifying the effects of climate change and harvesting on carbon dynamics of boreal aspen and jack pine forests using the TRIPLEX-Management model - Wang, Weifeng; Peng, Changhui; Kneeshaw, Daniel D.; Larocque, Guy R.; Song, Xinzhang; Zhou, Xiaolu (Forest Ecology and Management, 2012)

Photosynthesis, water use efficiency and stable carbon isotope composition are associated with anatomical properties of leaf and xylem in six poplar species - Cao, X.; Jia, J. B.; Li, H.; Li, M. C.; Luo, J.; Liang, Z. S.; Liu, T. X.; Liu, W. G.; Peng, C. H.; Luo, Z. B. (Plant Biology, 2012)
Abstract Although fast‐growing Populus species consume a large amount of water for biomass production, there are considerable variations in water use efficiency (WUE) across different poplar species. To compare differences in growth, WUE and anatomical properties of leaf and xylem and to examine the relationship between photosynthesis/WUE and anatomical properties of leaf and xylem, cuttings of six poplar species were grown in a botanical garden. The growth performance, photosynthesis, intrinsic WUE (WUE i ), stable carbon isotope composition (δ 13 C) and anatomical properties of leaf and xylem were analysed in these poplar plants. Significant differences were found in growth, photosynthesis, WUE i and anatomical properties among the examined species. Populus cathayana was the clone with the fastest growth and the lowest WUE i /δ 13 C, whereas P. × euramericana had a considerable growth increment and the highest WUE i /δ 13 C. Among the analysed poplar species, the highest total stomatal density in P. cathayana was correlated with its highest stomatal conductance (g s ) and lowest WUE i /δ 13 C. Moreover, significant correlations were observed between WUE i and abaxial stomatal density and stem vessel lumen area. These data suggest that photosynthesis, WUE i and δ 13 C are associated with leaf and xylem anatomy and there are tradeoffs between growth and WUE i . It is anticipated that some poplar species, e.g. P. × euramericana , are better candidates for water‐limited regions and others, e.g. P. cathayana , may be better for water‐abundant areas.

Spatiotemporal Variations in Nitrous Oxide Emissions from an Open Fen on the Qinghai–Tibetan Plateau: a 3-Year Study - Chen, Huai; Wang, Yanfen; Wu, Ning; Zhu, Dan; Li, Wei; Gao, Yongheng; Zhu, Qiu’an; Yang, Gang; Peng, Changhui (Water, Air, & Soil Pollution, 2012)

Determining stem biomass of Pinus massoniana L. through variations in basic density - Zhang, L.; Deng, X.; Lei, X.; Xiang, W.; Peng, C.; Lei, P.; Yan, W. (Forestry, 2012)

An inventory of biogenic volatile organic compounds for a subtropical urban–rural complex - Chang, Jie; Ren, Yuan; Shi, Yan; Zhu, Yimei; Ge, Ying; Hong, Shengmao; Jiao, Li; Lin, Fengmei; Peng, Changhui; Mochizuki, Tomoki; Tani, Akira; Mu, Ying; et al. (Atmospheric Environment, 2012)

The long-term impact of urbanization on nitrogen patterns and dynamics in Shanghai, China - Gu, Baojing; Dong, Xiaoli; Peng, Changhui; Luo, Weidong; Chang, Jie; Ge, Ying (Environmental Pollution, 2012)

Elevated UV-B radiation increased the decomposition of Cinnamomum camphora and Cyclobalanopsis glauca leaf litter in subtropical China - Song, Xinzhang Z.; Zhang, Huiling L.; Chang, Scott X.; Jiang, Hong; Peng, Changhui H.; Yu, Shuquan Q. (Journal of Soils and Sediments, 2012)

Regional drought-induced reduction in the biomass carbon sink of Canada's boreal forests - Ma, Zhihai; Peng, Changhui; Zhu, Qiuan; Chen, Huai; Yu, Guirui; Li, Weizhong; Zhou, Xiaolu; Wang, Weifeng; Zhang, Wenhua (Proceedings of the National Academy of Sciences, 2012)
The boreal forests, identified as a critical “tipping element” of the Earth's climate system, play a critical role in the global carbon budget. Recent findings have suggested that terrestrial carbon sinks in northern high-latitude regions are weakening, but there has been little observational evidence to support the idea of a reduction of carbon sinks in northern terrestrial ecosystems. Here, we estimated changes in the biomass carbon sink of natural stands throughout Canada's boreal forests using data from long-term forest permanent sampling plots. We found that in recent decades, the rate of biomass change decreased significantly in western Canada (Alberta, Saskatchewan, and Manitoba), but there was no significant trend for eastern Canada (Ontario and Quebec). Our results revealed that recent climate change, and especially drought-induced water stress, is the dominant cause of the observed reduction in the biomass carbon sink, suggesting that western Canada's boreal forests may become net carbon sources if the climate change–induced droughts continue to intensify.

Simulations of runoff and evapotranspiration in Chinese fir plantation ecosystems using artificial neural networks - Liu, Zelin; Peng, Changhui; Xiang, Wenhua; Deng, Xiangwen; Tian, DaLun; Zhao, Meifang; Yu, Guirui (Ecological Modelling, 2012)

Simulations show potential for reduced emissions and carbon stocks increase in boreal forests under ecosystem management - Boisvenue, C; Bergeron, Y; Bernier, P; Peng, C (Carbon Management, 2012)

Constructed wetlands as biofuel production systems - Liu, Dong; Wu, Xu; Chang, Jie; Gu, Baojing; Min, Yong; Ge, Ying; Shi, Yan; Xue, Hui; Peng, Changhui; Wu, Jianguo (Nature Climate Change, 2012)

A model‐data comparison of gross primary productivity: Results from the North American Carbon Program site synthesis - Schaefer, Kevin; Schwalm, Christopher R.; Williams, Chris; Arain, M. Altaf; Barr, Alan; Chen, Jing M.; Davis, Kenneth J.; Dimitrov, Dimitre; Hilton, Timothy W.; Hollinger, David Y.; Humphreys, Elyn; Poulter, Benjamin; et al. (Journal of Geophysical Research: Biogeosciences, 2012)
Accurately simulating gross primary productivity (GPP) in terrestrial ecosystem models is critical because errors in simulated GPP propagate through the model to introduce additional errors in simulated biomass and other fluxes. We evaluated simulated, daily average GPP from 26 models against estimated GPP at 39 eddy covariance flux tower sites across the United States and Canada. None of the models in this study match estimated GPP within observed uncertainty. On average, models overestimate GPP in winter, spring, and fall, and underestimate GPP in summer. Models overpredicted GPP under dry conditions and for temperatures below 0°C. Improvements in simulated soil moisture and ecosystem response to drought or humidity stress will improve simulated GPP under dry conditions. Adding a low‐temperature response to shut down GPP for temperatures below 0°C will reduce the positive bias in winter, spring, and fall and improve simulated phenology. The negative bias in summer and poor overall performance resulted from mismatches between simulated and observed light use efficiency (LUE). Improving simulated GPP requires better leaf‐to‐canopy scaling and better values of model parameters that control the maximum potential GPP, such as ε max (LUE), V cmax (unstressed Rubisco catalytic capacity) or J max (the maximum electron transport rate). , Key Points Gross primary productivity (GPP) from 26 models tested at 39 flux tower sites Simulated light use efficiency controls model performance Models overpredict GPP under dry conditions

Effects of future climate change, CO2 enrichment, and vegetation structure variation on hydrological processes in China - Zhu, Qiuan; Jiang, Hong; Peng, Changhui; Liu, Jinxun; Fang, Xiuqin; Wei, Xiaohua; Liu, Shirong; Zhou, Guomo (Global and Planetary Change, 2012)

Assessment of private economic benefits and positive environmental externalities of tea plantation in China - Xue, Hui; Ren, Xiaoyi; Li, Shiyu; Wu, Xu; Cheng, Hao; Xu, Bin; Gu, Baojing; Yang, Guofu; Peng, Changhui; Ge, Ying; Chang, Jie (Environmental Monitoring and Assessment, 2013)

Cadmium tolerance in six poplar species - He, Jiali; Ma, Chaofeng; Ma, Yonglu; Li, Hong; Kang, Jingquan; Liu, Tongxian; Polle, Andrea; Peng, Changhui; Luo, Zhi-Bin (Environmental Science and Pollution Research, 2013)

Evaluating the agreement between measurements and models of net ecosystem exchange at different times and timescales using wavelet coherence: an example using data from the North American Carbon Program Site-Level Interim Synthesis - Stoy, P. C.; Dietze, M. C.; Richardson, A. D.; Vargas, R.; Barr, A. G.; Anderson, R. S.; Arain, M. A.; Baker, I. T.; Black, T. A.; Chen, J. M.; Cook, R. B.; Gough, C. M.; et al. (Biogeosciences, 2013)
Abstract. Earth system processes exhibit complex patterns across time, as do the models that seek to replicate these processes. Model output may or may not be significantly related to observations at different times and on different frequencies. Conventional model diagnostics provide an aggregate view of model–data agreement, but usually do not identify the time and frequency patterns of model–data disagreement, leaving unclear the steps required to improve model response to environmental drivers that vary on characteristic frequencies. Wavelet coherence can quantify the times and timescales at which two time series, for example time series of models and measurements, are significantly different. We applied wavelet coherence to interpret the predictions of 20 ecosystem models from the North American Carbon Program (NACP) Site-Level Interim Synthesis when confronted with eddy-covariance-measured net ecosystem exchange (NEE) from 10 ecosystems with multiple years of available data. Models were grouped into classes with similar approaches for incorporating phenology, the calculation of NEE, the inclusion of foliar nitrogen (N), and the use of model–data fusion. Models with prescribed, rather than prognostic, phenology often fit NEE observations better on annual to interannual timescales in grassland, wetland and agricultural ecosystems. Models that calculated NEE as net primary productivity (NPP) minus heterotrophic respiration (HR) rather than gross ecosystem productivity (GPP) minus ecosystem respiration (ER) fit better on annual timescales in grassland and wetland ecosystems, but models that calculated NEE as GPP minus ER were superior on monthly to seasonal timescales in two coniferous forests. Models that incorporated foliar nitrogen (N) data were successful at capturing NEE variability on interannual (multiple year) timescales at Howland Forest, Maine. The model that employed a model–data fusion approach often, but not always, resulted in improved fit to data, suggesting that improving model parameterization is important but not the only step for improving model performance. Combined with previous findings, our results suggest that the mechanisms driving daily and annual NEE variability tend to be correctly simulated, but the magnitude of these fluxes is often erroneous, suggesting that model parameterization must be improved. Few NACP models correctly predicted fluxes on seasonal and interannual timescales where spectral energy in NEE observations tends to be low, but where phenological events, multi-year oscillations in climatological drivers, and ecosystem succession are known to be important for determining ecosystem function. Mechanistic improvements to models must be made to replicate observed NEE variability on seasonal and interannual timescales.

Nitrous oxide emissions from the surface of the Three Gorges Reservoir - Zhu, Dan; Chen, Huai; Yuan, Xingzhong; Wu, Ning; Gao, Yongheng; Wu, Yan; Zhang, Yongmei; Peng, Changhui; Zhu, Qiu’an; Yang, Gang; Wu, Jianghua (Ecological Engineering, 2013)

The effects of plant diversity on nitrous oxide emissions in hydroponic microcosms - Sun, Hongying; Zhang, Chongbang; Song, Changchun; Chang, Scott X.; Gu, Baojing; Chen, Zhengxin; Peng, Changhui; Chang, Jie; Ge, Ying (Atmospheric Environment, 2013)

Changes in carbon, nutrients and stoichiometric relations under different soil depths, plant tissues and ages in black locust plantations - Li, Hong; Li, Jing; He, Yalong; Li, Shaojun; Liang, Zongsuo; Peng, Changhui; Polle, Andrea; Luo, Zhi-Bin (Acta Physiologiae Plantarum, 2013)

Assessing the spatio-temporal variation and uncertainty patterns of historical and future projected water resources in China - Zhu, Qiuan; Jiang, Hong; Peng, Changhui; Liu, Jinxun; Fang, Xiuqin; Chen, Huai; Liu, Shirong (Journal of Water and Climate Change, 2013)
The spatial and temporal variation and uncertainty of precipitation and runoff in China were compared and evaluated between historical and future periods under different climate change scenarios. The precipitation pattern is derived from observed and future projected precipitation data for historical and future periods, respectively. The runoff is derived from simulation results in historical and future periods using a dynamic global vegetation model (DGVM) forced with historical observed and global climate models (GCMs) future projected climate data, respectively. One GCM (CGCM3.1) under two emission scenarios (SRES A2 and SRES B1) was used for the future period simulations. The results indicated high uncertainties and variations in climate change effects on hydrological processes in China: precipitation and runoff showed a significant increasing trend in the future period but a decreasing trend in the historical period at the national level; the temporal variation and uncertainty of projected precipitation and runoff in the future period were predicted to be higher than those in the historical period; the levels of precipitation and runoff in the future period were higher than those in the historical period. The change in trends of precipitation and runoff are highly affected by different climate change scenarios. GCM structure and emission scenarios should be the major sources of uncertainty.

Global Priority Conservation Areas in the Face of 21st Century Climate Change - Li, Junsheng; Lin, Xin; Chen, Anping; Peterson, Townsend; Ma, Keping; Bertzky, Monika; Ciais, Philippe; Kapos, Valerie; Peng, Changhui; Poulter, Benjamin (PLoS ONE, 2013)

Net fluxes of ammonium and nitrate in association with H+ fluxes in fine roots of Populus popularis - Luo, Jie; Qin, Jingjing; He, Fangfang; Li, Hong; Liu, Tongxian; Polle, Andrea; Peng, Changhui; Luo, Zhi-Bin (Planta, 2013)

Differences in fine root traits between early and late-successional tree species in a Chinese subtropical forest - Xiang, W.; Wu, W.; Tong, J.; Deng, X.; Tian, D.; Zhang, L.; Liu, C.; Peng, C. (Forestry, 2013)

Assessing the role of parameter interactions in the sensitivity analysis of a model of peatland dynamics - Quillet, Anne; Frolking, Steve; Garneau, Michelle; Talbot, Julie; Peng, Changhui (Ecological Modelling, 2013)

Climate warming-induced upward shift of Moso bamboo population on Tianmu Mountain, China - Song, Xin-zhang; Peng, Chang-hui; Zhou, Guo-mo; Jiang, Hong; Wang, Wei-feng; Xiang, Wen-hua (Journal of Mountain Science, 2013)

A climate change‐induced threat to the ecological resilience of a subtropical monsoon evergreen broad‐leaved forest in Southern China - Zhou, Guoyi; Peng, Changhui; Li, Yuelin; Liu, Shizhong; Zhang, Qianmei; Tang, Xuli; Liu, Juxiu; Yan, Junhua; Zhang, Deqiang; Chu, Guowei (Global Change Biology, 2013)
Abstract Recent studies have suggested that tropical forests may not be resilient against climate change in the long term, primarily owing to predicted reductions in rainfall and forest productivity, increased tree mortality, and declining forest biomass carbon sinks. These changes will be caused by drought‐induced water stress and ecosystem disturbances. Several recent studies have reported that climate change has increased tree mortality in temperate and boreal forests, or both mortality and recruitment rates in tropical forests. However, no study has yet examined these changes in the subtropical forests that account for the majority of China's forested land. In this study, we describe how the monsoon evergreen broad‐leaved forest has responded to global warming and drought stress using 32 years of data from forest observation plots. Due to an imbalance in mortality and recruitment, and changes in diameter growth rates between larger and smaller trees and among different functional groups, the average DBH of trees and forest biomass have decreased. Sap flow measurements also showed that larger trees were more stressed than smaller trees by the warming and drying environment. As a result, the monsoon evergreen broad‐leaved forest community is undergoing a transition from a forest dominated by a cohort of fewer and larger individuals to a forest dominated by a cohort of more and smaller individuals, with a different species composition, suggesting that subtropical forests are threatened by their lack of resilience against long‐term climate change.

Effects of Increased Nitrogen Deposition and Rotation Length on Long-Term Productivity of Cunninghamia lanceolata Plantation in Southern China - Zhao, Meifang; Xiang, Wenhua; Tian, Dalun; Deng, Xiangwen; Huang, Zhihong; Zhou, Xiaolu; Peng, Changhui (PLoS ONE, 2013)

Does growing vegetables in plastic greenhouses enhance regional ecosystem services beyond the food supply? - Chang, Jie; Wu, Xu; Wang, Yan; Meyerson, Laura A; Gu, Baojing; Min, Yong; Xue, Hui; Peng, Changhui; Ge, Ying (Frontiers in Ecology and the Environment, 2013)
In recent years, plastic greenhouse vegetable cultivation (PGVC) has expanded worldwide, particularly in China, where it accounts for more than 90% of all global PGVC operations. As compared with conventional agricultural methods, PGVC has doubled crop yields by extending growing seasons and intensifying agriculture. PGVC also offers more ecosystem services relative to conventional approaches, including greater soil carbon sequestration, lower water consumption, and improved soil protection at regional scales. The economic benefits of this easily implemented agricultural method are attractive to small‐holder farmers. However, greater environmental impacts (eg greenhouse‐gas emissions, generation of large amounts of plastic waste) are associated with PGVC than with conventional approaches. Here, we review what is currently known about PGVC and identify future research priorities that will comprehensively assess the ecosystem services offered by this method of cultivation, as well as its environmental impacts and socioeconomic benefits.

The role of industrial nitrogen in the global nitrogen biogeochemical cycle - Gu, Baojing; Chang, Jie; Min, Yong; Ge, Ying; Zhu, Qiuan; Galloway, James N.; Peng, Changhui (Scientific Reports, 2013)

Inter-Annual Variations of Methane Emission from an Open Fen on the Qinghai-Tibetan Plateau: A Three-Year Study - Chen, Huai; Wu, Ning; Wang, Yanfen; Zhu, Dan; Zhu, Qiu’an; Yang, Gang; Gao, Yongheng; Fang, Xiuqin; Wang, Xu; Peng, Changhui (PLoS ONE, 2013)

Methane emissions from rice paddies natural wetlands, lakes in China: synthesis new estimate - Chen, Huai; Zhu, Qiu'an; Peng, Changhui; Wu, Ning; Wang, Yanfen; Fang, Xiuqin; Jiang, Hong; Xiang, Wenhua; Chang, Jie; Deng, Xiangwen; Yu, Guirui (Global Change Biology, 2013)
Abstract Sources of methane ( CH 4 ) become highly variable for countries undergoing a heightened period of development due to both human activity and climate change. An urgent need therefore exists to budget key sources of CH 4 , such as wetlands (rice paddies and natural wetlands) and lakes (including reservoirs and ponds), which are sensitive to these changes. For this study, references in relation to CH 4 emissions from rice paddies, natural wetlands, and lakes in C hina were first reviewed and then reestimated based on the review itself. Total emissions from the three CH 4 sources were 11.25 Tg CH 4 yr −1 (ranging from 7.98 to 15.16 Tg CH 4 yr −1 ). Among the emissions, 8.11 Tg CH 4 yr −1 (ranging from 5.20 to 11.36 Tg CH 4 yr −1 ) derived from rice paddies, 2.69 Tg CH 4 yr −1 (ranging from 2.46 to 3.20 Tg CH 4 yr −1 ) from natural wetlands, and 0.46 Tg CH 4 yr −1 (ranging from 0.33 to 0.59 Tg CH 4 yr −1 ) from lakes (including reservoirs and ponds). Plentiful water and warm conditions, as well as its large rice paddy area make rice paddies in southeastern C hina the greatest overall source of CH 4 , accounting for approximately 55% of total paddy emissions. Natural wetland estimates were slightly higher than the other estimates owing to the higher CH 4 emissions recorded within Q inghai‐ T ibetan P lateau peatlands. Total CH 4 emissions from lakes were estimated for the first time by this study, with three quarters from the littoral zone and one quarter from lake surfaces. Rice paddies, natural wetlands, and lakes are not constant sources of CH 4 , but decreasing ones influenced by anthropogenic activity and climate change. A new progress‐based model used in conjunction with more observations through model‐data fusion approach could help obtain better estimates and insights with regard to CH 4 emissions deriving from wetlands and lakes in C hina.

MODELING INDIVIDUAL TREE MORTALITY RATES USING MARGINAL AND RANDOM EFFECTS REGRESSION MODELS - Ma, Zhihai; Peng, Changhui; Li, Weizhong; Zhu, Qiuan; Wang, Weifeng; Song, Xinzhang; Liu, Jianwei (Natural Resource Modeling, 2013)
A bstract Developing models to predict tree mortality using data from long‐term repeated measurement data sets can be difficult and challenging due to the nature of mortality as well as the effects of dependence on observations. Marginal (population‐averaged) generalized estimating equations (GEE) and random effects (subject‐specific) models offer two possible ways to overcome these effects. For this study, standard logistic, marginal logistic based on the GEE approach, and random logistic regression models were fitted and compared. In addition, four model evaluation statistics were calculated by means of K ‐fold cross‐valuation. They include the mean prediction error, the mean absolute prediction error, the variance of prediction error, and the mean square error. Results from this study suggest that the random effects model produced the smallest evaluation statistics among the three models. Although marginal logistic regression accommodated for correlations between observations, it did not provide noticeable improvements of model performance compared to the standard logistic regression model that assumed impendence. This study indicates that the random effects model was able to increase the overall accuracy of mortality modeling. Moreover, it was able to ascertain correlation derived from the hierarchal data structure as well as serial correlation generated through repeated measurements.

Incorporating weather sensitivity in inventory-based estimates of boreal forest productivity: A meta-analysis of process model results - Wang, Z.; Grant, R.F.; Arain, M.A.; Bernier, P.Y.; Chen, B.; Chen, J.M.; Govind, A.; Guindon, L.; Kurz, W.A.; Peng, C.; Price, D.T.; Stinson, G.; et al. (Ecological Modelling, 2013)

Application of TRIPLEX model for predicting Cunninghamia lanceolata and Pinus massoniana forest stand production in Hunan Province, southern China - Zhao, Meifang; Xiang, Wenhua; Deng, Xiangwen; Tian, Dalun; Huang, Zhihong; Zhou, Xiaolu; Yu, Guirui; He, Honglin; Peng, Changhui (Ecological Modelling, 2013)

The impacts of climate change and human activities on biogeochemical cycles on the Q inghai‐ T ibetan P lateau - Chen, Huai; Zhu, Qiuan; Peng, Changhui; Wu, Ning; Wang, Yanfen; Fang, Xiuqing; Gao, Yongheng; Zhu, Dan; Yang, Gang; Tian, Jianqing; Kang, Xiaoming; Piao, Shilong; et al. (Global Change Biology, 2013)
Abstract With a pace of about twice the observed rate of global warming, the temperature on the Qinghai‐Tibetan Plateau (Earth's ‘third pole’) has increased by 0.2 °C per decade over the past 50 years, which results in significant permafrost thawing and glacier retreat. Our review suggested that warming enhanced net primary production and soil respiration, decreased methane ( CH 4 ) emissions from wetlands and increased CH 4 consumption of meadows, but might increase CH 4 emissions from lakes. Warming‐induced permafrost thawing and glaciers melting would also result in substantial emission of old carbon dioxide ( CO 2 ) and CH 4 . Nitrous oxide ( N 2 O ) emission was not stimulated by warming itself, but might be slightly enhanced by wetting. However, there are many uncertainties in such biogeochemical cycles under climate change. Human activities (e.g. grazing, land cover changes) further modified the biogeochemical cycles and amplified such uncertainties on the plateau. If the projected warming and wetting continues, the future biogeochemical cycles will be more complicated. So facing research in this field is an ongoing challenge of integrating field observations with process‐based ecosystem models to predict the impacts of future climate change and human activities at various temporal and spatial scales. To reduce the uncertainties and to improve the precision of the predictions of the impacts of climate change and human activities on biogeochemical cycles, efforts should focus on conducting more field observation studies, integrating data within improved models, and developing new knowledge about coupling among carbon, nitrogen, and phosphorus biogeochemical cycles as well as about the role of microbes in these cycles.

Direct and Indirect Effects of UV-B Exposure on Litter Decomposition: A Meta-Analysis - Song, Xinzhang; Peng, Changhui; Jiang, Hong; Zhu, Qiuan; Wang, Weifeng (PLoS ONE, 2013)

Monitoring and estimating drought-induced impacts on forest structure, growth, function, and ecosystem services using remote-sensing data: recent progress and future challenges - Zhang, Yao; Peng, Changhui; Li, Weizhong; Fang, Xiuqin; Zhang, Tinglong; Zhu, Qiuan; Chen, Huai; Zhao, Pengxiang (Environmental Reviews, 2013)
Alongside global warming, droughts are expected to increase in frequency, severity, and extent in the near future, which will likely result in significant impacts on forest growth, production, structure, composition, and ecosystem services. However, due to spatial and temporal characteristics, it is difficult to monitor and assess the potential effects of droughts. Remote sensing can provide an effective way to obtain real-time conditions of forests affected by drought and offer a range of spatial and temporal insights into drought-induced changes to forest ecosystem structure, function, and services. Remote sensing is rapidly developing as more satellites are launched. In situ and remotely sensed data fusion techniques have achieved notable success in assessing drought-induced damage to forests and carbon cycles. Even so, constraints still exist when using satellite data. The objectives of this review are to (1) briefly review existing data sources and methods of remote sensing; (2) synthesize current applications and contributions of remote sensing in monitoring and estimating impacts of droughts on forest ecosystems; and (3) highlight research gaps and future challenges.

Plant phenological modeling and its application in global climate change research: overview and future challenges - Zhao, Meifang; Peng, Changhui; Xiang, Wenhua; Deng, Xiangwen; Tian, Dalun; Zhou, Xiaolu; Yu, Guirui; He, Honglin; Zhao, Zhonghui (Environmental Reviews, 2013)
Plants interact to the seasonality of their environments, and changes in plant phenology have long been regarded as sensitive indicators of climatic change. Plant phenology modeling has been shown to be the simplest and most useful tool to assess phenol–climate shifts. Temperature, solar radiation, and water availability are assumed to be the key factors that control plant phenology. Statistical, mechanistic, and theoretical approaches have often been used for the parameterization of plant phenology models. The statistical approaches correlate the timing of phenological events to environmental factors or heat unit accumulations. The approaches have the simplified calculation procedures, correct phenological mechanism assumptions, but limited applications and predictive abilities. The mechanistic approaches describe plant phenology with the known or assumed “cause–effect relationships” between biological processes and key driving variables. The mechanistic approaches have the improved parameter processes, realistic assumptions, broad applications, and effective predictions. The theoretical approaches assume cost–benefit tradeoff strategies in trees. These methods are capable of capturing and quantifying the potential impacts and consequences of global climate change and human activity. However, certain limitations still exist related to our understanding of phenological mechanisms in relation to (1) interactions between plants and their specific climates, (2) the integration of both field observational and remote sensing data with plant phenology models across taxa and ecosystem type, (3) amplitude clarification of scale-related sensitivity to global climate change, and (4) improvements in parameterization processes and the overall reduction of modeling uncertainties to forecast impacts of future climate change on plant phenological dynamics. To improve our capacity in the prediction of the amplitude of plant phenological responses with regard to both structural and functional sensitivity to future global climate change, it is important to refine modeling methodologies by applying long-term and large-scale observational data. It is equally important to consider other less used but critical factors (such as heredity, pests, and anthropogenic drivers), apply advanced model parameterization and data assimilation techniques, incorporate process-based plant phenology models as a dynamic component into global vegetation dynamic models, and test plant phenology models against long-term ground observations and high-resolution satellite data across different spatial and temporal scales.

Nitrogen metabolism of two contrasting poplar species during acclimation to limiting nitrogen availability - Luo, Jie; Li, Hong; Liu, Tongxian; Polle, Andrea; Peng, Changhui; Luo, Zhi-Bin (Journal of Experimental Botany, 2013)

Policy options towards deforestation reduction in Cameroon: An analysis based on a systematic approach - Epule, Epule Terence; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Land Use Policy, 2014)

Carbon dynamics of peatlands in China during the Holocene - Wang, Mei; Chen, Huai; Wu, Ning; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; Yang, Gang; Wu, Jianghua; He, Yixin; Gao, Yongheng; Tian, Jianqing; Zhao, Xinquan (Quaternary Science Reviews, 2014)

An assessment of the predictors of the dynamics in arable production per capita index, arable production and permanent cropland and forest area based on structural equation models - Epule, Epule Terence; Bryant, Christopher Robin; Akkari, Cherine; Sarr, Mamadou Adama; Peng, Changhui (SpringerPlus, 2014)

Soil N forms and gross transformation rates in Chinese subtropical forests dominated by different tree species - Zeng, Yelin; Xiang, Wenhua; Deng, Xiangwen; Fang, Xi; Liu, Cong; Peng, Changhui (Plant and Soil, 2014)

Eradicating invasive Spartina alterniflora with alien Sonneratia apetala and its implications for invasion controls - Chen, Huai; Liao, Baowen; Liu, Bin’er; Peng, Changhui; Zhang, Yao; Guan, Wei; Zhu, Qiu’an; Yang, Gang (Ecological Engineering, 2014)

Applying an artificial neural network to simulate and predict Chinese fir (Cunninghamia lanceolata) plantation carbon flux in subtropical China - Wen, Xuding; Zhao, Zhonghui; Deng, Xiangwen; Xiang, Wenhua; Tian, Dalun; Yan, Wende; Zhou, Xiaolu; Peng, Changhui (Ecological Modelling, 2014)

High carbon dioxide uptake by subtropical forest ecosystems in the East Asian monsoon region - Yu, Guirui; Chen, Zhi; Piao, Shilong; Peng, Changhui; Ciais, Philippe; Wang, Qiufeng; Li, Xuanran; Zhu, Xianjin (Proceedings of the National Academy of Sciences, 2014)
Significance Understanding the location of carbon sources and sinks is essential for accurately predicting future changes in atmospheric carbon dioxide and climate. Mid- to high-latitude terrestrial ecosystems are well known to be the principal carbon sink regions, yet less attention has been paid to the mid- to low-latitude ecosystems. In this study, long-term eddy covariance observations demonstrate that there is a high carbon dioxide uptake (net ecosystem productivity) by the mid- to low-latitude East Asian monsoon subtropical forests that were shaped by the uplift of the Tibetan Plateau. Increasing nitrogen deposition, a young forest age structure, and sufficient water and heat availability combined to contribute to this large carbon dioxide uptake. , Temperate- and high-latitude forests have been shown to contribute a carbon sink in the Northern Hemisphere, but fewer studies have addressed the carbon balance of the subtropical forests. In the present study, we integrated eddy covariance observations established in the 1990s and 2000s to show that East Asian monsoon subtropical forests between 20°N and 40°N represent an average net ecosystem productivity (NEP) of 362 ± 39 g C m −2 yr −1 (mean ± 1 SE). This average forest NEP value is higher than that of Asian tropical and temperate forests and is also higher than that of forests at the same latitudes in Europe–Africa and North America. East Asian monsoon subtropical forests have comparable NEP to that of subtropical forests of the southeastern United States and intensively managed Western European forests. The total NEP of East Asian monsoon subtropical forests was estimated to be 0.72 ± 0.08 Pg C yr −1 , which accounts for 8% of the global forest NEP. This result indicates that the role of subtropical forests in the current global carbon cycle cannot be ignored and that the regional distributions of the Northern Hemisphere's terrestrial carbon sinks are needed to be reevaluated. The young stand ages and high nitrogen deposition, coupled with sufficient and synchronous water and heat availability, may be the primary reasons for the high NEP of this region, and further studies are needed to quantify the contribution of each underlying factor.

Chinese Grain for Green Program led to highly increased soil organic carbon levels: A meta-analysis - Song, Xinzhang; Peng, Changhui; Zhou, Guomo; Jiang, Hong; Wang, Weifeng (Scientific Reports, 2014)

Ectomycorrhizas with P axillus involutus enhance cadmium uptake and tolerance in P opulus × canescens - Ma, Yonglu; He, Jiali; Ma, Chaofeng; Luo, Jie; Li, Hong; Liu, Tongxian; Polle, Andrea; Peng, Changhui; Luo, Zhi‐Bin (Plant, Cell & Environment, 2014)
Ectomycorrhizas ( EMs ), which are symbiotic organs formed between tree roots and certain fungi, can mediate cadmium ( Cd ) tolerance of host plants, but the underlying physiological and molecular mechanisms are not fully understood. P opulus × canescens was inoculated with or without P axillus involutus (strain MAJ ) and subsequently exposed to 0 or 50 μM CdSO 4 . Higher net Cd 2+ influx in EMs well corresponded to higher transcript levels of genes involved in Cd 2+ uptake, transport and detoxification processes than those in nonmycorrhizal roots. Higher CO 2 assimilation, improved nutrient and carbohydrate status, and alleviated oxidative stress were found in mycorrhizal compared to nonmycorrhizal poplars despite higher Cd 2+ accumulation. , Abstract Ectomycorrhizas ( EMs ), which are symbiotic organs formed between tree roots and certain fungi, can mediate cadmium ( Cd ) tolerance of host plants, but the underlying physiological and molecular mechanisms are not fully understood. To investigate EMs mediated Cd tolerance in woody plants, P opulus × canescens was inoculated with P axillus involutus (strain MAJ ) to establish mycorrhizal roots. Mycorrhizal poplars and non‐mycorrhizal controls were exposed to 0 or 50 μ M CdSO 4 . EMs displayed higher net Cd 2+ influx than non‐mycorrhizal roots. Net Cd 2+ influx was coupled with net H + efflux and inactivation of plasma membrane ( PM ) H + ‐ ATPases reduced Cd 2+ uptake of EMs less than of non‐mycorrhizal roots. Consistent with higher Cd 2+ uptake in EMs , in most cases, transcript levels of genes involved in Cd 2+ uptake, transport and detoxification processes were increased in EMs compared to non‐mycorrhizal roots. Higher CO 2 assimilation, improved nutrient and carbohydrate status, and alleviated oxidative stress were found in mycorrhizal compared to non‐mycorrhizal poplars despite higher Cd 2+ accumulation. These results indicate that mycorrhizas increase Cd 2+ uptake, probably by an enlarged root volume and overexpression of genes involved in Cd 2+ uptake and transport, and concurrently enhance P o. × canescens Cd tolerance by increased detoxification, improved nutrient and carbohydrate status and defence preparedness.

Interactive effects of elevated UV-B radiation and N deposition on decomposition of Moso bamboo litter - Song, Xinzhang; Jiang, Hong; Zhang, Zhiting; Zhou, Guomo; Zhang, Shuikui; Peng, Changhui (Soil Biology and Biochemistry, 2014)

Modeling dissolved organic carbon in temperate forest soils: TRIPLEX-DOC model development and validation - Wu, H.; Peng, C.; Moore, T. R.; Hua, D.; Li, C.; Zhu, Q.; Peichl, M.; Arain, M. A.; Guo, Z. (Geoscientific Model Development, 2014)
Abstract. Even though dissolved organic carbon (DOC) is the most active carbon (C) cycling in soil organic carbon (SOC) pools, it receives little attention from the global C budget. DOC fluxes are critical to aquatic ecosystem inputs and contribute to the C balance of terrestrial ecosystems, but few ecosystem models have attempted to integrate DOC dynamics into terrestrial C cycling. This study introduces a new process-based model, TRIPLEX-DOC, that is capable of estimating DOC dynamics in forest soils by incorporating both ecological drivers and biogeochemical processes. TRIPLEX-DOC was developed from Forest-DNDC, a biogeochemical model simulating C and nitrogen (N) dynamics, coupled with a new DOC process module that predicts metabolic transformations, sorption/desorption, and DOC leaching in forest soils. The model was validated against field observations of DOC concentrations and fluxes at white pine forest stands located in southern Ontario, Canada. The model was able to simulate seasonal dynamics of DOC concentrations and the magnitudes observed within different soil layers, as well as DOC leaching in the age sequence of these forests. Additionally, TRIPLEX-DOC estimated the effect of forest harvesting on DOC leaching, with a significant increase following harvesting, illustrating that land use change is of critical importance in regulating DOC leaching in temperate forests as an important source of C input to aquatic ecosystems.

Modelling methane emissions from natural wetlands by development and application of the TRIPLEX-GHG model - Zhu, Q.; Liu, J.; Peng, C.; Chen, H.; Fang, X.; Jiang, H.; Yang, G.; Zhu, D.; Wang, W.; Zhou, X. (Geoscientific Model Development, 2014)
Abstract. A new process-based model TRIPLEX-GHG was developed based on the Integrated Biosphere Simulator (IBIS), coupled with a new methane (CH4) biogeochemistry module (incorporating CH4 production, oxidation, and transportation processes) and a water table module to investigate CH4 emission processes and dynamics that occur in natural wetlands. Sensitivity analysis indicates that the most sensitive parameters to evaluate CH4 emission processes from wetlands are r (defined as the CH4 to CO2 release ratio) and Q10 in the CH4 production process. These two parameters were subsequently calibrated to data obtained from 19 sites collected from approximately 35 studies across different wetlands globally. Being heterogeneously spatially distributed, r ranged from 0.1 to 0.7 with a mean value of 0.23, and the Q10 for CH4 production ranged from 1.6 to 4.5 with a mean value of 2.48. The model performed well when simulating magnitude and capturing temporal patterns in CH4 emissions from natural wetlands. Results suggest that the model is able to be applied to different wetlands under varying conditions and is also applicable for global-scale simulations.

Relationship between Air Pollutants and Economic Development of the Provincial Capital Cities in China during the Past Decade - Luo, Yunpeng; Chen, Huai; Zhu, Qiu'an; Peng, Changhui; Yang, Gang; Yang, Yanzheng; Zhang, Yao (PLoS ONE, 2014)

Effects of soil warming, rainfall reduction and water table level on CH 4 emissions from the Zoige peatland in China - Yang, Gang; Chen, Huai; Wu, Ning; Tian, Jianqing; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; He, Yixin; Zheng, Qunying; Zhang, Changbing (Soil Biology and Biochemistry, 2014)

The carbon stock of alpine peatlands on the Qinghai–Tibetan Plateau during the Holocene and their future fate - Chen, Huai; Yang, Gang; Peng, Changhui; Zhang, Yao; Zhu, Dan; Zhu, Qiuan; Hu, Ji; Wang, Mei; Zhan, Wei; Zhu, Erxiong; Bai, Zengzhi; Li, Wei; et al. (Quaternary Science Reviews, 2014)

Soil methane uptake by grasslands and forests in China - Wang, Yanfen; Chen, Huai; Zhu, Qiuan; Peng, Changhui; Wu, Ning; Yang, Gang; Zhu, Dan; Tian, Jianqing; Tian, Liuxi; Kang, Xiaoming; He, Yixin; Gao, Yongheng; et al. (Soil Biology and Biochemistry, 2014)

The causes, effects and challenges of Sahelian droughts: a critical review - Epule, Epule Terence; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Regional Environmental Change, 2014)

Climate Change Contribution to Forest Growth in Eastern China over Past Two Decades - Jin, Jiaxin; Jiang, Hong; Peng, Changhui; Zhang, Xiuying; Wang, Ying; Wang, Jinyin (Terrestrial, Atmospheric and Oceanic Sciences, 2014)

Quantification of soil respiration in forest ecosystems across China - Song, Xinzhang; Peng, Changhui; Zhao, Zhengyong; Zhang, Zhiting; Guo, Baohua; Wang, Weifeng; Jiang, Hong; Zhu, Qiuan (Atmospheric Environment, 2014)

Combination of nitrogen deposition and ultraviolet-B radiation decreased litter decomposition in subtropical China - Song, Xinzhang; Zhang, Huiling; Jiang, Hong; Peng, Changhui (Plant and Soil, 2014)

The 5000-year climate change of northeastern Qinghai-Tibetan Plateau and historical ecology of Zoige wetlands - He Yixin, 何奕忻; Wu Ning, 吴宁; Zhu Qiu'an, 朱求安; Chen Huai, 陈槐; Zhu Dan, 朱单; Peng Changhui, 彭长辉; Yang Gang, 杨刚; Gao Yongheng, 高永恒; Zhao Chuan, 赵川 (Acta Ecologica Sinica, 2014)

Anatomical, physiological and transcriptional responses of two contrasting poplar genotypes to drought and re‐watering - Cao, Xu; Jia, Jingbo; Zhang, Chao; Li, Hong; Liu, Tongxian; Jiang, Xiangning; Polle, Andrea; Peng, Changhui; Luo, Zhi‐Bin (Physiologia Plantarum, 2014)
Populus × euramericana (Pe) displays higher stable carbon isotope composition ( δ 13 C ) and intrinsic water use efficiency ( WUE i ) than Populus cathayana (Pc) under unlimited water conditions, rendering us to hypothesize that Pe is better acclimated to water deficiency than Pc. To examine this hypothesis, saplings of Pc and Pe were exposed to drought and subsequently re‐watered. Pc and Pe exhibited distinct anatomical, physiological and transcriptional responses in acclimation to drought and re‐watering, mainly due to stronger responsiveness of transcriptional regulation of genes encoding plasma membrane intrinsic proteins ( PIPs ), higher starch accumulation, δ 13 C , stable nitrogen isotope composition ( δ 15 N ) and WUE i , and lower reactive oxygen species ( ROS ) accumulation and scavenging in Pe. In acclimation to drought, both poplar genotypes demonstrated altered anatomical properties, declined height growth, differential expression of PIP s, activation of ABA signaling pathway, decreased total soluble sugars and starch, increased δ 13 C, δ 15 N and WUE i , and shifted homeostasis of ROS production and scavenging, and these changes can be recovered upon re‐watering. These data indicate that Pe is more tolerant to drought than Pc, and that anatomical, physiological and transcriptional acclimation to drought and re‐watering is essential for poplars to survive and grow under projected dry climate scenarios in the future.

Admixture of alder (Alnus formosana) litter can improve the decomposition of eucalyptus (Eucalyptus grandis) litter - Wu, Fuzhong; Peng, Changhui; Yang, Wanqin; Zhang, Jian; Han, Yu; Mao, Tao (Soil Biology and Biochemistry, 2014)

Insect‐induced tree mortality of boreal forests in eastern Canada under a changing climate - Zhang, Xiongqing; Lei, Yuancai; Ma, Zhihai; Kneeshaw, Dan; Peng, Changhui (Ecology and Evolution, 2014)
Abstract Forest insects are major disturbances that induce tree mortality in eastern coniferous (or fir‐spruce) forests in eastern North America. The spruce budworm ( SBW ) ( Choristoneura fumiferana [Clemens]) is the most devastating insect causing tree mortality. However, the relative importance of insect‐caused mortality versus tree mortality caused by other agents and how this relationship will change with climate change is not known. Based on permanent sample plots across eastern Canada, we combined a logistic model with a negative model to estimate tree mortality. The results showed that tree mortality increased mainly due to forest insects. The mean difference in annual tree mortality between plots disturbed by insects and those without insect disturbance was 0.0680 per year ( P < 0.0001, T ‐test), and the carbon sink loss was about 2.87t C ha −1 year −1 larger than in natural forests. We also found that annual tree mortality increased significantly with the annual climate moisture index ( CMI ) and decreased significantly with annual minimum temperature ( T min ), annual mean temperature ( T mean ) and the number of degree days below 0°C ( DD 0), which was inconsistent with previous studies (Adams et al. ; van Mantgem et al. ; Allen et al. ). Furthermore, the results for the trends in the magnitude of forest insect outbreaks were consistent with those of climate factors for annual tree mortality. Our results demonstrate that forest insects are the dominant cause of the tree mortality in eastern Canada but that tree mortality induced by insect outbreaks will decrease in eastern Canada under warming climate.

Enabling Conditions for Successful Greening of Public Spaces: The Case of Touroua, Cameroon Based on Perceptions - Epule, Epule Terence; Peng, Changhui; Lepage, Laurent; Chen, Zhi (Small-scale Forestry, 2014)

Integrating global socio-economic influences into a regional land use change model for China - Xu, Xia; Gao, Qiong; Peng, Changhui; Cui, Xuefeng; Liu, Yinghui; Jiang, Li (Frontiers of Earth Science, 2014)

Analysis of vegetation dynamics and climatic variability impacts on greenness across Canada using remotely sensed data from 2000 to 2009 - Fang, Xiuqin; Zhu, Qiuan; Chen, Huai; Ma, Zhihai; Wang, Weifeng; Song, Xinzhang; Zhao, Pengxiang; Peng, Changhui (Journal of Applied Remote Sensing, 2014)

Nitrous oxide fluxes from three forest types of the tropical mountain rainforests on Hainan Island, China - Bai, Zhenzhi; Yang, Gang; Chen, Huai; Zhu, Qiuan; Chen, Dexiang; Li, Yide; Wang, Xu; Wu, Zhongmin; Zhou, Guangyi; Peng, Changhui (Atmospheric Environment, 2014)

Elevation‐induced climate change as a dominant factor causing the late Miocene C_4 plant expansion in the Himalayan foreland - Wu, Haibin; Guo, Zhengtang; Guiot, Joël; Hatté, Christine; Peng, Changhui; Yu, Yanyan; Ge, Junyi; Li, Qin; Sun, Aizhi; Zhao, Deai (Global Change Biology, 2014)
Abstract During the late Miocene, a dramatic global expansion of C 4 plant distribution occurred with broad spatial and temporal variations. Although the event is well documented, whether subsequent expansions were caused by a decreased atmospheric CO 2 concentration or climate change is a contentious issue. In this study, we used an improved inverse vegetation modeling approach that accounts for the physiological responses of C 3 and C 4 plants to quantitatively reconstruct the paleoclimate in the Siwalik of Nepal based on pollen and carbon isotope data. We also studied the sensitivity of the C 3 and C 4 plants to changes in the climate and the atmospheric CO 2 concentration. We suggest that the expansion of the C 4 plant distribution during the late Miocene may have been primarily triggered by regional aridification and temperature increases. The expansion was unlikely caused by reduced CO 2 levels alone. Our findings suggest that this abrupt ecological shift mainly resulted from climate changes related to the decreased elevation of the Himalayan foreland.

Carbon accumulation and sequestration of lakes in China during the Holocene - Wang, Mei; Chen, Huai; Yu, Zicheng; Wu, Jianghua; Zhu, Qiu'an; Peng, Changhui; Wang, Yanfen; Qin, Boqiang (Global Change Biology, 2015)
Abstract Understanding the responses of lake systems to past climate change and human activity is critical for assessing and predicting the fate of lake carbon (C) in the future. In this study, we synthesized records of the sediment accumulation from 82 lakes and of C sequestration from 58 lakes with direct organic C measurements throughout China. We also identified the controlling factors of the long‐term sediment and C accumulation dynamics in these lakes during the past 12 ka (1 ka = 1000 cal yr BP ). Our results indicated an overall increasing trend of sediment and C accumulation since 12 ka, with an accumulation peak in the last couple of millennia for lakes in China, corresponding to terrestrial organic matter input due to land‐use change. The Holocene lake sediment accumulation rate ( SAR ) and C accumulation rate ( CAR ) averaged (mean ± SE ) 0.47 ± 0.05 mm yr −1 and 7.7 ± 1.4 g C m −2 yr −1 in China, respectively, comparable to the previous estimates for boreal and temperate regions. The SAR for lakes in the East Plain of subtropical China (1.05 ± 0.28 mm yr −1 ) was higher than those in other regions ( P < 0.05). However, CAR did not vary significantly among regions. Overall, the variability and history of climate and anthropogenic interference regulated the temporal and spatial dynamics of sediment and C sequestration for lakes in China. We estimated the total amount of C burial in lakes of China as 8.0 ± 1.0 Pg C. This first estimation of total C storage and dynamics in lakes of China confirms the importance of lakes in land C budget in monsoon‐influenced regions.

Application of the ecosystem model and Markov Chain Monte Carlo for parameter estimation and productivity prediction - Li, Weizhong; Peng, Changhui; Zhou, Xiaolu; Sun, Jianfeng; Zhu, Qiuan; Wu, Haibin; St-Onge, Benoit (Ecosphere, 2015)
It is increasingly being recognized that global ecological research requires novel methods and strategies in which to combine process‐based ecological models and data in cohesive, systematic ways. In process‐based model applications, inherent spatial and temporal heterogeneities found within terrestrial ecosystems may lead to the uncertainties of model predictions. To reduce simulation uncertainties due to inaccurate model parameters, the Markov Chain Monte Carlo (MCMC) method was applied in this study to improve the estimations of four key parameters used in the process‐based ecosystem model of TRIPLEX‐FLUX. These four key parameters include a maximum photosynthetic carboxylation rate of 25°C (Vmax), an electron transport (Jmax) light‐saturated rate within the photosynthetic carbon reduction cycle of leaves, a coefficient of stomatal conductance (m), and a reference respiration rate of 10°C (R10). Seven forest flux tower sites located across North America were used to investigate and facilitate understanding of the daily variation in model parameters for three deciduous forests, three evergreen temperate forests, and one evergreen boreal forest. Eddy covariance CO 2 exchange measurements were assimilated to optimize the parameters in the year 2006. After parameter optimization and adjustment took place, net ecosystem production prediction significantly improved (by approximately 25%) compared to the CO 2 flux measurements taken at the seven forest ecosystem sites. Results suggest that greater seasonal variability occurs in broadleaf forests in respect to the selected parameters than in needleleaf forests. This study also demonstrated that the model‐data fusion approach by incorporating MCMC method is able to better estimate parameters and improve simulation accuracy for different ecosystems located across North America.

Phosphorus and nitrogen physiology of two contrasting poplar genotypes when exposed to phosphorus and/or nitrogen starvation - Gan, Honghao; Jiao, Yu; Jia, Jingbo; Wang, Xinli; Li, Hong; Shi, Wenguang; Peng, Changhui; Polle, Andrea; Luo, Zhi-Bin (Tree Physiology, 2016)

Monitoring the impact of aerosol contamination on the drought-induced decline of gross primary productivity - Zhang, Yao; Li, Weizhong; Zhu, Qiuan; Chen, Huai; Fang, Xiuqin; Zhang, Tinglong; Zhao, Pengxiang; Peng, Changhui (International Journal of Applied Earth Observation and Geoinformation, 2015)

From plant functional types to plant functional traits: A new paradigm in modelling global vegetation dynamics - Yang, Yanzheng; Zhu, Qiuan; Peng, Changhui; Wang, Han; Chen, Huai (Progress in Physical Geography: Earth and Environment, 2015)
Dynamic global vegetation models (DGVMs) typically track the material and energy cycles in ecosystems with finite plant functional types (PFTs). Increasingly, the community ecology and modelling studies recognize that current PFT scheme is not sufficient for simulating ecological processes. Recent advances in the study of plant functional traits (FTs) in community ecology provide a novel and feasible approach for the improvement of PFT-based DGVMs. This paper reviews the development of current DGVMs over recent decades. After characterizing the advantages and disadvantages of the PFT-based scheme, it summarizes trait-based theories and discusses the possibility of incorporating FTs into DGVMs. More importantly, this paper summarizes three strategies for constructing next-generation DGVMs with FTs. Finally, the method’s limitations, current challenges and future research directions for FT theory are discussed for FT theory. We strongly recommend the inclusion of several FTs, namely specific leaf area (SLA), leaf nitrogen content (LNC), carbon isotope composition of leaves (Leaf δ 13 C), the ratio between leaf-internal and ambient mole fractions of CO 2 (Leaf C i /C a ), seed mass and plant height. These are identified as the most important in constructing DGVMs based on FTs, which are also recognized as important ecological strategies for plants. The integration of FTs into dynamic vegetation models is a critical step towards improving the results of DGVM simulations; communication and cooperation among ecologists and modellers is equally important for the development of the next generation of DGVMs.

A novel pathway of direct methane production and emission by eukaryotes including plants, animals and fungi: An overview - Liu, Jiangong; Chen, Huai; Zhu, Qiuan; Shen, Yan; Wang, Xue; Wang, Meng; Peng, Changhui (Atmospheric Environment, 2015)

Estimating global natural wetland methane emissions using process modelling: spatio‐temporal patterns and contributions to atmospheric methane fluctuations - Zhu, Qiuan; Peng, Changhui; Chen, Huai; Fang, Xiuqin; Liu, Jinxun; Jiang, Hong; Yang, Yanzheng; Yang, Gang (Global Ecology and Biogeography, 2015)
Abstract Aim The fluctuations of atmospheric methane ( CH 4 ) that have occurred in recent decades are not fully understood, particularly with regard to the contribution from wetlands. The application of spatially explicit parameters has been suggested as an effective method for reducing uncertainties in bottom‐up approaches to wetland CH 4 emissions, but has not been included in recent studies. Our goal was to estimate spatio‐temporal patterns of global wetland CH 4 emissions using a process model and then to identify the contribution of wetland emissions to atmospheric CH 4 fluctuations. Location Global. Methods A process‐based model integrated with full descriptions of methanogenesis ( TRIPLEX‐GHG ) was used to simulate global wetland CH 4 emissions. Results Global annual wetland CH 4 emissions ranged from 209 to 245 T g CH 4 year −1 between 1901 and 2012, with peaks occurring in 1991 and 2012. There is a decreasing trend between 1990 and 2010 with a rate of approximately 0.48 T g CH 4 year −1 , which was largely caused by emissions from tropical wetlands showing a decreasing trend of 0.44 T g CH 4 year −1 since the 1970s. Emissions from tropical, temperate and high‐latitude wetlands comprised 59, 26 and 15% of global emissions, respectively. Main conclusion Global wetland CH 4 emissions, the interannual variability of which was primary controlled by tropical wetlands, partially drive the atmospheric CH 4 burden. The stable to decreasing trend in wetland CH 4 emissions, a result of a balance of emissions from tropical and extratropical wetlands, was a particular factor in slowing the atmospheric CH 4 growth rate during the 1990s. The rapid decrease in tropical wetland CH 4 emissions that began in 2000 was supposed to offset the increase in anthropogenic emissions and resulted in a relatively stable level of atmospheric CH 4 from 2000 to 2006. Increasing wetland CH 4 emissions, particularly after 2010, should be an important contributor to the growth in atmospheric CH 4 seen since 2007.

Development and Evaluation of Models for the Relationship between Tree Height and Diameter at Breast Height for Chinese-Fir Plantations in Subtropical China - Li, Yan-qiong; Deng, Xiang-wen; Huang, Zhi-hong; Xiang, Wen-hua; Yan, Wen-de; Lei, Pi-feng; Zhou, Xiao-lu; Peng, Chang-hui (PLOS ONE, 2015)

Agricultural carbon flux changes driven by intensive plastic greenhouse cultivation in five climatic regions of China - Wu, Xu; Ge, Ying; Wang, Yan; Liu, Dong; Gu, Baojing; Ren, Yuan; Yang, Guofu; Peng, Changhui; Cheng, Jihua; Chang, Jie (Journal of Cleaner Production, 2015)

Effects of Topographic and Soil Factors on Woody Species Assembly in a Chinese Subtropical Evergreen Broadleaved Forest - Zhao, Lijuan; Xiang, Wenhua; Li, Jiaxiang; Lei, Pifeng; Deng, Xiangwen; Fang, Xi; Peng, Changhui (Forests, 2015)
Evergreen broadleaved forests in subtropical China contain a complicated structure of diverse species. The impact of topographic and soil factors on the assembly of woody species in the forest has been poorly understood. We used Ripley’s K(t) function to analyze the spatial patterns and associations of dominant species and residual analysis (RDA) to quantify the contribution of topography and soil to species assembly. The 1 ha plot investigated had 4797 stems with a diameter at breast height (dbh) larger than 1 cm that belong to 73 species, 55 genera, and 38 families. All stems of the entire forest and four late successional species exhibited a reversed J shape for dbh distribution, while two early successional species showed a unimodal shape. Aggregation was the major spatial pattern for entire forests and dominant species across vertical layers. Spatial associations between inter- and intra-species were mostly independent. Topographic and soil factors explained 28.1% of species assembly. The forest was close to late succession and showed the characteristics of diverse woody species, high regeneration capacity, and aggregated spatial patterns. Topographic and soil factors affected species assembly, but together they could only explain a small part of total variance.

Nitrous oxide emission from infralittoral zone and pelagic zone in a shallow lake: Implications for whole lake flux estimation and lake restoration - Zhu, Dan; Wu, Yan; Wu, Ning; Chen, Huai; He, Yixin; Zhang, Yongmei; Peng, Changhui; Zhu, Qiu'an (Ecological Engineering, 2015)

Higher recent peat C accumulation than that during the Holocene on the Zoige Plateau - Wang, Mei; Yang, Gang; Gao, Yongheng; Chen, Huai; Wu, Ning; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; Wu, Jianghua; He, Yixin; Tian, Jianqing; Zhao, Xinquan; et al. (Quaternary Science Reviews, 2015)

Using ecosystem service bundles to detect trade-offs and synergies across urban–rural complexes - Yang, Guofu; Ge, Ying; Xue, Hui; Yang, Wu; Shi, Yan; Peng, Changhui; Du, Yuanyuan; Fan, Xing; Ren, Yuan; Chang, Jie (Landscape and Urban Planning, 2015)

Temperature sensitivity of soil carbon dioxide and nitrous oxide emissions in mountain forest and meadow ecosystems in China - Zhang, Junjun; Peng, Changhui; Zhu, Qiuan; Xue, Wei; Shen, Yan; Yang, Yanzheng; Shi, Guohua; Shi, Shengwei; Wang, Meng (Atmospheric Environment, 2016)

A global meta-analysis of changes in soil carbon, nitrogen, phosphorus and sulfur, and stoichiometric shifts after forestation - Shi, Shengwei; Peng, Changhui; Wang, Meng; Zhu, Qiuan; Yang, Gang; Yang, Yanzheng; Xi, Tingting; Zhang, Tinglong (Plant and Soil, 2016)

Degradation of lignin and cellulose during foliar litter decomposition in an alpine forest river - Yue, Kai; Peng, Changhui; Yang, Wanqin; Peng, Yan; Zhang, Chuan; Huang, Chunping; Wu, Fuzhong (Ecosphere, 2016)
Abstract Lignin and cellulose are thought to be critical factors that affect the rate of litter decomposition; however, few data are available on their degradation dynamics during litter decomposition in lotic ecosystems, such as forest rivers, where litter can decompose much more rapidly than in terrestrial ecosystems. We studied the degradation of lignin and cellulose in the foliar litter of four dominant riparian species (willow: Salix paraplesia ; azalea: Rhododendron lapponicum ; cypress: Sabina saltuaria ; and larch: Larix mastersiana ) in an alpine forest river. Over an entire year's incubation, litter lignin and cellulose degraded by 14.7–100% and 57.7–100% of their initial masses, respectively, depending on litter species. Strong degradations of lignin and cellulose occurred in the prefreezing period (i.e., the first 41 d) during litter decomposition, and the degradation rate was the highest among all the decomposition periods regardless of litter species. Litter species, decomposition period, and environmental factors such as temperature and nutrient availability showed significant influences on lignin and cellulose degradation rates. Compared with previously reported data regarding the dynamics of lignin and cellulose during litter decomposition in terrestrial ecosystems, our results suggest that lignin and cellulose can be degraded much more rapidly in lotic ecosystems, indicating that the traditionally used two‐phased model for the dynamics of lignin in decomposing litter may not be suitable in lotic ecosystems.

The Spatial and Temporal Distribution of Dissolved Organic Carbon Exported from Three Chinese Rivers to the China Sea - Shi, Guohua; Peng, Changhui; Wang, Meng; Shi, Shengwei; Yang, Yanzheng; Chu, Junyao; Zhang, Junjun; Lin, Guanghui; Shen, Yan; Zhu, Qiuan (PLOS ONE, 2016)

Soil properties and species composition under different grazing intensity in an alpine meadow on the eastern Tibetan Plateau, China - Yang, Zhen’an; Xiong, Wan; Xu, Yingyi; Jiang, Lin; Zhu, Erxiong; Zhan, Wei; He, Yixin; Zhu, Dan; Zhu, Qiuan; Peng, Changhui; Chen, Huai (Environmental Monitoring and Assessment, 2016)

Climate-driven increase of natural wetland methane emissions offset by human-induced wetland reduction in China over the past three decades - Zhu, Qiuan; Peng, Changhui; Liu, Jinxun; Jiang, Hong; Fang, Xiuqin; Chen, Huai; Niu, Zhenguo; Gong, Peng; Lin, Guanghui; Wang, Meng; Wang, Han; Yang, Yanzheng; et al. (Scientific Reports, 2016)
Abstract Both anthropogenic activities and climate change can affect the biogeochemical processes of natural wetland methanogenesis. Quantifying possible impacts of changing climate and wetland area on wetland methane (CH 4 ) emissions in China is important for improving our knowledge on CH 4 budgets locally and globally. However, their respective and combined effects are uncertain. We incorporated changes in wetland area derived from remote sensing into a dynamic CH 4 model to quantify the human and climate change induced contributions to natural wetland CH 4 emissions in China over the past three decades. Here we found that human-induced wetland loss contributed 34.3% to the CH 4 emissions reduction (0.92 TgCH 4 ), and climate change contributed 20.4% to the CH 4 emissions increase (0.31 TgCH 4 ), suggesting that decreasing CH 4 emissions due to human-induced wetland reductions has offset the increasing climate-driven CH 4 emissions. With climate change only, temperature was a dominant controlling factor for wetland CH 4 emissions in the northeast (high latitude) and Qinghai-Tibet Plateau (high altitude) regions, whereas precipitation had a considerable influence in relative arid north China. The inevitable uncertainties caused by the asynchronous for different regions or periods due to inter-annual or seasonal variations among remote sensing images should be considered in the wetland CH 4 emissions estimation.

Simulated effects of nitrogen saturation on the global carbon budget using the IBIS model - Lu, Xuehe; Jiang, Hong; Liu, Jinxun; Zhang, Xiuying; Jin, Jiaxin; Zhu, Qiuan; Zhang, Zhen; Peng, Changhui (Scientific Reports, 2016)
Abstract Over the past 100 years, human activity has greatly changed the rate of atmospheric N (nitrogen) deposition in terrestrial ecosystems, resulting in N saturation in some regions of the world. The contribution of N saturation to the global carbon budget remains uncertain due to the complicated nature of C-N (carbon-nitrogen) interactions and diverse geography. Although N deposition is included in most terrestrial ecosystem models, the effect of N saturation is frequently overlooked. In this study, the IBIS (Integrated BIosphere Simulator) was used to simulate the global-scale effects of N saturation during the period 1961–2009. The results of this model indicate that N saturation reduced global NPP (Net Primary Productivity) and NEP (Net Ecosystem Productivity) by 0.26 and 0.03 Pg C yr −1 , respectively. The negative effects of N saturation on carbon sequestration occurred primarily in temperate forests and grasslands. In response to elevated CO 2 levels, global N turnover slowed due to increased biomass growth, resulting in a decline in soil mineral N. These changes in N cycling reduced the impact of N saturation on the global carbon budget. However, elevated N deposition in certain regions may further alter N saturation and C-N coupling.

Stimulation of terrestrial ecosystem carbon storage by nitrogen addition: a meta-analysis - Yue, Kai; Peng, Yan; Peng, Changhui; Yang, Wanqin; Peng, Xin; Wu, Fuzhong (Scientific Reports, 2016)
Abstract Elevated nitrogen (N) deposition alters the terrestrial carbon (C) cycle, which is likely to feed back to further climate change. However, how the overall terrestrial ecosystem C pools and fluxes respond to N addition remains unclear. By synthesizing data from multiple terrestrial ecosystems, we quantified the response of C pools and fluxes to experimental N addition using a comprehensive meta-analysis method. Our results showed that N addition significantly stimulated soil total C storage by 5.82% ([2.47%, 9.27%], 95% CI, the same below) and increased the C contents of the above- and below-ground parts of plants by 25.65% [11.07%, 42.12%] and 15.93% [6.80%, 25.85%], respectively. Furthermore, N addition significantly increased aboveground net primary production by 52.38% [40.58%, 65.19%] and litterfall by 14.67% [9.24%, 20.38%] at a global scale. However, the C influx from the plant litter to the soil through litter decomposition and the efflux from the soil due to microbial respiration and soil respiration showed insignificant responses to N addition. Overall, our meta-analysis suggested that N addition will increase soil C storage and plant C in both above- and below-ground parts, indicating that terrestrial ecosystems might act to strengthen as a C sink under increasing N deposition.

Archaeal communities in the sediments of different mangrove stands at Dongzhaigang, China - Li, Wei; Guan, Wei; Chen, Huai; Liao, Baowen; Hu, Ji; Peng, Changhui; Rui, Junpeng; Tian, Jianqing; Zhu, Dan; He, Yixin (Journal of Soils and Sediments, 2016)

A novel approach for modelling vegetation distributions and analysing vegetation sensitivity through trait-climate relationships in China - Yang, Yanzheng; Zhu, Qiuan; Peng, Changhui; Wang, Han; Xue, Wei; Lin, Guanghui; Wen, Zhongming; Chang, Jie; Wang, Meng; Liu, Guobin; Li, Shiqing (Scientific Reports, 2016)
Abstract Increasing evidence indicates that current dynamic global vegetation models (DGVMs) have suffered from insufficient realism and are difficult to improve, particularly because they are built on plant functional type (PFT) schemes. Therefore, new approaches, such as plant trait-based methods, are urgently needed to replace PFT schemes when predicting the distribution of vegetation and investigating vegetation sensitivity. As an important direction towards constructing next-generation DGVMs based on plant functional traits, we propose a novel approach for modelling vegetation distributions and analysing vegetation sensitivity through trait-climate relationships in China. The results demonstrated that a Gaussian mixture model (GMM) trained with a LMA-N mass -LAI data combination yielded an accuracy of 72.82% in simulating vegetation distribution, providing more detailed parameter information regarding community structures and ecosystem functions. The new approach also performed well in analyses of vegetation sensitivity to different climatic scenarios. Although the trait-climate relationship is not the only candidate useful for predicting vegetation distributions and analysing climatic sensitivity, it sheds new light on the development of next-generation trait-based DGVMs.

Evaluating the carbon budget pattern of Chinese terrestrial ecosystem from 1960 to 2006 using Integrated Biosphere Simulator - Yang Yanzheng, 杨延征; Ma Yuandan, 马元丹; Jiang Hong, 江洪; Zhu Qiu'an, 朱求安; Liu Jinxun, 刘金勋; Peng Changhui, 彭长辉 (Acta Ecologica Sinica, 2016)

Integrating a model with remote sensing observations by a data assimilation approach to improve the model simulation accuracy of carbon flux and evapotranspiration at two flux sites - Zhang, TingLong; Sun, Rui; Peng, ChangHui; Zhou, GuoYi; Wang, ChunLing; Zhu, QiuAn; Yang, YanZheng (Science China Earth Sciences, 2016)

Simulating carbon dioxide exchange in boreal ecosystems flooded by reservoirs - Kim, Youngil; Roulet, Nigel T.; Li, Changsheng; Frolking, Steve; Strachan, Ian B.; Peng, Changhui; Teodoru, Cristian R.; Prairie, Yves T.; Tremblay, Alain (Ecological Modelling, 2016)

Significant effects of biodiversity on forest biomass during the succession of subtropical forest in south China - Ouyang, Shuai; Xiang, Wenhua; Wang, Xiangping; Zeng, Yelin; Lei, Pifeng; Deng, Xiangwen; Peng, Changhui (Forest Ecology and Management, 2016)

Foliar litter decomposition in an alpine forest meta-ecosystem on the eastern Tibetan Plateau - Yue, Kai; Yang, Wanqin; Peng, Changhui; Peng, Yan; Zhang, Chuan; Huang, Chunping; Tan, Yu; Wu, Fuzhong (Science of The Total Environment, 2016)

Soil Carbon Dioxide Fluxes from Three Forest Types of the Tropical Montane Rainforest on Hainan Island, China - Jiang, Xinhua; Chen, Huai; Peng, Changhui; Li, Yide; He, Yixin; Chen, Dexiang; Lin, Mingxian; Hu, Ji; Ma, Tianli; Liu, Liangfeng; Liu, Xinwei; Xia, Miao; et al. (Water, Air, & Soil Pollution, 2016)

Uncertainty analysis of terrestrial net primary productivity and net biome productivity in China during 1901–2005 - Shao, Junjiong; Zhou, Xuhui; Luo, Yiqi; Zhang, Guodong; Yan, Wei; Li, Jiaxuan; Li, Bo; Dan, Li; Fisher, Joshua B.; Gao, Zhiqiang; He, Yong; Huntzinger, Deborah; et al. (Journal of Geophysical Research: Biogeosciences, 2016)
Abstract Despite the importance of net primary productivity (NPP) and net biome productivity (NBP), estimates of NPP and NBP for China are highly uncertain. To investigate the main sources of uncertainty, we synthesized model estimates of NPP and NBP for China from published literature and the Multi‐scale Synthesis and Terrestrial Model Intercomparison Project (MsTMIP). The literature‐based results showed that total NPP and NBP in China were 3.35 ± 1.25 and 0.14 ± 0.094 Pg C yr −1 , respectively. Classification and regression tree analysis based on literature data showed that model type was the primary source of the uncertainty, explaining 36% and 64% of the variance in NPP and NBP, respectively. Spatiotemporal scales, land cover conditions, inclusion of the N cycle, and effects of N addition also contributed to the overall uncertainty. Results based on the MsTMIP data suggested that model structures were overwhelmingly important (>90%) for the overall uncertainty compared to simulations with different combinations of time‐varying global change factors. The interannual pattern of NPP was similar among diverse studies and increased by 0.012 Pg C yr −1 during 1981–2000. In addition, high uncertainty in China's NPP occurred in areas with high productivity, whereas NBP showed the opposite pattern. Our results suggest that to significantly reduce uncertainty in estimated NPP and NBP, model structures should be substantially tested on the basis of empirical results. To this end, coordinated distributed experiments with multiple global change factors might be a practical approach that can validate specific structures of different models. , Key Points Large uncertainty exists in estimates of terrestrial NPP and NBP in China Methodological differences greatly contribute to the uncertainty in NPP and NBP Uncertainty in the interannual pattern of NBP is greater than that of NPP

Spatial and seasonal variations of leaf area index (LAI) in subtropicalsecondary forests related to floristic composition and stand characters - Zhu, Wenjuan; Xiang, Wenhua; Pan, Qiong; Zeng, Yelin; Ouyang, Shuai; Lei, Pifeng; Deng, Xiangwen; Fang, Xi; Peng, Changhui (Biogeosciences, 2016)
Abstract. Leaf area index (LAI) is an important parameter related to carbon, water, and energy exchange between canopy and atmosphere and is widely applied in process models that simulate production and hydrological cycles in forest ecosystems. However, fine-scale spatial heterogeneity of LAI and its controlling factors have yet to be fully understood in Chinese subtropical forests. We used hemispherical photography to measure LAI values in three subtropical forests (Pinus massoniana–Lithocarpus glaber coniferous and evergreen broadleaved mixed forests, Choerospondias axillaris deciduous broadleaved forests, and L. glaber–Cyclobalanopsis glauca evergreen broadleaved forests) from April 2014 to January 2015. Spatial heterogeneity of LAI and its controlling factors were analysed using geostatistical methods and the generalised additive models (GAMs) respectively. Our results showed that LAI values differed greatly in the three forests and their seasonal variations were consistent with plant phenology. LAI values exhibited strong spatial autocorrelation for the three forests measured in January and for the L. glaber–C. glauca forest in April, July, and October. Obvious patch distribution pattern of LAI values occurred in three forests during the non-growing period and this pattern gradually dwindled in the growing season. Stem number, crown coverage, proportion of evergreen conifer species on basal area basis, proportion of deciduous species on basal area basis, and forest types affected the spatial variations in LAI values in January, while stem number and proportion of deciduous species on basal area basis affected the spatial variations in LAI values in July. Floristic composition, spatial heterogeneity, and seasonal variations should be considered for sampling strategy in indirect LAI measurement and application of LAI to simulate functional processes in subtropical forests.

Dynamic allocation and transfer of non-structural carbohydrates, a possible mechanism for the explosive growth of Moso bamboo (Phyllostachys heterocycla) - Song, Xinzhang; Peng, Changhui; Zhou, Guomo; Gu, Honghao; Li, Quan; Zhang, Chao (Scientific Reports, 2016)
Abstract Moso bamboo can rapidly complete its growth in both height and diameter within only 35–40 days after shoot emergence. However, the underlying mechanism for this “explosive growth” remains poorly understood. We investigated the dynamics of non-structural carbohydrates (NSCs) in shoots and attached mature bamboos over a 20-month period. The results showed that Moso bamboos rapidly completed their height and diameter growth within 38 days. At the same time, attached mature bamboos transferred almost all the NSCs of their leaves, branches and especially trunks and rhizomes to the “explosively growing” shoots via underground rhizomes for the structural growth and metabolism of shoots. Approximately 4 months after shoot emergence, this transfer stopped when the leaves of the young bamboos could independently provide enough photoassimilates to meet the carbon demands of the young bamboos. During this period, the NSC content of the leaves, branches, trunks and rhizomes of mature bamboos declined by 1.5, 23, 28 and 5 fold, respectively. The trunk contributed the most NSCs to the shoots. Our findings provide new insight and a possible rational mechanism explaining the “explosive growth” of Moso bamboo and shed new light on understanding the role of NSCs in the rapid growth of Moso bamboo.

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation - Zhu, Qiuan; Peng, Changhui; Ciais, Philippe; Jiang, Hong; Liu, Jinxun; Bousquet, Philippe; Li, Shiqin; Chang, Jie; Fang, Xiuqin; Zhou, Xiaolu; Chen, Huai; Liu, Shirong; et al. (Global Change Biology, 2017)
Abstract Methane (CH 4 ) emissions from tropical wetlands contribute 60%–80% of global natural wetland CH 4 emissions. Decreased wetland CH 4 emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño–Southern Oscillation (ENSO) on CH 4 emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models’ projections. We use a process‐based model of global wetland CH 4 emissions to investigate the impacts of the ENSO on CH 4 emissions in tropical wetlands for the period from 1950 to 2012. The results show that CH 4 emissions from tropical wetlands respond strongly to repeated ENSO events, with negative anomalies occurring during El Niño periods and with positive anomalies occurring during La Niña periods. An approximately 8‐month time lag was detected between tropical wetland CH 4 emissions and ENSO events, which was caused by the combined time lag effects of ENSO events on precipitation and temperature over tropical wetlands. The ENSO can explain 49% of interannual variations for tropical wetland CH 4 emissions. Furthermore, relative to neutral years, changes in temperature have much stronger effects on tropical wetland CH 4 emissions than the changes in precipitation during ENSO periods. The occurrence of several El Niño events contributed to a lower decadal mean growth rate in atmospheric CH 4 concentrations throughout the 1980s and 1990s and to stable atmospheric CH 4 concentrations from 1999 to 2006, resulting in negative feedback to global warming.

Modeling Global Soil Carbon and Soil Microbial Carbon by Integrating Microbial Processes into the Ecosystem Process Model TRIPLEX‐GHG - Wang, Kefeng; Peng, Changhui; Zhu, Qiuan; Zhou, Xiaolu; Wang, Meng; Zhang, Kerou; Wang, Gangsheng (Journal of Advances in Modeling Earth Systems, 2017)
Abstract Microbial physiology plays a critical role in the biogeochemical cycles of the Earth system. However, most traditional soil carbon models are lacking in terms of the representation of key microbial processes that control the soil carbon response to global climate change. In this study, the improved process‐based model TRIPLEX‐GHG was developed by coupling it with the new MEND (Microbial‐ENzyme‐mediated Decomposition) model to estimate total global soil organic carbon (SOC) and global soil microbial carbon. The new model (TRIPLEX‐MICROBE) shows considerable improvement over the previous version (TRIPLEX‐GHG) in simulating SOC. We estimated the global soil carbon stock to be approximately 1195 Pg C, with 348 Pg C located in the high northern latitudes, which is in good agreement with the well‐regarded Harmonized World Soil Database (HWSD) and the Northern Circumpolar Soil Carbon Database (NCSCD). We also estimated the global soil microbial carbon to be 21 Pg C, similar to the 23 Pg C estimated by Xu et al. (2014). We found that the microbial carbon quantity in the latitudinal direction showed reversions at approximately 30°N, near the equator and at 25°S. A sensitivity analysis suggested that the tundra ecosystem exhibited the highest sensitivity to a 1°C increase or decrease in temperature in terms of dissolved organic carbon (DOC), microbial biomass carbon (MBC), and mineral‐associated organic carbon (MOC). However, our work represents the first step toward a new generation of ecosystem process models capable of integrating key microbial processes into soil carbon cycles. , Key Points Traditional soil carbon models are lacking in their representation of key microbial processes that control the soil carbon response to global climate change A Ecosystem model (TRIPLEX‐MICROBE) offers considerable improvement over a previous version (TRIPLEX‐GHG) in simulating soil organic carbon Our work is the first step toward a new generation of ecosystem process models that integrate key microbial processes into soil carbon cycles

Past and future carbon sequestration benefits of China’s grain for green program - Deng, Lei; Liu, Shuguang; Kim, Dong Gill; Peng, Changhui; Sweeney, Sandra; Shangguan, Zhouping (Global Environmental Change, 2017)

Spatial variations in soil organic carbon, nitrogen and phosphorus concentrations related to stand characteristics in subtropical areas - Jiang, Fang; Wu, Xiaohong; Xiang, Wenhua; Fang, Xi; Zeng, Yeling; Ouyang, Shuai; Lei, Pifeng; Deng, Xiangwen; Peng, Changhui (Plant and Soil, 2017)

Spatial patterns of leaf δ^13 C and its relationship with plant functional groups and environmental factors in China: Factors Dominate Plant Traits - Li, Mingxu; Peng, Changhui; Wang, Meng; Yang, Yanzheng; Zhang, Kerou; Li, Peng; Yang, Yan; Ni, Jian; Zhu, Qiuan (Journal of Geophysical Research: Biogeosciences, 2017)

Model prediction of biome‐specific global soil respiration from 1960 to 2012 - Zhao, Zhengyong; Peng, Changhui; Yang, Qi; Meng, Fan‐Rui; Song, Xinzhang; Chen, Shutao; Epule, Terence Epule; Li, Peng; Zhu, Qiuan (Earth's Future, 2017)
Abstract Biome‐specific soil respiration (Rs) has important yet different roles in both the carbon cycle and climate change from regional to global scales. To date, no comparable studies related to global biome‐specific Rs have been conducted applying comprehensive global Rs databases. The goal of this study was to develop artificial neural network ( ANN ) models capable of spatially estimating global Rs and to evaluate the effects of interannual climate variations on 10 major biomes. We used 1976 annual Rs field records extracted from global Rs literature to train and test the ANN models. We determined that the best ANN model for predicting biome‐specific global annual Rs was the one that applied mean annual temperature ( MAT ), mean annual precipitation ( MAP ), and biome type as inputs ( r 2 = 0.60). The ANN models reported an average global Rs of 93.3 ± 6.1 Pg C yr −1 from 1960 to 2012 and an increasing trend in average global annual Rs of 0.04 Pg C yr −1 . Estimated annual Rs increased with increases in MAT and MAP in cropland, boreal forest, grassland, shrubland, and wetland biomes. Additionally, estimated annual Rs decreased with increases in MAT and increased with increases in MAP in desert and tundra biomes, and only significantly decreased with increases in MAT ( r 2 = 0.87) in the savannah biome. The developed biome‐specific global Rs database for global land and soil carbon models will aid in understanding the mechanisms underlying variations in soil carbon dynamics and in quantifying uncertainty in the global soil carbon cycle. , Key Points Predict biome‐specific global soil respiration from 1960 to 2012 using an artificial neural network model Prediction determined an average global soil respiration of 93.3 ± 6.1 Pg C yr −1 and an increasing trend of 0.04 Pg C yr −1 The 10 biome‐specific soil respiration estimates made it possible to trace different responses to global climate change in each biome

The carbon flux of global rivers: A re-evaluation of amount and spatial patterns - Li, Mingxu; Peng, Changhui; Wang, Meng; Xue, Wei; Zhang, Kerou; Wang, Kefeng; Shi, Guohua; Zhu, Qiuan (Ecological Indicators, 2017)

Observed high and persistent carbon uptake by Moso bamboo forests and its response to environmental drivers - Song, Xinzhang; Chen, Xiaofeng; Zhou, Guomo; Jiang, Hong; Peng, Changhui (Agricultural and Forest Meteorology, 2017)

The NEBIE plot network: Highlights of long-term scientific studies - Bell, F. Wayne; Dacosta, Jennifer; Newmaster, Steven G.; Mallik, Azim; Hunt, Shelley; Anand, Madhur; Maloles, Jose; Peng, Changhui; Parton, John; McLaughlin, John; Winters, John; Wester, Monique; et al. (The Forestry Chronicle, 2017)
The NEBIE plot network is a stand-scale, multi-agency research project designed to compare the ecological effects of a range of silvicultural treatments in northern temperate and boreal forest regions of Ontario, Canada. While research on silviculture intensities has been previously conducted, the NEBIE plot network is at a larger scale, and covers a wider range of intensities in a variety of northern temperate and boreal forest types. Details about experimental design, treatment designs and research sites, are presented in a companion paper which is published in this edition of The Forestry Chronicle. The operational scale of treatment plots allow for assessment of a variety of forest values. We used a criteria and indicator approach to organize long-term research studies on the network sites, with the goal of providing scientific findings that would inform forest policy. Pre-treatment, and 2-, 5-, and 10-year post-harvesting data have been collected. These initial data add to existing information on the effects of intensification of silviculture on biological diversity, forest productivity, ecosystem health and vitality, soil and water resources, contribution of enhanced forest management global carbon cycles, and long-term multiple socio-economic benefits of northern forests.

Higher temperature variability reduces temperature sensitivity of vegetation growth in Northern Hemisphere - Wu, Xiuchen; Liu, Hongyan; Li, Xiaoyan; Piao, Shilong; Ciais, Philippe; Guo, Weichao; Yin, Yi; Poulter, Ben; Peng, Changhui; Viovy, Nicolas; Vuichard, Nicolas; Wang, Pei; et al. (Geophysical Research Letters, 2017)
Abstract Interannual air temperature variability has changed over some regions in Northern Hemisphere (NH), accompanying with climate warming. However, whether and to what extent it regulates the interannual sensitivity of vegetation growth to temperature variability (i.e., interannual temperature sensitivity)—one central issue in understanding and predicting the responses of vegetation growth to changing climate—still remains poorly quantified and understood. Here we quantify the relationships between the interannual temperature sensitivity of mean growing‐season (April–October) normalized difference vegetation index (NDVI) and ecosystem model simulations of gross primary productivity (GPP), and variability in mean growing‐season temperature for forest, shrub, and grass over NH. We find that higher interannual variability in mean growing‐season temperature leads to consistent decrease in interannual temperature sensitivity of mean growing‐season NDVI among all vegetation types but not in model simulations of GPP. Drier condition associates with ~130 ± 150% further decrease in interannual temperature sensitivity of mean growing‐season NDVI by temperature variability in forest and shrub. These results illustrate that varying temperature variability can significantly regulate the interannual temperature sensitivity of vegetation growth over NH, interacted with drought variability and nonlinear responses of photosynthesis to temperature. Our findings call for an improved characterization of the nonlinear effects of temperature variability on vegetation growth within global ecosystem models. , Key Points It shows consistent decrease in temperature sensitivity of vegetation growth by temperature variability for all vegetation types Larger decrease in temperature sensitivity of vegetation growth by temperature variability is found in forest and shrub in dry regions Drier condition adds further decrease in temperature sensitivity of vegetation growth by temperature variability for forest and shrub in dry regions

Effects of canopy gaps on N 2 O fluxes in a tropical montane rainforest in Hainan of China - Yang, Huai; Detto, Matteo; Liu, Shirong; Yuan, Wenping; Hsieh, Cheng-I; Wang, Xu; Chen, Renli; Chen, Huai; Peng, Changhui; Jiang, Xinhua; Li, Yide; Xu, Han; et al. (Ecological Engineering, 2017)

Quantification of methane emissions from municipal solid waste landfills in China during the past decade - Du, Mingxi; Peng, Changhui; Wang, Xiaoge; Chen, Huai; Wang, Meng; Zhu, Qiuan (Renewable and Sustainable Energy Reviews, 2017)

Effects of nitrogen deposition and management practices on leaf litterfall and N and P return in a Moso bamboo forest - Zhang, Junbo; Lv, Jianhua; Li, Quan; Ying, Yeqing; Peng, Changhui; Song, Xinzhang (Biogeochemistry, 2017)

Effects of three global change drivers on terrestrial C:N:P stoichiometry: a global synthesis - Yue, Kai; Fornara, Dario A.; Yang, Wanqin; Peng, Yan; Li, Zhijie; Wu, Fuzhong; Peng, Changhui (Global Change Biology, 2017)
Abstract Over the last few decades, there has been an increasing number of controlled‐manipulative experiments to investigate how plants and soils might respond to global change. These experiments typically examined the effects of each of three global change drivers [i.e., nitrogen (N) deposition, warming, and elevated CO 2 ] on primary productivity and on the biogeochemistry of carbon (C), N, and phosphorus (P) across different terrestrial ecosystems. Here, we capitalize on this large amount of information by performing a comprehensive meta‐analysis (>2000 case studies worldwide) to address how C:N:P stoichiometry of plants, soils, and soil microbial biomass might respond to individual vs. combined effects of the three global change drivers. Our results show that (i) individual effects of N addition and elevated CO 2 on C:N:P stoichiometry are stronger than warming, (ii) combined effects of pairs of global change drivers (e.g., N addition + elevated CO 2 , warming + elevated CO 2 ) on C:N:P stoichiometry were generally weaker than the individual effects of each of these drivers, (iii) additive interactions (i.e., when combined effects are equal to or not significantly different from the sum of individual effects) were more common than synergistic or antagonistic interactions, (iv) C:N:P stoichiometry of soil and soil microbial biomass shows high homeostasis under global change manipulations, and (v) C:N:P responses to global change are strongly affected by ecosystem type, local climate, and experimental conditions. Our study is one of the first to compare individual vs. combined effects of the three global change drivers on terrestrial C:N:P ratios using a large set of data. To further improve our understanding of how ecosystems might respond to future global change, long‐term ecosystem‐scale studies testing multifactor effects on plants and soils are urgently required across different world regions.

Stoichiometric and nutrient resorption characteristics of dominant tree species in subtropical Chinese forests - Zeng, Yelin; Fang, Xi; Xiang, Wenhua; Deng, Xiangwen; Peng, Changhui (Ecology and Evolution, 2017)
Abstract This study investigated seasonal patterns in stoichiometric ratios, nutrient resorption characteristics, and nutrient use strategies of dominant tree species at three successional stages in subtropical China, which have not been fully understood. Fresh leaf and leaf litterfall samples were collected in growing and nongrowing seasons for determining the concentrations of carbon (C), nitrogen (N), and phosphorus (P). Then, stoichiometric ratios (i.e., C:N, C:P, N:P, and C:N:P) and resorption parameters were calculated. Our results found that there was no consistent variation in leaf C:N and C:P ratios among different species. However, leaf N:P ratios in late‐successional species became significantly higher, indicating that P limitation increases during successional development. Due to the P limitation in this study area, P resorption efficiency and proficiency were higher than corresponding N resorption parameters. Dominant tree species at early‐successional stage adopted “conservative consumption” nutrient use strategy, whereas the species at late‐successional stage inclined to adopt “resource spending” strategy.

Towards a universal model for carbon dioxide uptake by plants - Wang, Han; Prentice, I. Colin; Keenan, Trevor F.; Davis, Tyler W.; Wright, Ian J.; Cornwell, William K.; Evans, Bradley J.; Peng, Changhui (Nature Plants, 2017)

Photosynthetic responses to altitude: an explanation based on optimality principles - Wang, Han; Prentice, I. Colin; Davis, Tyler W.; Keenan, Trevor F.; Wright, Ian J.; Peng, Changhui (New Phytologist, 2017)

Soil CH4 and CO2 dynamics and nitrogen transformations with incubation in mountain forest and meadow ecosystems - Zhang, Junjun; Peng, Changhui; Xue, Wei; Yang, Zhenan; Yang, Bin; Li, Peng; Zhu, Qiuan; Wang, Meng (CATENA, 2018)

Modeling Gross Primary Production of a Typical Coastal Wetland in China Using MODIS Time Series and CO2 Eddy Flux Tower Data - Kang, Xiaoming; Yan, Liang; Zhang, Xiaodong; Li, Yong; Tian, Dashuan; Peng, Changhui; Wu, Haidong; Wang, Jinzhi; Zhong, Lei (Remote Sensing, 2018)
How to effectively combine remote sensing data with the eddy covariance (EC) technique to accurately quantify gross primary production (GPP) in coastal wetlands has been a challenge and is also important and necessary for carbon (C) budgets assessment and climate change studies at larger scales. In this study, a satellite-based Vegetation Photosynthesis Model (VPM) combined with EC measurement and Moderate Resolution Imaging Spectroradiometer (MODIS) data was used to evaluate the phenological characteristics and the biophysical performance of MODIS-based vegetation indices (VIs) and the feasibility of the model for simulating GPP of coastal wetland ecosystems. The results showed that greenness-related and water-related VIs can better identify the green-up and the senescence phases of coastal wetland vegetation, corresponds well with the C uptake period and the phenological patterns that were delineated by GPP from EC tower (GPPEC). Temperature can explain most of the seasonal variation in VIs and GPPEC fluxes. Both enhanced vegetation index (EVI) and water-sensitive land surface water index (LSWI) have a higher predictive power for simulating GPP in this coastal wetland. The comparisons between modeled GPP (GPPVPM) and GPPEC indicated that VPM model can commendably simulate the trajectories of the seasonal dynamics of GPPEC fluxes in terms of patterns and magnitudes, explaining about 85% of GPPEC changes over the study years (p < 0.0001). The results also demonstrate the potential of satellite-driven VPM model for modeling C uptake at large spatial and temporal scales in coastal wetlands, which can provide valuable production data for the assessment of global wetland C sink/source.

Biochar mitigates dissolved organic carbon loss but does not affect dissolved organic nitrogen leaching loss caused by nitrogen deposition in Moso bamboo plantations - Lei, Zhaofeng; Li, Quan; Song, Xinzhang; Wang, Weifeng; Zhang, Zhiting; Peng, Changhui; Tian, Linlin (Global Ecology and Conservation, 2018)

Allocation Mechanisms of Non-Structural Carbohydrates of Robinia pseudoacacia L. Seedlings in Response to Drought and Waterlogging - Yang, Bin; Peng, Changhui; Harrison, Sandy P.; Wei, Hua; Wang, Han; Zhu, Qiuan; Wang, Meng (Forests, 2018)
Climate change is likely to lead to an increased frequency of droughts and floods, both of which are implicated in large-scale carbon allocation and tree mortality worldwide. Non-structural carbohydrates (NSCs) play an important role in tree survival under stress, but how NSC allocation changes in response to drought or waterlogging is still unclear. We measured soluble sugars (SS) and starch in leaves, twigs, stems and roots of Robinia pseudoacacia L. seedlings that had been subjected to a gradient in soil water availability from extreme drought to waterlogged conditions for a period of 30 days. Starch concentrations decreased and SS concentrations increased in tissues of R. pseudoacacia seedlings, such that the ratio of SS to starch showed a progressive increase under both drought and waterlogging stress. The strength of the response is asymmetric, with the largest increase occurring under extreme drought. While the increase in SS concentration in response to extreme drought is the largest in roots, the increase in the ratio of SS to starch is the largest in leaves. Individual components of SS showed different responses to drought and waterlogging across tissues: glucose concentrations increased significantly with drought in all tissues but showed little response to waterlogging in twigs and stems; sucrose and fructose concentrations showed marked increases in leaves and roots in response to drought but a greater response to drought and waterlogging in stems and twigs. These changes are broadly compatible with the roles of individual SS under conditions of water stress. While it is important to consider the role of NSC in buffering trees against mortality under stress, modelling this behaviour is unlikely to be successful unless it accounts for different responses within organs and the type of stress involved.

Hydrologic and Edaphic Controls on Soil Carbon Emission in Dongting Lake Floodplain, China - Deng, Zhengmiao; Li, Youzhi; Xie, Yonghong; Peng, Changhui; Chen, Xinsheng; Li, Feng; Ren, Yijie; Pan, Baihan; Zhang, Chengyi (Journal of Geophysical Research: Biogeosciences, 2018)
Abstract Wetlands play a critical role in mitigating carbon emission. However, little is known about soil carbon emission and their environmental controls from inland floodplain wetlands. This study aimed to determine the effects of hydrologic and edaphic controllers (water table depth [ WTD ], soil temperature [ Ts ], and soil water content [ SWC ]) on soil C emission in Dongting Lake wetland, China. One‐year emissions were measured in Carex meadow and mudflat using static chambers during 2013 to 2014, including nonflooded season ( NFs ) and flooded season ( Fs ). The results showed that soil C emission in the Carex meadow and mudflat was 307.8 and 264.3 g C·m −2 ·year −1 , respectively, and 50–66% of soil C were emitted during NFs. Compared with NFs, CO 2 emission was significantly decreased by 57% but CH 4 emission was significantly increased by 38 times during Fs in the Carex meadow. Stepwise regression combined with structural equation model analysis showed that CO 2 and CH 4 flux were mainly influenced by Ts during NFs, and they were controlled by water temperature ( Tw ) during Fs. During NFs, CO 2 flux increased with increasing Ts and SWC but decreased significantly when SWC was over 66% and 52% in the Carex meadow and mudflat, respectively. CH 4 flux showed an emission pulse at SWC and Ts of 65% and 17.2 °C, respectively. These results indicate that flooding significantly inhibited soil CO 2 emission but stimulated CH 4 emission. The continuous decrease of flooding days caused by anthropogenic disturbances may induce soil C loss in Dongting Lake wetlands. , Key Points Soil C emission in Dongting Lake floodplain was 264.3–307.8 g C.m ‐2 .year ‐1 Flooding significantly inhibited soil CO 2 emission but stimulated CH 4 emission The decline of flooding days in Dongting Lake wetlands can potentially increase soil C loss

Data supporting assessment for nitrous oxide emissions from soils under traditional cropland and apple orchard in the Loess Plateau of China - Pang, Junzhu; Wang, Xiaoke; Peng, Changhui; Mu, Yujing; Ouyang, Zhiyun; Lu, Fei; Zhang, Hongxing; Zhang, Shuoxin; Liu, Wenzhao (Data in Brief, 2018)

CH4 concentrations and fluxes in a subtropical metropolitan river network: Watershed urbanization impacts and environmental controls - Wang, Xiaofeng; He, Yixin; Chen, Huai; Yuan, Xingzhong; Peng, Changhui; Yue, Junsheng; Zhang, Qiaoyong; Zhou, Lilei (Science of The Total Environment, 2018)

A global strategy to mitigate the environmental impact of China’s ruminant consumption boom - Du, Yuanyuan; Ge, Ying; Ren, Yuan; Fan, Xing; Pan, Kaixuan; Lin, Linshan; Wu, Xu; Min, Yong; Meyerson, Laura A.; Heino, Mikko; Chang, Scott X.; Liu, Xiaozi; et al. (Nature Communications, 2018)
Abstract Rising demand for ruminant meat and dairy products in developing countries is expected to double anthropogenic greenhouse gas and ammonia emissions from livestock by 2050. Mitigation strategies are urgently needed to meet demand while minimizing environmental impacts. Here, we develop scenarios for mitigating emissions under local vs global supply policies using data from 308 livestock farms across mainland China, where emissions intensities are ~50% higher than those in developed nations. Intensification of domestic production and globalized expansion through increased trade result in reductions in global emissions by nearly 30% over a business-as-usual scenario, but at the expense of trading partners absorbing the associated negative externalities of environmental degradation. Only adoption of a mixed strategy combining global best-practice in sustainable intensification of domestic production, with increased green-source trading as a short-term coping strategy, can meet 2050 demand while minimizing the local and global environmental footprint of China’s ruminant consumption boom.

Development of a New TRIPLEX-Insect Model for Simulating the Effect of Spruce Budworm on Forest Carbon Dynamics - Liu, Zelin; Peng, Changhui; De Grandpré, Louis; Candau, Jean-Noël; Zhou, Xiaolu; Kneeshaw, Daniel (Forests, 2018)
The spruce budworm (SBW) defoliates and kills conifer trees, consequently affecting carbon (C) exchanges between the land and atmosphere. Here, we developed a new TRIPLEX-Insect sub-model to quantify the impacts of insect outbreaks on forest C fluxes. We modeled annual defoliation (AD), cumulative defoliation (CD), and tree mortality. The model was validated against observed and published data at the stand level in the North Shore region of Québec and Cape Breton Island in Nova Scotia, Canada. The results suggest that TRIPLEX-Insect performs very well in capturing tree mortality following SBW outbreaks and slightly underestimates current annual volume increment (CAI). In both mature and immature forests, the simulation model suggests a larger reduction in gross primary productivity (GPP) than in autotrophic respiration (Ra) at the same defoliation level when tree mortality was low. After an SBW outbreak, the growth release of surviving trees contributes to the recovery of annual net ecosystem productivity (NEP) based on forest age if mortality is not excessive. Overall, the TRIPLEX-Insect model is capable of simulating C dynamics of balsam fir following SBW disturbances and can be used as an efficient tool in forest insect management.

Application of machine-learning methods in forest ecology: recent progress and future challenges - Liu, Zelin; Peng, Changhui; Work, Timothy; Candau, Jean-Noel; DesRochers, Annie; Kneeshaw, Daniel (Environmental Reviews, 2018)
Machine learning, an important branch of artificial intelligence, is increasingly being applied in sciences such as forest ecology. Here, we review and discuss three commonly used methods of machine learning (ML) including decision-tree learning, artificial neural network, and support vector machine and their applications in four different aspects of forest ecology over the last decade. These applications include: (i) species distribution models, (ii) carbon cycles, (iii) hazard assessment and prediction, and (iv) other applications in forest management. Although ML approaches are useful for classification, modeling, and prediction in forest ecology research, further expansion of ML technologies is limited by the lack of suitable data and the relatively “higher threshold” of applications. However, the combined use of multiple algorithms and improved communication and cooperation between ecological researchers and ML developers still present major challenges and tasks for the betterment of future ecological research. We suggest that future applications of ML in ecology will become an increasingly attractive tool for ecologists in the face of “big data” and that ecologists will gain access to more types of data such as sound and video in the near future, possibly opening new avenues of research in forest ecology.

Controls of soil and aggregate‐associated organic carbon variations following natural vegetation restoration on the L oess P lateau in C hina - Deng, Lei; Kim, Dong‐Gill; Peng, Changhui; Shangguan, Zhouping (Land Degradation & Development, 2018)
Abstract Natural vegetation restoration can enhance soil organic carbon (SOC) sequestration, but the mechanisms and control factors underlying SOC sequestration are still unknown. The objectives of the study are to quantify the temporal variation of soil and aggregate‐associated organic carbon (OC) and identify factors controlling the variation following natural vegetation restoration after farmland abandonment. We collected soils from sites having 5, 30, 60, 100, and 160 years of a natural vegetation restoration chronosequence after farmland abandonment in the Loess Plateau, China. The results showed that natural vegetation restoration increased macroaggregates (0.25–2 mm; 46.6% to 73.9%), SOC (2.27 to 9.81 g kg −1 ), and aggregate OC (7.33 to 36.98 g kg −1 ) in the top 20‐cm soil compared with abandoned farmland, and the increases mainly occurred in the early stage (<60 years). The increase of SOC was contributed by OC accumulated in macroaggregates (0.25–2 mm) rather than microaggregates (≤0.25 mm). Moreover, SOC sequestration in the topsoil (0–10 cm) was mainly determined by fine root biomass (FR), labile organic carbon (LOC), and microbial biomass carbon (MBC). And in the subsoil (10–20 cm), SOC sequestration was mainly determined by the proportion of macroaggregates. The results suggest that natural vegetation restoration increased SOC and aggregate OC, and FR, MBC, LOC, and the physical protection of aggregates played important roles in regulating SOC and aggregate OC.

Asymmetric responses of primary productivity to altered precipitation simulated by ecosystem models across three long-term grassland sites - Wu, Donghai; Ciais, Philippe; Viovy, Nicolas; Knapp, Alan K.; Wilcox, Kevin; Bahn, Michael; Smith, Melinda D.; Vicca, Sara; Fatichi, Simone; Zscheischler, Jakob; He, Yue; Li, Xiangyi; et al. (Biogeosciences, 2018)
Abstract. Field measurements of aboveground net primary productivity (ANPP) in temperate grasslands suggest that both positive and negative asymmetric responses to changes in precipitation (P) may occur. Under normal range of precipitation variability, wet years typically result in ANPP gains being larger than ANPP declines in dry years (positive asymmetry), whereas increases in ANPP are lower in magnitude in extreme wet years compared to reductions during extreme drought (negative asymmetry). Whether the current generation of ecosystem models with a coupled carbon–water system in grasslands are capable of simulating these asymmetric ANPP responses is an unresolved question. In this study, we evaluated the simulated responses of temperate grassland primary productivity to scenarios of altered precipitation with 14 ecosystem models at three sites: Shortgrass steppe (SGS), Konza Prairie (KNZ) and Stubai Valley meadow (STU), spanning a rainfall gradient from dry to moist. We found that (1) the spatial slopes derived from modeled primary productivity and precipitation across sites were steeper than the temporal slopes obtained from inter-annual variations, which was consistent with empirical data; (2) the asymmetry of the responses of modeled primary productivity under normal inter-annual precipitation variability differed among models, and the mean of the model ensemble suggested a negative asymmetry across the three sites, which was contrary to empirical evidence based on filed observations; (3) the mean sensitivity of modeled productivity to rainfall suggested greater negative response with reduced precipitation than positive response to an increased precipitation under extreme conditions at the three sites; and (4) gross primary productivity (GPP), net primary productivity (NPP), aboveground NPP (ANPP) and belowground NPP (BNPP) all showed concave-down nonlinear responses to altered precipitation in all the models, but with different curvatures and mean values. Our results indicated that most models overestimate the negative drought effects and/or underestimate the positive effects of increased precipitation on primary productivity under normal climate conditions, highlighting the need for improving eco-hydrological processes in those models in the future.

Estimates and Predictions of Methane Emissions from Wastewater in China from 2000 to 2020 - Du, Mingxi; Zhu, Qiuan; Wang, Xiaoge; Li, Peng; Yang, Bin; Chen, Huai; Wang, Meng; Zhou, Xiaolu; Peng, Changhui (Earth's Future, 2018)
Methane accounts for 20% of the global warming caused by greenhouse gases, and wastewater is a major anthropogenic source of methane. Based on the Intergovernmental Panel on Climate Change greenhouse gas inventory guidelines and current research findings, we calculated the amount of methane emissions from 2000 to 2014 that originated from wastewater from different provinces in China. Methane emissions from wastewater increased from 1349.01 to 3430.03 Gg from 2000 to 2014, and the mean annual increase was 167.69 Gg. The methane emissions from industrial wastewater treated by wastewater treatment plants ( E It ) accounted for the highest proportion of emissions. We also estimated the future trend of industrial wastewater methane emissions using the artificial neural network model. A comparison of the emissions for the years 2020, 2010, and 2000 showed an increasing trend in methane emissions in China and a spatial transition of industrial wastewater emissions from eastern and southern regions to central and southwestern regions and from coastal regions to inland regions. These changes were caused by changes in economics, demographics, and relevant policies. , Key Points Methane emission from wastewater from 2000 to 2014 was calculated to increase from 1349.01 Gg to 3430.03 Gg. Methane emission from wastewater from 2015 to 2020 was estimated to increase from 3875.30 Gg to 5212.75 Gg. A spatial transition of methane emission from wastewater was found and discussed in the present study.

The response of the net primary production of Moso bamboo forest to the On and Off-year management: A case study in Anji County, Zhejiang, China - Chen, Shulin; Jiang, Hong; Cai, Zhijian; Zhou, Xiaolu; Peng, Changhui (Forest Ecology and Management, 2018)

Effect of Drought on Agronomic Traits of Rice and Wheat: A Meta-Analysis - Zhang, Jinmeng; Zhang, Shiqiao; Cheng, Min; Jiang, Hong; Zhang, Xiuying; Peng, Changhui; Lu, Xuehe; Zhang, Minxia; Jin, Jiaxin (International Journal of Environmental Research and Public Health, 2018)
Drought has been one of the most important limiting factors for crop production, which deleteriously affects food security worldwide. The main objective of the present study was to quantitatively assess the effect of drought on the agronomic traits (e.g., plant height, biomass, yield, and yield components) of rice and wheat in combination with several moderators (e.g., drought stress intensity, rooting environment, and growth stage) using a meta-analysis study. The database was created from 55 published studies on rice and 60 published studies on wheat. The results demonstrated that drought decreased the agronomic traits differently between rice and wheat among varying growth stages. Wheat and rice yields decreased by 27.5% and 25.4%, respectively. Wheat grown in pots showed greater decreases in agronomic traits than those grown in the field. Rice showed opposite growing patterns when compared to wheat in rooting environments. The effect of drought on rice increased with plant growth and drought had larger detrimental influences during the reproductive phase (e.g., blooming stage, filling stage, and maturity). However, an exception was found in wheat, which had similar decreased performance during the complete growth cycle. Based on these results, future droughts could produce lower yields of rice and wheat when compared to the current drought.

Large-scale detection of vegetation dynamics and their potential drivers using MODIS images and BFAST: A case study in Quebec, Canada - Fang, Xiuqin; Zhu, Qiuan; Ren, Liliang; Chen, Huai; Wang, Kai; Peng, Changhui (Remote Sensing of Environment, 2018)

Multi-scale temporal variation of methane flux and its controls in a subtropical tidal salt marsh in eastern China - Li, Hong; Dai, Shengqi; Ouyang, Zutao; Xie, Xiao; Guo, Haiqiang; Gu, Caihong; Xiao, Xiangming; Ge, Zhenming; Peng, Changhui; Zhao, Bin (Biogeochemistry, 2018)

The linkage between vegetation and soil nutrients and their variation under different grazing intensities in an alpine meadow on the eastern Qinghai-Tibetan Plateau - Yang, Zhenan; Zhu, Qiuan; Zhan, Wei; Xu, Yingyi; Zhu, Erxiong; Gao, Yongheng; Li, Shiqing; Zheng, Qunying; Zhu, Dan; He, Yixin; Peng, Changhui; Chen, Huai (Ecological Engineering, 2018)

Individual and combined effects of multiple global change drivers on terrestrial phosphorus pools: A meta-analysis - Yue, Kai; Yang, Wanqin; Peng, Yan; Peng, Changhui; Tan, Bo; Xu, Zhenfeng; Zhang, Li; Ni, Xiangyin; Zhou, Wei; Wu, Fuzhong (Science of The Total Environment, 2018)

A critical analysis of the carbon neutrality assumption in life cycle assessment of forest bioenergy systems - Liu, Weiguo; Yu, Zhen; Xie, Xinfeng; Von Gadow, Klaus; Peng, Changhui (Environmental Reviews, 2018)
This study presents a critical analysis regarding the assumption of carbon neutrality in life cycle assessment (LCA) models that assess climate change impacts of bioenergy usage. We identified a complex of problems in the carbon neutrality assumption, especially regarding bioenergy derived from forest residues. In this study, we summarized several issues related to carbon neutral assumptions, with particular emphasis on possible carbon accounting errors at the product level. We analyzed errors in estimating emissions in the supply chain, direct and indirect emissions due to forest residue extraction, biogenic CO 2 emission from biomass combustion for energy, and other effects related to forest residue extraction. Various modeling approaches are discussed in detail. We concluded that there is a need to correct accounting errors when estimating climate change impacts and proposed possible remedies. To accurately assess climate change impacts of bioenergy use, greater efforts are required to improve forest carbon cycle modeling, especially to identify and correct pitfalls associated with LCA accounting, forest residue extraction effects on forest fire risk and biodiversity. Uncertainties in accounting carbon emissions in LCA are also highlighted, and associated risks are discussed.

Variation in Soil Methane Fluxes and Comparison between Two Forests in China - Wei, Hua; Peng, Changhui; Liu, Shirong; Liu, Xiaojing; Li, Peng; Song, Hanxiong; Yuan, Minshu; Wang, Meng (Forests, 2018)
Methane (CH4) is a vital greenhouse gas with a 28-fold higher global warming potential than carbon dioxide when considering a molar basis for the time horizon of 100 years. Here, we investigated the variation of soil CH4 fluxes, soil physiochemical properties, and CH4-related bacteria community composition of two forests in China. We measured CH4 fluxes using static chambers and analyzed soil bacterial communities using next-generation high-throughput sequencing in a temperate broad-leaved deciduous forest at Baotianman Nature Reserve (TBDF-BTM) and a tropical rainforest at Jianfengling National Natural Reserve (TRF-JFL). Our results showed that the soils from both sites were CH4 sinks. Significant variation in soil CH4 fluxes was found at TBDF-BTM exclusively, while no seasonal variation in the CH4 uptake was observed at TRF-JFL. The CH4 fluxes at TBDF-BTM were substantially higher than those at TRF-JFL during all seasons. One genus of methanotrophs and three genera of methylotrophs were detected at both sites, though they had no direct relationship with soil CH4 fluxes. Water-filled pore space and soil total carbon content are the main factors controlling the soil CH4 fluxes at TBDF-BTM. At TRF-JFL, the soil CH4 fluxes showed no significant correlations with any of the soil properties. This study improves our understanding of soil CH4 fluxes and their influencing factors in forests in different climatic zones and provides a reference for future investigation of forest soil CH4 fluxes, the forest ecosystem carbon cycle, and the forest CH4 model.

Recoupling Industrial Dairy Feedlots and Industrial Farmlands Mitigates the Environmental Impacts of Milk Production in China - Fan, Xing; Chang, Jie; Ren, Yuan; Wu, Xu; Du, Yuanyuan; Xu, Ronghua; Liu, Dong; Chang, Scott X.; Meyerson, Laura A.; Peng, Changhui; Ge, Ying (Environmental Science & Technology, 2018)

Positive responses of belowground C dynamics to nitrogen enrichment in China - Deng, Lei; Peng, Changhui; Zhu, Guangyu; Chen, Lei; Liu, Yulin; Shangguan, Zhouping (Science of The Total Environment, 2018)

Stand carbon density drivers and changes under future climate scenarios across global forests - Guo, Yanrong; Peng, Changhui; Trancoso, Ralph; Zhu, Qiuan; Zhou, Xiaolu (Forest Ecology and Management, 2019)

Simulation of dissolved organic carbon concentrations and fluxes in Chinese monsoon forest ecosystems using a modified TRIPLEX-DOC model - Shi, Shengwei; Yang, Mingxia; Hou, Yue; Peng, Changhui; Wu, Haibin; Zhu, Qiuan; Liang, Qiong; Xie, Junfei; Wang, Meng (Science of The Total Environment, 2019)

Re-estimating the changes and ranges of forest biomass carbon in China during the past 40 years - Zhou, Xiaolu; Lei, Xiangdong; Liu, Caixia; Huang, Huabing; Zhou, Carl; Peng, Changhui (Forest Ecosystems, 2019)
Abstract Background In recent decades the future of global forests has been a matter of increasing concern, particularly in relation to the threat of forest ecosystem responses under potential climate change. To the future predictions of these responses, the current forest biomass carbon storage (FCS) should first be clarified as much as possible, especially at national scales. However, few studies have introduced how to verify an FCS estimate by delimiting the reasonable ranges. This paper addresses an estimation of national FCS and its verification using two-step process to narrow the uncertainty. Our study focuses on a methodology for reducing the uncertainty resulted by converting from growing stock volume to above- and below-ground biomass (AB biomass), so as to eliminate the significant bias in national scale estimations. Methods We recommend splitting the estimation into two parts, one part for stem and the other part for AB biomass to preclude possible significant bias. Our method estimates the stem biomass from volume and wood density (WD), and converts the AB biomass from stem biomass by using allometric relationships. Results Based on the presented two-step process, the estimation of China’s FCS is performed as an example to explicate how to infer the ranges of national FCS. The experimental results demonstrate a national FCS estimation within the reasonable ranges (relative errors: + 4.46% and − 4.44%), e.g., 5.6–6.1 PgC for China’s forest ecosystem at the beginning of the 2010s. These ranges are less than 0.52 PgC for confirming each FCS estimate of different periods during the last 40 years. In addition, our results suggest the upper-limits by specifying a highly impractical value of WD (0.7 t∙m − 3 ) on the national scale. As a control reference, this value decides what estimate is impossible to achieve for the FCS estimates. Conclusions Presented methodological analysis highlights the possibility to determine a range that the true value could be located in. The two-step process will help to verify national FCS and also to reduce uncertainty in related studies. While the true value of national FCS is immeasurable, our work should motivate future studies that explore new estimations to approach the true value by narrowing the uncertainty in FCS estimations on national and global scales.

Comparison of methane emissions among invasive and native mangrove species in Dongzhaigang, Hainan Island - He, Yixin; Guan, Wei; Xue, Dan; Liu, Liangfeng; Peng, Changhui; Liao, Baowen; Hu, Ji; Zhu, Qiu'an; Yang, Yanzhen; Wang, Xu; Zhou, Guanyi; Wu, Zhongming; et al. (Science of The Total Environment, 2019)

Exposures to temperature beyond threshold disproportionately reduce vegetation growth in the northern hemisphere - Wu, Xiuchen; Guo, Weichao; Liu, Hongyan; Li, Xiaoyan; Peng, Changhui; Allen, Craig D; Zhang, Cicheng; Wang, Pei; Pei, Tingting; Ma, Yujun; Tian, Yuhong; Song, Zhaoliang; et al. (National Science Review, 2019)
Abstract In recent decades, terrestrial vegetation in the northern hemisphere (NH) has been exposed to warming and more extremely high temperatures. However, the consequences of these changes for terrestrial vegetation growth remain poorly quantified and understood. By examining a satellite-based vegetation index, tree-ring measurements and land-surface model simulations, we discovered a consistent convex pattern in the responses of vegetation growth to temperature exposure (TE) for forest, shrub and grass in both the temperate (30°−50° N) and boreal (50°−70° N) NH during the period of 1982−2012. The response of vegetation growth to TE for the three vegetation types in both the temperate and boreal NH increased convergently with increasing temperature, until vegetation type-dependent temperature thresholds were reached. A TE beyond these temperature thresholds resulted in disproportionately weak positive or even strong negative responses. Vegetation growth in the boreal NH was more vulnerable to extremely high-temperature events than vegetation growth in the temporal NH. The non-linear responses discovered here provide new insights into the dynamics of northern terrestrial ecosystems in a warmer world.

Carbon and Water Use Efficiencies: A Comparative Analysis of Ten Terrestrial Ecosystem Models under Changing Climate - El Masri, Bassil; Schwalm, Christopher; Huntzinger, Deborah N.; Mao, Jiafu; Shi, Xiaoying; Peng, Changhui; Fisher, Joshua B.; Jain, Atul K.; Tian, Hanqin; Poulter, Benjamin; Michalak, Anna M. (Scientific Reports, 2019)
Abstract Terrestrial ecosystems carbon and water cycles are tightly coupled through photosynthesis and evapotranspiration processes. The ratios of carbon stored to carbon uptake and water loss to carbon gain are key ecophysiological indicators essential to assess the magnitude and response of the terrestrial plant to the changing climate. Here, we use estimates from 10 terrestrial ecosystem models to quantify the impacts of climate, atmospheric CO 2 concentration, and nitrogen (N) deposition on water use efficiency (WUE), and carbon use efficiency (CUE). We find that across models, WUE increases over the 20 th Century particularly due to CO 2 fertilization and N deposition and compares favorably to experimental studies. Also, the results show a decrease in WUE with climate for the last 3 decades, in contrasts with up-scaled flux observations that demonstrate a constant WUE. Modeled WUE responds minimally to climate with modeled CUE exhibiting no clear trend across space and time. The divergence between simulated and observationally-constrained WUE and CUE is driven by modeled NPP and autotrophic respiration, nitrogen cycle, carbon allocation, and soil moisture dynamics in current ecosystem models. We suggest that carbon-modeling community needs to reexamine stomatal conductance schemes and the soil-vegetation interactions for more robust modeling of carbon and water cycles.

Field-experiment constraints on the enhancement of the terrestrial carbon sink by CO2 fertilization - Liu, Yongwen; Piao, Shilong; Gasser, Thomas; Ciais, Philippe; Yang, Hui; Wang, Han; Keenan, Trevor F.; Huang, Mengtian; Wan, Shiqiang; Song, Jian; Wang, Kai; Janssens, Ivan A.; et al. (Nature Geoscience, 2019)

Pervasive decreases in living vegetation carbon turnover time across forest climate zones - Yu, Kailiang; Smith, William K.; Trugman, Anna T.; Condit, Richard; Hubbell, Stephen P.; Sardans, Jordi; Peng, Changhui; Zhu, Kai; Peñuelas, Josep; Cailleret, Maxime; Levanic, Tom; Gessler, Arthur; et al. (Proceedings of the National Academy of Sciences, 2019)
Forests play a major role in the global carbon cycle. Previous studies on the capacity of forests to sequester atmospheric CO 2 have mostly focused on carbon uptake, but the roles of carbon turnover time and its spatiotemporal changes remain poorly understood. Here, we used long-term inventory data (1955 to 2018) from 695 mature forest plots to quantify temporal trends in living vegetation carbon turnover time across tropical, temperate, and cold climate zones, and compared plot data to 8 Earth system models (ESMs). Long-term plots consistently showed decreases in living vegetation carbon turnover time, likely driven by increased tree mortality across all major climate zones. Changes in living vegetation carbon turnover time were negatively correlated with CO 2 enrichment in both forest plot data and ESM simulations. However, plot-based correlations between living vegetation carbon turnover time and climate drivers such as precipitation and temperature diverged from those of ESM simulations. Our analyses suggest that forest carbon sinks are likely to be constrained by a decrease in living vegetation carbon turnover time, and accurate projections of forest carbon sink dynamics will require an improved representation of tree mortality processes and their sensitivity to climate in ESMs.

Modelling the impacts of climate and land use changes on soil water erosion: Model applications, limitations and future challenges - Guo, Yanrong; Peng, Changhui; Zhu, Qiuan; Wang, Meng; Wang, Han; Peng, Shushi; He, Honglin (Journal of Environmental Management, 2019)

Modeling Global Riverine DOC Flux Dynamics From 1951 to 2015 - Li, Mingxu; Peng, Changhui; Zhou, Xiaolu; Yang, Yanzheng; Guo, Yanrong; Shi, Guohua; Zhu, Qiuan (Journal of Advances in Modeling Earth Systems, 2019)
Abstract Climate change has a profound impact on the global carbon cycle, including effects on riverine carbon pools, which connect terrestrial, oceanic, and atmospheric carbon pools. Until now, terrestrial ecosystem models have rarely incorporated riverine carbon components into global carbon budgets. Here we developed a new process‐based model, TRIPLEX‐HYDRA (TRIPLEX‐hydrological routing algorithm), that considers the production, consumption, and transport processes of nonanthropogenic dissolved organic carbon (DOC) from soil to river ecosystems. After the parameter calibration, model results explained more than 50% of temporal variations in all but three rivers. Validation results suggested that DOC yield simulated by TRIPLEX‐HYDRA has a good fit ( R 2 = 0.61, n = 71, p < 0.001) with global river observations. And then, we applied this model for global rivers. We found that mean DOC yield of global river approximately 1.08 g C/m 2 year, where most high DOC yield appeared in the rivers from high northern or tropic regions. Furthermore, our results suggested that global riverine DOC flux appeared a significant decrease trend (average rate: 0.38 Pg C/year) from 1951 to 2015, although the variation patterns of DOC fluxes in global rivers are diverse. A decreasing trend in riverine DOC flux appeared in the middle and high northern latitude regions (30–90°N), which could be attributable to an increased flow path and DOC degradation during the transport process. Furthermore, increasing trend of DOC fluxes is found in rivers from tropical regions (30°S–30°N), which might be related to an increase in terrestrial organic carbon input. Many other rivers (e.g., Mississippi, Yangtze, and Lena rivers) experienced no significant changes under a changing environment. , Key Points Terrestrial ecosystem models rarely incorporate riverine DOC components into the global carbon cycle The TRIPLEX‐HYDRA model simulates the spatiotemporal variation in the DOC fluxes in global rivers The global riverine DOC flux simulated by the TRIPLEX‐HYDRA model has significantly decreased from 1951 to 2015

Simulation and Analysis of the Effect of a Spruce Budworm Outbreak on Carbon Dynamics in Boreal Forests of Quebec - Liu, Zelin; Peng, Changhui; De Grandpré, Louis; Candau, Jean-Noël; Work, Timothy; Huang, Chunbo; Kneeshaw, Daniel (Ecosystems, 2019)

Responses of nitrogen concentrations and pools to multiple environmental change drivers: A meta‐analysis across terrestrial ecosystems - Yue, Kai; Peng, Yan; Fornara, Dario A.; Van Meerbeek, Koenraad; Vesterdal, Lars; Yang, Wanqin; Peng, Changhui; Tan, Bo; Zhou, Wei; Xu, Zhenfeng; Ni, Xiangyin; Zhang, Li; et al. (Global Ecology and Biogeography, 2019)
Abstract Aim We sought to understand how the individual and combined effects of multiple environmental change drivers differentially influence terrestrial nitrogen (N) concentrations and N pools and whether the interactive effects of these drivers are mainly antagonistic, synergistic or additive. Location Worldwide. Time period Contemporary. Major taxa studied Plants, soil, and soil microbes in terrestrial ecosystems. Methods We synthesized data from manipulative field studies from 758 published articles to estimate the individual, combined and interactive effects of key environmental change drivers (elevated CO 2 , warming, N addition, phosphorus addition, increased rainfall and drought) on plant, soil, and soil microbe N concentrations and pools using meta‐analyses. We assessed the influences of moderator variables on these effects through structural equation modelling. Results We found that (a) N concentrations and N pools were significantly affected by the individual and combined effects of multiple drivers, with N addition (either alone or in combination with another driver) showing the strongest positive effects; (b) the individual and combined effects of these drivers differed significantly between N concentrations and N pools in plants, but seldom in soils and microbes; (c) additive effects of driver pairs on N concentrations and pools were much more common than synergistic or antagonistic effects across plants, soils and microbes; and (d) environmental and experimental factors were important moderators of the individual, combined and interactive effects of these drivers on terrestrial N. Main conclusions Our results indicate that terrestrial N concentrations and N pools, especially those of plants, can be significantly affected by the individual and combined effects of environmental change drivers, with the interactive effects of these drivers being mostly additive. Our findings are important because they contribute to the development of models to better predict how altered N availability affects ecosystem carbon cycling under future environmental changes.

Structural and functional differentiation of the microbial community in the surface and subsurface peat of two minerotrophic fens in China - Wang, Meng; Tian, Jianqing; Bu, Zhaojun; Lamit, Louis J.; Chen, Huai; Zhu, Qiuan; Peng, Changhui (Plant and Soil, 2019)

Factors Affecting the Spatial and Temporal Variations in Soil Erodibility of China - Zhu, Guangyu; Tang, Zhuangsheng; Shangguan, Zhouping; Peng, Changhui; Deng, Lei (Journal of Geophysical Research: Earth Surface, 2019)
Abstract Soil erosion occurs extensively across China, leading to severe degradation of the land and ecosystem services. However, the spatial and temporal variations in soil erodibility ( k ) and the distribution of soil erosion across land use types and slopes remain unclear. We synthesized the results from 325 sites published in 152 literatures to analyze the factors affecting the k , such as land use type, climate, topography, soil, and vegetation restoration age. The results showed that areas with slopes >25° had a larger k factor ( k = 0.1047) than did those with slope <6° ( k = 0.0637) or 6–25° ( k = 0.0832). The k from 2006 to 2011 ( k = 0.0725) was higher than that from 1999 to 2005 ( k = 0.058) and that from 2012 to 2016 ( k = 0.0631). The k value initially increased with vegetation restoration age and then gradually decreased. Land use also had an impact on the k factor, with the k factor of cropland ( k = 0.0697) being higher than that of grassland ( k = 0.0663) but lower than that of forest ( k = 0.0967). Across China, North Shaanxi, Heilongjiang, and South Guizhou, which are located in the Loess Plateau in Northwest China, the Black Soil region of Northeast China, and the Karst areas in Southwest China, respectively, were the three most severely eroded regions due to hydraulic erosion, frost‐thaw erosion, and high‐intensity erosion, respectively. Overall, the most important factors affecting the k were soil characteristics, followed by topography and climate. Among them, soil nitrogen and precipitation were the two most critical factors influencing the k . , Key Points Grassland had lower soil erodibility than had cropland and forestland North Shaanxi, Heilongjiang, and South Guizhou were the three most severely eroded regions Precipitation and soil N play critical roles in controlling soil erosion

Assessment of frozen ground organic carbon pool on the Qinghai-Tibet Plateau - Jiang, Lin; Chen, Huai; Zhu, Qiuan; Yang, Yanzheng; Li, Mingxu; Peng, Changhui; Zhu, Dan; He, Yixin (Journal of Soils and Sediments, 2019)

Separating Regressions for Model Fitting to Reduce the Uncertainty in Forest Volume-Biomass Relationship - Liu, Caixia; Zhou, Xiaolu; Lei, Xiangdong; Huang, Huabing; Zhou, Carl; Peng, Changhui; Wang, Xiaoyi (Forests, 2019)
The method of forest biomass estimation based on a relationship between the volume and biomass has been applied conventionally for estimating stand above- and below-ground biomass (SABB, t ha−1) from mean growing stock volume (m3 ha−1). However, few studies have reported on the diagnosis of the volume-SABB equations fitted using field data. This paper addresses how to (i) check parameters of the volume-SABB equations, and (ii) reduce the bias while building these equations. In our analysis, all equations were applied based on the measurements of plots (biomass or volume per hectare) rather than individual trees. The volume-SABB equation is re-expressed by two Parametric Equations (PEs) for separating regressions. Stem biomass is an intermediate variable (parametric variable) in the PEs, of which one is established by regressing the relationship between stem biomass and volume, and the other is created by regressing the allometric relationship of stem biomass and SABB. A graphical analysis of the PEs proposes a concept of “restricted zone,” which helps to diagnose parameters of the volume-SABB equations in regression analyses of field data. The sampling simulations were performed using pseudo data (artificially generated in order to test a model) for the model test. Both analyses of the regression and simulation demonstrate that the wood density impacts the parameters more than the allometric relationship does. This paper presents an applicable method for testing the field data using reasonable wood densities, restricting the error in field data processing based on limited field plots, and achieving a better understanding of the uncertainty in building those equations.

Variation in the functional traits of fine roots is linked to phylogenetics in the common tree species of Chinese subtropical forests - Liu, Cong; Xiang, Wenhua; Zou, Limei; Lei, Pifeng; Zeng, Yelin; Ouyang, Shuai; Deng, Xiangwen; Fang, Xi; Liu, Zelin; Peng, Changhui (Plant and Soil, 2019)

Linkage between tree species richness and soil microbial diversity improves phosphorus bioavailability - Wu, Huili; Xiang, Wenhua; Ouyang, Shuai; Forrester, David I.; Zhou, Bo; Chen, Lingxiu; Ge, Tida; Lei, Pifeng; Chen, Liang; Zeng, Yelin; Song, Xinzhang; Peñuelas, Josep; et al. (Functional Ecology, 2019)
Abstract Increased availability of soil phosphorus (P) has recently been recognised as an underlying driving factor for the positive relationship between plant diversity and ecosystem function. The effects of plant diversity on the bioavailable forms of P involved in biologically mediated rhizospheric processes and how the link between plant and soil microbial diversity facilitates soil P bioavailability, however, remain poorly understood. This study quantified four forms of bioavailable P (CaCl 2 ‐P, citric‐P, enzyme‐P and HCl‐P) in mature subtropical forests using a novel biologically based approach, which emulates how rhizospheric processes influence the release and supply of available P. Soil microbial diversity was measured by Illumina high‐throughput sequencing. Our results suggest that tree species richness significantly affects soil microbial diversity ( p < 0.05), increases litter decomposition, fine‐root biomass and length and soil organic carbon and thus increases the four forms of bioavailable P. A structural equation model that links plants, soil microbes and P forms indicated that soil bacterial and fungal diversity play dominant roles in mediating the effects of tree species richness on soil P bioavailability. An increase in the biodiversity of plants, soil bacteria and fungi could maintain soil P bioavailability and alleviate soil P limitations. Our results imply that biodiversity strengthens plant and soil feedback and increases P recycling. A plain language summary is available for this article.

Effects of stand age, richness and density on productivity in subtropical forests in China - Ouyang, Shuai; Xiang, Wenhua; Wang, Xiangping; Xiao, Wenfa; Chen, Liang; Li, Shenggong; Sun, Han; Deng, Xiangwen; Forrester, David I.; Zeng, Lixiong; Lei, Pifeng; Lei, Xiangdong; et al. (Journal of Ecology, 2019)
Abstract Forest productivity may be determined not only by biodiversity but also by environmental factors and stand structure attributes. However, the relative importance of these factors in determining productivity is still controversial for subtropical forests. Based on a large dataset from 600 permanent forest inventory plots across subtropical China, we examined the relationship between biodiversity and forest productivity and tested whether stand structural attributes (stand density in terms of trees per ha, age and tree size) and environmental factors (climate and site conditions) had larger effects on productivity. Furthermore, we quantified the relative importance of environmental factors, stand structure and diversity in determining forest productivity. Diversity, together with stand structure and site conditions, regulated the variability in forest productivity. The relationship between diversity and forest productivity did not vary along environmental gradients. Stand density and age were more important modulators of forest productivity than diversity. Synthesis . Diversity had significant and positive effects on productivity in species‐rich subtropical forests, but the effects of stand density and age were also important. Our work highlights that while biodiversity conservation is often important, the regulation of stand structure can be even more important to maintain high productivity in subtropical forests.

The effects of persistent drought and waterlogging on the dynamics of nonstructural carbohydrates of Robinia pseudoacacia L. seedlings in Northwest China - Yang, Bin; Peng, Changhui; Zhu, Qiuan; Zhou, Xiaolu; Liu, Weiguo; Duan, Min; Wang, Hui; Liu, Zhihao; Guo, Xinyi; Wang, Meng (Forest Ecosystems, 2019)

Weakening of the ‘enzymatic latch’ mechanism following long-term fertilization in a minerotrophic peatland - Li, Tong; Bu, Zhaojun; Liu, Wenyan; Zhang, Mingying; Peng, Changhui; Zhu, Qiuan; Shi, Shengwei; Wang, Meng (Soil Biology and Biochemistry, 2019)

Changes in soil organic carbon and microbial carbon storage projected during the 21st century using TRIPLEX-MICROBE - Wang, Kefeng; Peng, Changhui; Zhu, Qiuan; Wang, Meng; Wang, Gangsheng; Zhou, Xiaolu; Yang, Yanzheng; Ding, Juhua; Wei, Hua (Ecological Indicators, 2019)

Vegetation restoration stimulates soil carbon sequestration and stabilization in a subtropical area of southern China - Gu, Xiang; Fang, Xi; Xiang, Wenhua; Zeng, Yelin; Zhang, Shiji; Lei, Pifeng; Peng, Changhui; Kuzyakov, Yakov (CATENA, 2019)

Global soil nitrous oxide emissions since the preindustrial era estimated by an ensemble of terrestrial biosphere models: Magnitude, attribution, and uncertainty - Tian, Hanqin; Yang, Jia; Xu, Rongting; Lu, Chaoqun; Canadell, Josep G.; Davidson, Eric A.; Jackson, Robert B.; Arneth, Almut; Chang, Jinfeng; Ciais, Philippe; Gerber, Stefan; Ito, Akihiko; et al. (Global Change Biology, 2019)
Abstract Our understanding and quantification of global soil nitrous oxide (N 2 O) emissions and the underlying processes remain largely uncertain. Here, we assessed the effects of multiple anthropogenic and natural factors, including nitrogen fertilizer (N) application, atmospheric N deposition, manure N application, land cover change, climate change, and rising atmospheric CO 2 concentration, on global soil N 2 O emissions for the period 1861–2016 using a standard simulation protocol with seven process‐based terrestrial biosphere models. Results suggest global soil N 2 O emissions have increased from 6.3 ± 1.1 Tg N 2 O‐N/year in the preindustrial period (the 1860s) to 10.0 ± 2.0 Tg N 2 O‐N/year in the recent decade (2007–2016). Cropland soil emissions increased from 0.3 Tg N 2 O‐N/year to 3.3 Tg N 2 O‐N/year over the same period, accounting for 82% of the total increase. Regionally, China, South Asia, and Southeast Asia underwent rapid increases in cropland N 2 O emissions since the 1970s. However, US cropland N 2 O emissions had been relatively flat in magnitude since the 1980s, and EU cropland N 2 O emissions appear to have decreased by 14%. Soil N 2 O emissions from predominantly natural ecosystems accounted for 67% of the global soil emissions in the recent decade but showed only a relatively small increase of 0.7 ± 0.5 Tg N 2 O‐N/year (11%) since the 1860s. In the recent decade, N fertilizer application, N deposition, manure N application, and climate change contributed 54%, 26%, 15%, and 24%, respectively, to the total increase. Rising atmospheric CO 2 concentration reduced soil N 2 O emissions by 10% through the enhanced plant N uptake, while land cover change played a minor role. Our estimation here does not account for indirect emissions from soils and the directed emissions from excreta of grazing livestock. To address uncertainties in estimating regional and global soil N 2 O emissions, this study recommends several critical strategies for improving the process‐based simulations.

Quantifying leaf‐trait covariation and its controls across climates and biomes - Yang, Yanzheng; Wang, Han; Harrison, Sandy P.; Prentice, I. Colin; Wright, Ian J.; Peng, Changhui; Lin, Guanghui (New Phytologist, 2019)
Summary Plant functional ecology requires the quantification of trait variation and its controls. Field measurements on 483 species at 48 sites across China were used to analyse variation in leaf traits, and assess their predictability. Principal components analysis ( PCA ) was used to characterize trait variation, redundancy analysis ( RDA ) to reveal climate effects, and RDA with variance partitioning to estimate separate and overlapping effects of site, climate, life‐form and family membership. Four orthogonal dimensions of total trait variation were identified: leaf area ( LA ), internal‐to‐ambient CO 2 ratio (χ), leaf economics spectrum traits (specific leaf area ( SLA ) versus leaf dry matter content ( LDMC ) and nitrogen per area ( N area )), and photosynthetic capacities ( V cmax , J max at 25°C). LA and χ covaried with moisture index. Site, climate, life form and family together explained 70% of trait variance. Families accounted for 17%, and climate and families together 29%. LDMC and SLA showed the largest family effects. Independent life‐form effects were small. Climate influences trait variation in part by selection for different life forms and families. Trait values derived from climate data via RDA showed substantial predictive power for trait values in the available global data sets. Systematic trait data collection across all climates and biomes is still necessary.

Spatial and temporal variations of N2O emissions from global forest and grassland ecosystems - Zhang, Kerou; Zhu, Qiuan; Liu, Jinxun; Wang, Meng; Zhou, Xiaolu; Li, Mingxu; Wang, Kefeng; Ding, Juhua; Peng, Changhui (Agricultural and Forest Meteorology, 2019)

Nitrous oxide emissions from soils under traditional cropland and apple orchard in the semi-arid Loess Plateau of China - Pang, Junzhu; Wang, Xiaoke; Peng, Changhui; Mu, Yujing; Ouyang, Zhiyun; Lu, Fei; Zhang, Hongxing; Zhang, Shuoxin; Liu, Wenzhao (Agriculture, Ecosystems & Environment, 2019)

Nitrogen depositions increase soil respiration and decrease temperature sensitivity in a Moso bamboo forest - Li, Quan; Song, Xinzhang; Chang, Scott X.; Peng, Changhui; Xiao, Wenfa; Zhang, Junbo; Xiang, Wenhua; Li, Yan; Wang, Weifeng (Agricultural and Forest Meteorology, 2019)

Land use/cover change in the Three Gorges Reservoir area, China: Reconciling the land use conflicts between development and protection - Huang, Chunbo; Huang, Xin; Peng, Changhui; Zhou, Zhixiang; Teng, Mingjun; Wang, Pengcheng (CATENA, 2019)

Differences of soil CO2 flux in two contrasting subalpine ecosystems on the eastern edge of the Qinghai-Tibetan Plateau: A four-year study - Duan, Min; Li, Andi; Wu, Yanhong; Zhao, Zuoping; Peng, Changhui; DeLuca, Thomas H.; Sun, Shouqin (Atmospheric Environment, 2019)

Comparative analyses of different biogenic CO2 emission accounting systems in life cycle assessment - Liu, Weiguo; Zhu, Qiuan; Zhou, Xiaolu; Peng, Changhui (Science of The Total Environment, 2019)

How is biodiversity changing in response to ecological restoration in terrestrial ecosystems? A meta-analysis in China - Huang, Chunbo; Zhou, Zhixiang; Peng, Changhui; Teng, Mingjun; Wang, Pengcheng (Science of The Total Environment, 2019)

Modeling and estimating aboveground biomass of Dacrydium pierrei in China using machine learning with climate change - Wu, Chunyan; Chen, Yongfu; Peng, Changhui; Li, Zhaochen; Hong, Xiaojiang (Journal of Environmental Management, 2019)

Vegetation Functional Properties Determine Uncertainty of Simulated Ecosystem Productivity: A Traceability Analysis in the East Asian Monsoon Region - Cui, Erqian; Huang, Kun; Arain, Muhammad Altaf; Fisher, Joshua B.; Huntzinger, Deborah N.; Ito, Akihiko; Luo, Yiqi; Jain, Atul K.; Mao, Jiafu; Michalak, Anna M.; Niu, Shuli; Parazoo, Nicholas C.; et al. (Global Biogeochemical Cycles, 2019)
Abstract Global and regional projections of climate change by Earth system models are limited by their uncertain estimates of terrestrial ecosystem productivity. At the middle to low latitudes, the East Asian monsoon region has higher productivity than forests in Europe‐Africa and North America, but its estimate by current generation of terrestrial biosphere models (TBMs) has seldom been systematically evaluated. Here, we developed a traceability framework to evaluate the simulated gross primary productivity (GPP) by 15 TBMs in the East Asian monsoon region. The framework links GPP to net primary productivity, biomass, leaf area and back to GPP via incorporating multiple vegetation functional properties of carbon‐use efficiency (CUE), vegetation C turnover time ( τ veg ), leaf C fraction (F leaf ), specific leaf area (SLA), and leaf area index (LAI)‐level photosynthesis (P LAI ), respectively. We then applied a relative importance algorithm to attribute intermodel variation at each node. The results showed that large intermodel variation in GPP over 1901–2010 were mainly propagated from their different representation of vegetation functional properties. For example, SLA explained 77% of the intermodel difference in leaf area, which contributed 90% to the simulated GPP differences. In addition, the models simulated higher CUE (18.1 ± 21.3%), τ veg (18.2 ± 26.9%), and SLA (27.4±36.5%) than observations, leading to the overestimation of simulated GPP across the East Asian monsoon region. These results suggest the large uncertainty of current TBMs in simulating GPP is largely propagated from their poor representation of the vegetation functional properties and call for a better understanding of the covariations between plant functional properties in terrestrial ecosystems. , Key Points A GPP‐traceability framework is established to diagnose the uncertainty sources of modeled GPP Large intermodel differences of modeled GPP result from their different representation of vegetation functional properties Positive bias in simulated GPP over the East Asian monsoon region could be attributed to the higher simulated CUE and SLA comparing with observations

Land-use changes driven by ‘Grain for Green’ program reduced carbon loss induced by soil erosion on the Loess Plateau of China - Deng, Lei; Kim, Dong-Gill; Li, Miaoyu; Huang, Chunbo; Liu, Qiuyu; Cheng, Min; Shangguan, Zhouping; Peng, Changhui (Global and Planetary Change, 2019)

Does direct-seeded rice decrease ecosystem-scale methane emissions?—A case study from a rice paddy in southeast China - Li, Hong; Guo, Hai-Qiang; Helbig, Manuel; Dai, Sheng-Qi; Zhang, Meng-Shan; Zhao, Min; Peng, Chang-Hui; Xiao, Xiang-Ming; Zhao, Bin (Agricultural and Forest Meteorology, 2019)

The impact of secondary forest restoration on multiple ecosystem services and their trade-offs - Zeng, Yelin; Gou, Mengmeng; Ouyang, Shuai; Chen, Liang; Fang, Xi; Zhao, Lijuan; Li, Jiaxiang; Peng, Changhui; Xiang, Wenhua (Ecological Indicators, 2019)

Drivers of soil microbial metabolic limitation changes along a vegetation restoration gradient on the Loess Plateau, China - Deng, Lei; Peng, Changhui; Huang, Chunbo; Wang, Kaibo; Liu, Qiuyu; Liu, Yulin; Hai, Xuying; Shangguan, Zhouping (Geoderma, 2019)

Immediate and carry-over effects of increased soil frost on soil respiration and microbial activity in a spruce forest - Yang, Kaijun; Peng, Changhui; Peñuelas, Josep; Kardol, Paul; Li, Zhijie; Zhang, Li; Ni, Xiangyin; Yue, Kai; Tan, Bo; Yin, Rui; Xu, Zhenfeng (Soil Biology and Biochemistry, 2019)

Distribution margins as natural laboratories to infer species’ flowering responses to climate warming and implications for frost risk - Guo, Liang; Wang, Jinghong; Li, Mingjun; Liu, Lu; Xu, Jianchu; Cheng, Jimin; Gang, Chengcheng; Yu, Qiang; Chen, Ji; Peng, Changhui; Luedeling, Eike (Agricultural and Forest Meteorology, 2019)

Peatland degradation reduces methanogens and methane emissions from surface to deep soils - Yang, Gang; Tian, Jianqing; Chen, Huai; Jiang, Lin; Zhan, Wei; Hu, Ji; Zhu, Erxiong; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; He, Yixin; Li, Mingxu; et al. (Ecological Indicators, 2019)

Climate changes in the Holocene: impact, adaptation, and resilience - Chiotis, Eustathios (CRC Press, 2019)
Climate change in the current geological era, from approximately 11,000 years ago to the present

Svalbard ice-sheet decay after the Last Glacial Maximum: New insights from micropalaeontological and organic biomarker paleoceanographical reconstructions - Rigual-Hernández, A.S.; Colmenero-Hidalgo, E.; Martrat, B.; Bárcena, M.A.; De Vernal, A.; Sierro, F.J.; Flores, J.A.; Grimalt, J.O.; Henry, M.; Lucchi, R.G. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)

A New Chronology of Late Quaternary Sequences From the Central Arctic Ocean Based on “Extinction Ages” of Their Excesses in^231 Pa and^230 Th - Hillaire‐Marcel, C.; Ghaleb, B.; De Vernal, A.; Maccali, J.; Cuny, K.; Jacobel, A.; Le Duc, C.; McManus, J. (Geochemistry, Geophysics, Geosystems, 2017)
Abstract Merging the late Quaternary Arctic paleoceanography into the Earth's global climate history remains challenging due to the lack of robust marine chronostratigraphies. Over ridges notably, low and variable sedimentation rates, scarce biogenic remains ensuing from low productivity and/or poor preservation, and oxygen isotope and paleomagnetic records differing from global stacks represent major impediments. However, as illustrate here based on consistent records from Mendeleev‐Alpha and Lomonosov Ridges, disequilibria between U‐series isotopes can provide benchmark ages. In such settings, fluxes of the particle‐reactive U‐daughter isotopes 230 Th and 231 Pa from the water column, are not unequivocally linked to sedimentation rates, but rather to sea‐ice rafting and brine production histories, thus to the development of sea‐ice factories over shelves during intervals of high relative sea level. The excesses in 230 Th and 231 Pa over fractions supported by their parent U‐isotopes, collapse down sedimentary sequences, due to radioactive decay, and provide radiometric benchmark ages of approximately 300 and 140 ka, respectively. These “extinction ages” point to mean sedimentation rates of ∼4.3 and ∼1.7 mm/ka, respectively, over the Lomonosov and Mendeleev Ridges, which are significantly lower than assumed in most recent studies, thus highlighting the need for revisiting current interpretations of Arctic lithostratigraphies in relation to the global‐scale late Quaternary climatostratigraphy. , Plain Language Summary The Arctic Ocean represents a major component of the Earth climate system notably with regard to the Arctic amplification and freshwater fluxes toward the global ocean. Understanding its role versus the global climate history of the recent glacial/interglacial cycles remains challenging due to the lack of robust chronology of marine sedimentary archives. In the present study, we demonstrate that the decay of Uranium series isotopes in sediments from major Arctic ridges provide benchmark ages for the last ∼300,000 years and support the concept of a “sediment‐starved” environment in the central Arctic Ocean. , Key Points New chronology of late Quaternary marine sequences from the central Arctic Mean sedimentation rates of the order of millimeters per thousand years over ridges Highly discontinuous ice‐rafted sedimentation over ridges with gaps

Holocene paleoceanography of the Bay of Biscay: Evidence for west-east linkages in the North Atlantic based on dinocyst data - Zumaque, Jena; Eynaud, Frédérique; De Vernal, Anne (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)

New data on the Holocene evolution of the Dvina Bay (White Sea) - Novichkova, Ye. A.; Reikhard, L. Ye.; Lisitzin, A. P.; Rybalko, A. Ye.; De Vernal, A. (Doklady Earth Sciences, 2017)

Comparison of qualitative and quantitative dinoflagellate cyst approaches in reconstructing glacial-interglacial climate variability at West Iberian Margin IODP ‘Shackleton’ Site U1385 - Datema, Mariska; Sangiorgi, Francesca; De Vernal, Anne; Reichart, Gert-Jan; Lourens, Lucas J.; Sluijs, Appy (Marine Micropaleontology, 2017)

Quaternary dinoflagellate cysts in the Arctic Ocean: Potential and limitations for stratigraphy and paleoenvironmental reconstructions - Matthiessen, Jens; Schreck, Michael; De Schepper, Stijn; Zorzi, Coralie; De Vernal, Anne (Quaternary Science Reviews, 2018)

Identification key for Pliocene and Quaternary Spiniferites taxa bearing intergonal processes based on observations from estuarine and coastal environments - Limoges, Audrey; Londeix, Laurent; Mertens, Kenneth Neil; Rochon, André; Pospelova, Vera; Cuéllar, Tomasa; De Vernal, Anne (Palynology, 2018)

Environmental forcing on the flux of organic-walled dinoflagellate cysts in recent sediments from a subtropical lagoon in the Gulf of California - Cuellar-Martinez, Tomasa; Alonso-Rodríguez, Rosalba; Ruiz-Fernández, Ana Carolina; De Vernal, Anne; Morquecho, Lourdes; Limoges, Audrey; Henry, Maryse; Sanchez-Cabeza, Joan-Albert (Science of The Total Environment, 2018)

Paleoceanography of northeastern Fram Strait since the last glacial maximum: Palynological evidence of large amplitude changes - Falardeau, Jade; De Vernal, Anne; Spielhagen, Robert F. (Quaternary Science Reviews, 2018)

Arctic environmental change beyond instrumental records: introduction and overview - Ó Cofaigh, Colm; Kirchner, Nina; Fedorov, Grigory; Noormets, Riko; De Vernal, Anne (arktos, 2018)

Late Holocene Sea Surface Instabilities in the Disko Bugt Area, West Greenland, in Phase With δ^18 O Oscillations at Camp Century - Allan, Estelle; De Vernal, Anne; Knudsen, Mads Faurschou; Hillaire‐Marcel, Claude; Moros, Matthias; Ribeiro, Sofia; Ouellet‐Bernier, Marie‐Michèle; Seidenkrantz, Marit‐Solveig (Paleoceanography and Paleoclimatology, 2018)
Abstract Palynological analyses of sediment core MSM343310 from Disko Bugt (68°38′861°N, 53°49′493°W) document decadal‐ to centennial‐scale variability of sea surface conditions during the last ~ 3,600 years. Dinocyst fluxes (>10 4 cysts/cm 2 yr −1 ) indicate a very high productivity. Dinocyst assemblages dominated by Islandinium minutum , Brigantedinium spp., Islandinium ? cezare , and the cyst of Pentapharsodinium dalei suggest low surface salinity and marked shifts in summer sea surface temperature. The application of the modern analog technique to dinocyst assemblages, using an updated reference data set with new sites from the West Greenland margin, led to reconstruct decadal‐centennial‐scale variations in sea surface salinity and temperature, in phase with the δ 18 O variations in the Camp Century ice core. At ~ 1.5 ka BP, the seasonal sea ice cover records an important regime change, from winter‐only sea ice to more unstable conditions marked by successive cooling pulses with sea ice cover of up to 8 months/yr. The data suggest a close relationship between hydrographic conditions and regional climate over Greenland. Our record shows variations with a mean 200 years periodicity until ~2 ka BP, which supports the hypothesis of climate variations driven by solar variability. After 1.5 ka BP, our data show a variability characterized by a 60–70 year periodicity, which suggests linkages with the Atlantic Multidecadal Oscillation and southwestward migration of the atmospheric polar front. The most recent part of the record, from ~1900 CE to 2007 CE, is characterized by assemblages reflecting warmer surface conditions and reduced sea ice cover. , Key Points Sea surface salinity changes are used as indicators of fresh‐meltwater events and sea ice cover as a diagnostic feature of regional climate Changing sea surface conditions from Disko Bugt are closely related with regional climate over Greenland A marked change in surface waters at about 1.5 ka BP corresponds to enhanced sea ice cover and the onset of unstable conditions

The dinoflagellate cyst genera Achomosphaera Evitt 1963 and Spiniferites Mantell 1850 in Pliocene to modern sediments: a summary of round table discussions - Mertens, Kenneth Neil; Van Nieuwenhove, Nicolas; Gurdebeke, Pieter R.; Aydin, Hilal; Bogus, Kara; Bringué, Manuel; Dale, Barrie; De Schepper, Stijn; De Vernal, Anne; Ellegaard, Marianne; Grothe, Arjen; Gu, Haifeng; et al. (Palynology, 2018)

Distribution and (palaeo)ecological affinities of the main Spiniferites taxa in the mid-high latitudes of the Northern Hemisphere - De Vernal, Anne; Eynaud, Frédérique; Henry, Maryse; Limoges, Audrey; Londeix, Laurent; Matthiessen, Jens; Marret, Fabienne; Pospelova, Vera; Radi, Taoufik; Rochon, André; Van Nieuwenhove, Nicolas; Zaragosi, Sébastien (Palynology, 2018)

Palaeoclimate constraints on the impact of 2 °C anthropogenic warming and beyond - Fischer, Hubertus; Meissner, Katrin J.; Mix, Alan C.; Abram, Nerilie J.; Austermann, Jacqueline; Brovkin, Victor; Capron, Emilie; Colombaroli, Daniele; Daniau, Anne-Laure; Dyez, Kelsey A.; Felis, Thomas; Finkelstein, Sarah A.; et al. (Nature Geoscience, 2018)

Postglacial paleoceanography and paleoenvironments in the northwestern Barents Sea - Ivanova, Elena; Murdmaa, Ivar; De Vernal, Anne; Risebrobakken, Bjørg; Peyve, Alexander; Brice, Camille; Seitkalieva, Elvira; Pisarev, Sergey (Quaternary Research, 2019)
Abstract The Barents Sea offers a suitable location for documenting advection of warm and saline Atlantic Water (AW) into the Arctic and its impact on deglaciation and postglacial conditions. We investigate the timing, succession, and mechanisms of the transition from proximal glaciomarine to marine environment in the northwestern Barents Sea. Two studied sediment cores demonstrate diachronous retreat of the grounded ice sheet from the Kvitøya Trough (core S2528) to Erik Eriksen Trough (core S2519). Oxygen isotope records from core S2528 depict a two-step pattern, with lower δ 18 O values prior to the Younger Dryas (YD), and higher values afterward because of advection of the more saline, 18 O-enriched AW. At this location, subsurface AW penetration increased during the Allerød and YD/Preboreal transition. In the study area, foraminiferal and dinocyst data from the YD interval suggest cold conditions, extensive sea-ice cover, and brine formation, along with the flow of chilled AW at subsurface and the development of a high-productivity polynya in the Erik Eriksen Trough. Dense winter sea-ice cover with seasonal productivity persisted in the Kvitøya Trough area during the early Holocene, whereas surface warming seems to have occurred during the middle Holocene interval.

Millennial‐Scale Climate Variability and Dinoflagellate‐Cyst‐Based Seasonality Changes Over the Last ~150 kyrs at “Shackleton Site” U1385 - Datema, Mariska; Sangiorgi, Francesca; De Vernal, Anne; Reichart, Gert‐Jan; Lourens, Lucas J.; Sluijs, Appy (Paleoceanography and Paleoclimatology, 2019)
Abstract During the last glacial period, climate conditions in the North Atlantic region were determined by the alternation of relatively warm interstadials and relatively cool stadials, with superimposed rapid warming (Dansgaard‐Oeschger) and cooling (Heinrich) events. So far little is known about the impact of these rapid climate shifts on the seasonal variations in sea surface temperature (SST) within the North Atlantic region. Here, we present a high‐resolution seasonal SST record for the past 152 kyrs derived from Integrated Ocean Drilling Program “Shackleton” Site U1385, offshore Portugal. Assemblage counts of dinoflagellates cysts (dinocysts) in combination with a modern analog technique (MAT), and regression analyses were used for the reconstructions. We compare our records with previously published SST records from the same location obtained from the application of MAT on planktonic foraminifera. Our dinocyst‐based reconstructions confirm the impression of the Greenland stadials and interstadials offshore the Portuguese margin and indicate increased seasonal contrast of temperature during the cold periods of the glacial cycle (average 9.0 °C, maximum 12.2 °C) with respect to present day (5.1 °C), due to strong winter cooling by up to 8.3 °C. Our seasonal temperature reconstructions are in line with previously published data, which showed increased seasonality due to strong winter cooling during the Younger Dryas and the Last Glacial Maximum over the European continent and North Atlantic region. In addition, we show that over longer time scales, increased seasonal contrasts of temperature remained characteristic of the colder phases of the glacial cycle. , Key Points New high‐resolution dinocyst‐based summer and winter SST record from IODP “Shackleton” Site U1385 for the last 150 kyrs is presented Dinocyst‐based SST confirms the D‐O cycles and HEs at Site U1385 Increased seasonal contrast of SST (up to 12 degree C) during cold periods of the glacial cycle related to strong winter cooling is shown

Challenges and research priorities to understand interactions between climate, ice sheets and global mean sea level during past interglacials - Capron, Emilie; Rovere, Alessio; Austermann, Jacqueline; Axford, Yarrow; Barlow, Natasha L.M.; Carlson, Anders E.; De Vernal, Anne; Dutton, Andrea; Kopp, Robert E.; McManus, Jerry F.; Menviel, Laurie; Otto-Bliesner, Bette L.; et al. (Quaternary Science Reviews, 2019)

Impagidinium detroitense and I.? diaphanum: Two new dinoflagellate cyst species from the Pliocene of the North Pacific Ocean, and their biostratigraphic significance - Zorzi, Coralie; Head, Martin J.; Matthiessen, Jens; De Vernal, Anne (Review of Palaeobotany and Palynology, 2019)

Holocene trends in the foraminifer record from the Norwegian Sea and the North Atlantic Ocean - Andersson, C.; Pausata, F. S. R.; Jansen, E.; Risebrobakken, B.; Telford, R. J. (Climate of the Past, 2010)
Abstract. The early to mid-Holocene thermal optimum is a well-known feature in a wide variety of paleoclimate archives from the Northern Hemisphere. Reconstructed summer temperature anomalies from across northern Europe show a clear maximum around 6000 years before present (6 ka). For the marine realm, Holocene trends in sea-surface temperature reconstructions for the North Atlantic and Norwegian Sea do not exhibit a consistent pattern of early to mid-Holocene warmth. Sea-surface temperature records based on alkenones and diatoms generally show the existence of a warm early to mid-Holocene optimum. In contrast, several foraminifer and radiolarian based temperature records from the North Atlantic and Norwegian Sea show a cool mid-Holocene anomaly and a trend towards warmer temperatures in the late Holocene. In this paper, we revisit the foraminifer record from the Vøring Plateau in the Norwegian Sea. We also compare this record with published foraminifer based temperature reconstructions from the North Atlantic and with modelled (CCSM3) upper ocean temperatures. Model results indicate that while the seasonal summer warming of the sea-surface was stronger during the mid-Holocene, sub-surface depths experienced a cooling. This hydrographic setting can explain the discrepancies between the Holocene trends exhibited by phytoplankton and zooplankton based temperature proxy records.

Catastrophic Drought in the Afro-Asian Monsoon Region During Heinrich Event 1 - Stager, J. Curt; Ryves, David B.; Chase, Brian M.; Pausata, Francesco S. R. (Science, 2011)
An extreme megadrought occurred in the Afro-Asian monsoon region during an iceberg melting episode 50,000 years ago. , Between 15,000 and 18,000 years ago, large amounts of ice and meltwater entered the North Atlantic during Heinrich stadial 1. This caused substantial regional cooling, but major climatic impacts also occurred in the tropics. Here, we demonstrate that the height of this stadial, about 16,000 to 17,000 years ago (Heinrich event 1), coincided with one of the most extreme and widespread megadroughts of the past 50,000 years or more in the Afro-Asian monsoon region, with potentially serious consequences for Paleolithic cultures. Late Quaternary tropical drying commonly is attributed to southward drift of the intertropical convergence zone, but the broad geographic range of the Heinrich event 1 megadrought suggests that severe, systemic weakening of Afro-Asian rainfall systems also occurred, probably in response to sea surface cooling.

Chinese stalagmite δ18O controlled by changes in the Indian monsoon during a simulated Heinrich event - Pausata, Francesco S. R.; Battisti, David S.; Nisancioglu, Kerim H.; Bitz, Cecilia M. (Nature Geoscience, 2011)

The key role of topography in altering North Atlantic atmospheric circulation during the last glacial period - Pausata, F. S. R.; Li, C.; Wettstein, J. J.; Kageyama, M.; Nisancioglu, K. H. (Climate of the Past, 2011)
Abstract. The Last Glacial Maximum (LGM; 21 000 yr before present) was a period of low atmospheric greenhouse gas concentrations, when vast ice sheets covered large parts of North America and Europe. Paleoclimate reconstructions and modeling studies suggest that the atmospheric circulation was substantially altered compared to today, both in terms of its mean state and its variability. Here we present a suite of coupled model simulations designed to investigate both the separate and combined influences of the main LGM boundary condition changes (greenhouse gases, ice sheet topography and ice sheet albedo) on the mean state and variability of the atmospheric circulation as represented by sea level pressure (SLP) and 200-hPa zonal wind in the North Atlantic sector. We find that ice sheet topography accounts for most of the simulated changes during the LGM. Greenhouse gases and ice sheet albedo affect the SLP gradient in the North Atlantic, but the overall placement of high and low pressure centers is controlled by topography. Additional analysis shows that North Atlantic sea surface temperatures and sea ice edge position do not substantially influence the pattern of the climatological-mean SLP field, SLP variability or the position of the North Atlantic jet in the LGM.

North Atlantic Oscillation and tropospheric ozone variability in Europe: model analysis and measurements intercomparison - Pausata, F. S. R.; Pozzoli, L.; Vignati, E.; Dentener, F. J. (Atmospheric Chemistry and Physics, 2012)
Abstract. Ozone pollution represents a serious health and environmental problem. While ozone pollution is mostly produced by photochemistry in summer, elevated ozone concentrations can also be influenced by long range transport driven by the atmospheric circulation and stratospheric ozone intrusions. We analyze the role of large scale atmospheric circulation variability in the North Atlantic basin in determining surface ozone concentrations over Europe. Here, we show, using ground station measurements and a coupled atmosphere-chemistry model simulation for the period 1980–2005, that the North Atlantic Oscillation (NAO) does affect surface ozone concentrations – on a monthly timescale, over 10 ppbv in southwestern, central and northern Europe – during all seasons except fall. The commonly used NAO index is able to capture the link existing between atmospheric dynamics and surface ozone concentrations in winter and spring but it fails in summer. We find that the first Principal Component, computed from the time variation of the sea level pressure (SLP) field, detects the atmosphere circulation/ozone relationship not only in winter and spring but also during summer, when the atmospheric circulation weakens and regional photochemical processes peak. Given the NAO forecasting skill at intraseasonal time scale, the first Principal Component of the SLP field could be used as an indicator to identify areas more exposed to forthcoming ozone pollution events. Finally, our results suggest that the increasing baseline ozone in western and northern Europe during the 1990s could be related to the prevailing positive phase of the NAO in that period.

Impacts of changes in North Atlantic atmospheric circulation on particulate matter and human health in Europe - R. Pausata, Francesco S.; Pozzoli, Luca; Dingenen, Rita Van; Vignati, Elisabetta; Cavalli, Fabrizia; Dentener, Frank J. (Geophysical Research Letters, 2013)
In this study we use a global climate model to assess particulate matter (PM) variability induced by the North Atlantic Oscillation (NAO) in Europe during winter and the potential impact on human health of a future shift in the NAO mean state. Our study shows that extreme NAO phases in the 1990s modulated most of the interannual variability of winter PM concentrations in several European countries. Increased PM concentrations as a result of a positive shift in the mean winter NAO of one standard deviation would lead to about 5500 additional premature deaths in Mediterranean countries, compared to the simulated average PM health impact for the year 2000. In central‐northern Europe, instead, higher wind speed and increased PM removal by precipitation lead to negative PM concentration anomalies with associated health benefits. We suggest that the NAO index is a useful indicator for the role of interannual atmospheric variability on large‐scale pollution‐health impacts. , Key Points NAO impacts on PM concentrations Potential impacts of NAO shifts on human health Large‐scale atmospheric indicators as proxy for risk estimates of PM episodes

The role of aerosol in altering North Atlantic atmospheric circulation in winter and its impact on air quality - Pausata, F. S. R.; Gaetani, M.; Messori, G.; Kloster, S.; Dentener, F. J. (Atmospheric Chemistry and Physics, 2015)
Abstract. Numerical model scenarios of future climate depict a global increase in temperatures and changing precipitation patterns, primarily driven by increasing greenhouse gas (GHG) concentrations. Aerosol particles also play an important role by altering the Earth's radiation budget and consequently surface temperature. Here, we use the general circulation aerosol model ECHAM5-HAM, coupled to a mixed layer ocean model, to investigate the impacts of future air pollution mitigation strategies in Europe on winter atmospheric circulation over the North Atlantic. We analyse the extreme case of a maximum feasible end-of-pipe reduction of aerosols in the near future (2030), in combination with increasing GHG concentrations. Our results show a more positive North Atlantic Oscillation (NAO) mean state by 2030, together with a significant eastward shift of the southern centre of action of sea-level pressure (SLP). Moreover, we show a significantly increased blocking frequency over the western Mediterranean. By separating the impacts of aerosols and GHGs, our study suggests that future aerosol abatement may be the primary driver of both the eastward shift in the southern SLP centre of action and the increased blocking frequency over the western Mediterranean. These concomitant modifications of the atmospheric circulation over the Euro-Atlantic sector lead to more stagnant weather conditions that favour air pollutant accumulation, especially in the western Mediterranean sector. Changes in atmospheric circulation should therefore be included in future air pollution mitigation assessments. The indicator-based evaluation of atmospheric circulation changes presented in this work will allow an objective first-order assessment of the role of changes in wintertime circulation on future air quality in other climate model simulations.

Late-glacial to late-Holocene shifts in global precipitation δ18O - Jasechko, S.; Lechler, A.; Pausata, F. S. R.; Fawcett, P. J.; Gleeson, T.; Cendón, D. I.; Galewsky, J.; LeGrande, A. N.; Risi, C.; Sharp, Z. D.; Welker, J. M.; Werner, M.; et al. (Climate of the Past, 2015)
Abstract. Reconstructions of Quaternary climate are often based on the isotopic content of paleo-precipitation preserved in proxy records. While many paleo-precipitation isotope records are available, few studies have synthesized these dispersed records to explore spatial patterns of late-glacial precipitation δ18O. Here we present a synthesis of 86 globally distributed groundwater (n = 59), cave calcite (n = 15) and ice core (n = 12) isotope records spanning the late-glacial (defined as ~ 50 000 to ~ 20 000 years ago) to the late-Holocene (within the past ~ 5000 years). We show that precipitation δ18O changes from the late-glacial to the late-Holocene range from −7.1 ‰ (δ18Olate-Holocene > δ18Olate-glacial) to +1.7 ‰ (δ18Olate-glacial > δ18Olate-Holocene), with the majority (77 %) of records having lower late-glacial δ18O than late-Holocene δ18O values. High-magnitude, negative precipitation δ18O shifts are common at high latitudes, high altitudes and continental interiors (δ18Olate-Holocene > δ18Olate-glacial by more than 3 ‰). Conversely, low-magnitude, positive precipitation δ18O shifts are concentrated along tropical and subtropical coasts (δ18Olate-glacial > δ18Olate-Holocene by less than 2 ‰). Broad, global patterns of late-glacial to late-Holocene precipitation δ18O shifts suggest that stronger-than-modern isotopic distillation of air masses prevailed during the late-glacial, likely impacted by larger global temperature differences between the tropics and the poles. Further, to test how well general circulation models reproduce global precipitation δ18O shifts, we compiled simulated precipitation δ18O shifts from five isotope-enabled general circulation models simulated under recent and last glacial maximum climate states. Climate simulations generally show better inter-model and model-measurement agreement in temperate regions than in the tropics, highlighting a need for further research to better understand how inter-model spread in convective rainout, seawater δ18O and glacial topography parameterizations impact simulated precipitation δ18O. Future research on paleo-precipitation δ18O records can use the global maps of measured and simulated late-glacial precipitation isotope compositions to target and prioritize field sites.

Impacts of high-latitude volcanic eruptions on ENSO and AMOC - Pausata, Francesco S. R.; Chafik, Leon; Caballero, Rodrigo; Battisti, David S. (Proceedings of the National Academy of Sciences, 2015)
Significance In the model simulations analyzed here, large high-latitude volcanic eruptions have global and long-lasting effects on climate, altering the spatiotemporal characteristic of the El Niño–Southern Oscillation (ENSO) on both short (<1 y) and long timescales and affecting the strength of the Atlantic Meridional Overturning Circulation (AMOC). In the first 8–9 mo following the start of the eruption, El Niño-like anomalies develop over the equatorial Pacific. The large high-latitude eruptions also trigger a strengthening of the AMOC in the first 25 y after the eruption, which is associated with an increase in ENSO variability. This is then followed by a weakening of the AMOC lasting another 30–35 y, associated with decreased ENSO variability. , Large volcanic eruptions can have major impacts on global climate, affecting both atmospheric and ocean circulation through changes in atmospheric chemical composition and optical properties. The residence time of volcanic aerosol from strong eruptions is roughly 2–3 y. Attention has consequently focused on their short-term impacts, whereas the long-term, ocean-mediated response has not been well studied. Most studies have focused on tropical eruptions; high-latitude eruptions have drawn less attention because their impacts are thought to be merely hemispheric rather than global. No study to date has investigated the long-term effects of high-latitude eruptions. Here, we use a climate model to show that large summer high-latitude eruptions in the Northern Hemisphere cause strong hemispheric cooling, which could induce an El Niño-like anomaly, in the equatorial Pacific during the first 8–9 mo after the start of the eruption. The hemispherically asymmetric cooling shifts the Intertropical Convergence Zone southward, triggering a weakening of the trade winds over the western and central equatorial Pacific that favors the development of an El Niño-like anomaly. In the model used here, the specified high-latitude eruption also leads to a strengthening of the Atlantic Meridional Overturning Circulation (AMOC) in the first 25 y after the eruption, followed by a weakening lasting at least 35 y. The long-lived changes in the AMOC strength also alter the variability of the El Niño–Southern Oscillation (ENSO).

Fennoscandian freshwater control on Greenland hydroclimate shifts at the onset of the Younger Dryas - Muschitiello, Francesco; Pausata, Francesco S. R.; Watson, Jenny E.; Smittenberg, Rienk H.; Salih, Abubakr A. M.; Brooks, Stephen J.; Whitehouse, Nicola J.; Karlatou-Charalampopoulou, Artemis; Wohlfarth, Barbara (Nature Communications, 2015)
Abstract Sources and timing of freshwater forcing relative to hydroclimate shifts recorded in Greenland ice cores at the onset of Younger Dryas, ∼12,800 years ago, remain speculative. Here we show that progressive Fennoscandian Ice Sheet (FIS) melting 13,100–12,880 years ago generates a hydroclimate dipole with drier–colder conditions in Northern Europe and wetter–warmer conditions in Greenland. FIS melting culminates 12,880 years ago synchronously with the start of Greenland Stadial 1 and a large-scale hydroclimate transition lasting ∼180 years. Transient climate model simulations forced with FIS freshwater reproduce the initial hydroclimate dipole through sea-ice feedbacks in the Nordic Seas. The transition is attributed to the export of excess sea ice to the subpolar North Atlantic and a subsequent southward shift of the westerly winds. We suggest that North Atlantic hydroclimate sensitivity to FIS freshwater can explain the pace and sign of shifts recorded in Greenland at the climate transition into the Younger Dryas.

On the enigmatic similarity in Greenland δ^18 O between the Oldest and Younger Dryas - Pausata, Francesco S. R.; Löfverström, Marcus (Geophysical Research Letters, 2015)
Abstract The last deglaciation (20.0–10.0 kyr B.P.) was punctuated by two major cooling events affecting the Northern Hemisphere: the Oldest Dryas (OD; 18.0–14.7 kyr B.P.) and the Younger Dryas (YD; 12.8–11.5 kyr B.P.). Greenland ice core δ 18 O temperature reconstructions suggest that the YD was as cold as the OD, despite a 50 ppmv increase in atmospheric CO 2 , while modeling studies suggest that the YD was approximately 4–5°C warmer than the OD. This discrepancy has been surmised to result from changes in the origin of the water vapor delivered to Greenland; however, this hypothesis has not been hitherto tested. Here we use an atmospheric circulation model with an embedded moisture‐tracing module to investigate atmospheric processes that may have been responsible for the similar δ 18 O values during the OD and YD. Our results show that the summer‐to‐winter precipitation ratio over central Greenland in the OD is twice as high as in the YD experiment, which shifts the δ 18 O signal toward warmer (summer) temperatures (enriched δ 18 O values and it accounts for ~45% of the expected YD‐OD δ 18 O difference). A change in the inversion (cloud) temperature relationship between the two climate states further contributes (~20%) to altering the δ 18 O‐temperature‐relation model. Our experiments also show a 7% decrease of δ 18 O‐depleted precipitation from distant regions (e.g., the Pacific Ocean) in the OD, hence further contributing (15–20%) in masking the actual temperature difference. All together, these changes provide a physical explanation for the ostensible similarity in the ice core δ 18 O temperature reconstructions in Greenland during OD and YD. , Key Points Precipitation seasonality and inversion temperature changes behind YD‐OD δ 18 O enigma Local processes changes accounting up to 65% of the expected YD‐OD δ 18 O difference Moisture transport changes from the Pacific accounting only up to 20% of the expected YD‐OD δ 18 O difference

Deglacial Indian monsoon failure and North Atlantic stadials linked by Indian Ocean surface cooling - Tierney, Jessica E.; Pausata, Francesco S. R.; deMenocal, Peter (Nature Geoscience, 2016)

Impacts of dust reduction on the northward expansion of the African monsoon during the Green Sahara period - Pausata, Francesco S.R.; Messori, Gabriele; Zhang, Qiong (Earth and Planetary Science Letters, 2016)

Sources of Sahelian‐Sudan moisture: Insights from a moisture‐tracing atmospheric model - Salih, Abubakr A. M.; Zhang, Qiong; Pausata, Francesco S. R.; Tjernström, Michael (Journal of Geophysical Research: Atmospheres, 2016)
Abstract The summer rainfall across Sahelian‐Sudan is one of the main sources of water for agriculture, human, and animal needs. However, the rainfall is characterized by large interannual variability, which has attracted extensive scientific efforts to understand it. This study attempts to identify the source regions that contribute to the Sahelian‐Sudan moisture budget during July through September. We have used an atmospheric general circulation model with an embedded moisture‐tracing module (Community Atmosphere Model version 3), forced by observed (1979–2013) sea‐surface temperatures. The result suggests that about 40% of the moisture comes with the moisture flow associated with the seasonal migration of the Intertropical Convergence Zone (ITCZ) and originates from Guinea Coast, central Africa, and the Western Sahel. The Mediterranean Sea, Arabian Peninsula, and South Indian Ocean regions account for 10.2%, 8.1%, and 6.4%, respectively. Local evaporation and the rest of the globe supply the region with 20.3% and 13.2%, respectively. We also compared the result from this study to a previous analysis that used the Lagrangian model FLEXPART forced by ERA‐Interim. The two approaches differ when comparing individual regions, but are in better agreement when neighboring regions of similar atmospheric flow features are grouped together. Interannual variability with the rainfall over the region is highly correlated with contributions from regions that are associated with the ITCZ movement, which is in turn linked to the Atlantic Multidecadal Oscillation. Our result is expected to provide insights for the effort on seasonal forecasting of the rainy season over Sahelian Sudan. , Key Points The moisture associated with ITCZ flow accounts for about 40%‐50% of the precipitated water The local evaporation provides about 20% of the precipitated water The multiyear variability in the rainfall seems to be linked to the AMO

ENSO response to high‐latitude volcanic eruptions in the Northern Hemisphere: The role of the initial conditions - Pausata, Francesco S. R.; Karamperidou, Christina; Caballero, Rodrigo; Battisti, David S. (Geophysical Research Letters, 2016)
Abstract A large ensemble of Earth System Model simulations is analyzed to show that high‐latitude Northern Hemisphere eruptions give rise to El Niño‐like anomalies in the winter following the eruption, the amplitude of which depends on the state of the tropical Pacific at the time of the eruption. The El Niño‐like anomalies are almost three times larger when the eruption occurs during an incipient La Niña or during a neutral state compared to an incipient El Niño. The differential response results from stronger atmosphere‐ocean coupling and extra‐tropical feedbacks during an incipient La Niña compared to El Niño. Differences in the response continue through the second and third years following the eruption. When the eruption happens in a year of an incipient El Niño, a large cold (La Niña‐like) anomaly develops in year 2; if the eruption occurs in a year of an incipient La Niña, no anomalies are simulated in year 2 and a La Niña‐like response appears in year 3. After the El Niño‐like anomaly in the first winter, the overall tendency of ENSO in the following 2 years is toward a La Niña state. Our results highlight the high sensitivity of tropical Pacific dynamics under volcanic forcing to the ENSO initial state and lay the groundwork for improved predictions of the global climatic response to high‐latitude volcanic eruptions. , Key Points HL eruptions alter the mean state of ENSO, and detectable anomalies are seen up to 3 years after the eruption Stronger El Niño‐like anomalies on year 1 when eruptions occurs under developing La Niñas La Niña‐like anomalies on year 2 and year 3 when eruptions occurs under developing El Niños and La Niñas, respectively

The Model Intercomparison Project on the climatic response toVolcanic forcing (VolMIP): experimental design and forcing input data for CMIP6 - Zanchettin, Davide; Khodri, Myriam; Timmreck, Claudia; Toohey, Matthew; Schmidt, Anja; Gerber, Edwin P.; Hegerl, Gabriele; Robock, Alan; Pausata, Francesco S. R.; Ball, William T.; Bauer, Susanne E.; Bekki, Slimane; et al. (Geoscientific Model Development, 2016)
Abstract. The enhancement of the stratospheric aerosol layer by volcanic eruptions induces a complex set of responses causing global and regional climate effects on a broad range of timescales. Uncertainties exist regarding the climatic response to strong volcanic forcing identified in coupled climate simulations that contributed to the fifth phase of the Coupled Model Intercomparison Project (CMIP5). In order to better understand the sources of these model diversities, the Model Intercomparison Project on the climatic response to Volcanic forcing (VolMIP) has defined a coordinated set of idealized volcanic perturbation experiments to be carried out in alignment with the CMIP6 protocol. VolMIP provides a common stratospheric aerosol data set for each experiment to minimize differences in the applied volcanic forcing. It defines a set of initial conditions to assess how internal climate variability contributes to determining the response. VolMIP will assess to what extent volcanically forced responses of the coupled ocean–atmosphere system are robustly simulated by state-of-the-art coupled climate models and identify the causes that limit robust simulated behavior, especially differences in the treatment of physical processes. This paper illustrates the design of the idealized volcanic perturbation experiments in the VolMIP protocol and describes the common aerosol forcing input data sets to be used.

Climate effects of a hypothetical regional nuclear war: Sensitivity to emission duration and particle composition - Pausata, Francesco S. R.; Lindvall, Jenny; Ekman, Annica M. L.; Svensson, Gunilla (Earth's Future, 2016)
Abstract Here, we use a coupled atmospheric‐ocean‐aerosol model to investigate the plume development and climate effects of the smoke generated by fires following a regional nuclear war between emerging third‐world nuclear powers. We simulate a standard scenario where 5 Tg of black carbon ( BC ) is emitted over 1 day in the upper troposphere–lower stratosphere. However, it is likely that the emissions from the fires ignited by bomb detonations include a substantial amount of particulate organic matter ( POM ) and that they last more than 1 day. We therefore test the sensitivity of the aerosol plume and climate system to the BC / POM ratio (1:3, 1:9) and to the emission length (1 day, 1 week, 1 month). We find that in general, an emission length of 1 month substantially reduces the cooling compared to the 1‐day case, whereas taking into account POM emissions notably increases the cooling and the reduction of precipitation associated with the nuclear war during the first year following the detonation. Accounting for POM emissions increases the particle size in the short‐emission‐length scenarios (1 day/1 week), reducing the residence time of the injected particle. While the initial cooling is more intense when including POM emission, the long‐lasting effects, while still large, may be less extreme compared to the BC ‐only case. Our study highlights that the emission altitude reached by the plume is sensitive to both the particle type emitted by the fires and the emission duration. Consequently, the climate effects of a nuclear war are strongly dependent on these parameters. , Key Points Importance of including OC when simulating nuclear wars Importance of the fire emission length when simulating nuclear wars

Rainfall regimes of the Green Sahara - Tierney, Jessica E.; Pausata, Francesco S. R.; deMenocal, Peter B. (Science Advances, 2017)
We estimate rainfall during the “Green Sahara” period. , During the “Green Sahara” period (11,000 to 5000 years before the present), the Sahara desert received high amounts of rainfall, supporting diverse vegetation, permanent lakes, and human populations. Our knowledge of rainfall rates and the spatiotemporal extent of wet conditions has suffered from a lack of continuous sedimentary records. We present a quantitative reconstruction of western Saharan precipitation derived from leaf wax isotopes in marine sediments. Our data indicate that the Green Sahara extended to 31°N and likely ended abruptly. We find evidence for a prolonged “pause” in Green Sahara conditions 8000 years ago, coincident with a temporary abandonment of occupational sites by Neolithic humans. The rainfall rates inferred from our data are best explained by strong vegetation and dust feedbacks; without these mechanisms, climate models systematically fail to reproduce the Green Sahara. This study suggests that accurate simulations of future climate change in the Sahara and Sahel will require improvements in our ability to simulate vegetation and dust feedbacks.

On the links between meteorological variables, aerosols, and tropical cyclone frequency in individual ocean basins - Chiacchio, Marc; Pausata, Francesco S. R.; Messori, Gabriele; Hannachi, Abdel; Chin, Mian; Önskog, Thomas; Ekman, Annica M. L.; Barrie, Leonard (Journal of Geophysical Research: Atmospheres, 2017)
Abstract A generalized linear model based on Poisson regression has been used to assess the impact of environmental variables modulating tropical cyclone frequency in six main cyclone development areas: the East Pacific, West Pacific, North Atlantic, North Indian, South Indian, and South Pacific. The analysis covers the period 1980–2009 and focuses on widely used meteorological parameters including wind shear, sea surface temperature, and relative humidity from different reanalyses as well as aerosol optical depth for different compounds simulated by the Goddard Chemistry Aerosol Radiation and Transport model. Circulation indices are also included. Cyclone frequency is obtained from the International Best Track Archive for Climate Stewardship. A strong link is found between cyclone frequency and the relative sea surface temperature, Atlantic Meridional Mode, and wind shear with significant explained log likelihoods in the North Atlantic of 37%, 27%, and 28%, respectively. A significant impact of black carbon and organic aerosols on cyclone frequency is found over the North Indian Ocean, with explained log likelihoods of 27%. A weaker but still significant impact is found for observed dust aerosols in the North Atlantic with an explained log likelihood of 11%. Changes in lower stratospheric temperatures explain 28% of the log likelihood in the North Atlantic. Lower stratospheric temperatures from a subset of Coupled Model Intercomparison Project Phase 5 models properly simulate the warming and subsequent cooling of the lower stratosphere that follows a volcanic eruption but underestimates the cooling by about 0.5°C. , Key Points Significant impact of black carbon and organic aerosols Significant impact of observed dust aerosols in the North Atlantic Lower stratospheric temperatures explain 28% of the log likelihood

Future Response of Temperature and Precipitation to Reduced Aerosol Emissions as Compared with Increased Greenhouse Gas Concentrations - Acosta Navarro, Juan C.; Ekman, Annica M. L.; Pausata, Francesco S. R.; Lewinschal, Anna; Varma, Vidya; Seland, Øyvind; Gauss, Michael; Iversen, Trond; Kirkevåg, Alf; Riipinen, Ilona; Hansson, Hans Christen (Journal of Climate, 2017)
Abstract Experiments with a climate model (NorESM1) were performed to isolate the effects of aerosol particles and greenhouse gases on surface temperature and precipitation in simulations of future climate. The simulations show that by 2025–49 a reduction of aerosol emissions from fossil fuels following a maximum technically feasible reduction (MFR) scenario could lead to a global and Arctic warming of 0.26 and 0.84 K, respectively, as compared with a simulation with fixed aerosol emissions at the level of 2005. If fossil fuel emissions of aerosols follow a current legislation emissions (CLE) scenario, the NorESM1 model simulations yield a nonsignificant change in global and Arctic average surface temperature as compared with aerosol emissions fixed at year 2005. The corresponding greenhouse gas effect following the representative concentration pathway 4.5 (RCP4.5) emission scenario leads to a global and Arctic warming of 0.35 and 0.94 K, respectively. The model yields a marked annual average northward shift in the intertropical convergence zone with decreasing aerosol emissions and subsequent warming of the Northern Hemisphere. The shift is most pronounced in the MFR scenario but also visible in the CLE scenario. The modeled temperature response to a change in greenhouse gas concentrations is relatively symmetric between the hemispheres, and there is no marked shift in the annual average position of the intertropical convergence zone. The strong reduction in aerosol emissions in the MFR scenario also leads to a net southward cross-hemispheric energy transport anomaly both in the atmosphere and ocean, and enhanced monsoon circulation in Southeast Asia and East Asia causing an increase in precipitation over a large part of this region.

Tropical cyclone activity enhanced by Sahara greening and reduced dust emissions during the African Humid Period - Pausata, Francesco S. R.; Emanuel, Kerry A.; Chiacchio, Marc; Diro, Gulilat T.; Zhang, Qiong; Sushama, Laxmi; Stager, J. Curt; Donnelly, Jeffrey P. (Proceedings of the National Academy of Sciences, 2017)
Significance Our modeling study shows the crucial role of vegetation cover over the Sahara and reduced dust emission in altering tropical cyclone activity during the mid-Holocene (6,000 yBP). Our results also demonstrate how these regional changes in land cover and dust emission are able to affect areas far afield through changes of large-scale atmospheric circulation. Our study strongly suggests that an appropriate representation of land cover and dust emission is of paramount importance to be able to capture past—and potentially future—climate changes. , Tropical cyclones (TCs) can have devastating socioeconomic impacts. Understanding the nature and causes of their variability is of paramount importance for society. However, historical records of TCs are too short to fully characterize such changes and paleo-sediment archives of Holocene TC activity are temporally and geographically sparse. Thus, it is of interest to apply physical modeling to understanding TC variability under different climate conditions. Here we investigate global TC activity during a warm climate state (mid-Holocene, 6,000 yBP) characterized by increased boreal summer insolation, a vegetated Sahara, and reduced dust emissions. We analyze a set of sensitivity experiments in which not only solar insolation changes are varied but also vegetation and dust concentrations. Our results show that the greening of the Sahara and reduced dust loadings lead to more favorable conditions for tropical cyclone development compared with the orbital forcing alone. In particular, the strengthening of the West African Monsoon induced by the Sahara greening triggers a change in atmospheric circulation that affects the entire tropics. Furthermore, whereas previous studies suggest lower TC activity despite stronger summer insolation and warmer sea surface temperature in the Northern Hemisphere, accounting for the Sahara greening and reduced dust concentrations leads instead to an increase of TC activity in both hemispheres, particularly over the Caribbean basin and East Coast of North America. Our study highlights the importance of regional changes in land cover and dust concentrations in affecting the potential intensity and genesis of past TCs and suggests that both factors may have appreciable influence on TC activity in a future warmer climate.

The role of the meridional sea surface temperature gradient in controlling the Caribbean low‐level jet - Maldonado, Tito; Rutgersson, Anna; Caballero, Rodrigo; Pausata, Francesco S. R.; Alfaro, Eric; Amador, Jorge (Journal of Geophysical Research: Atmospheres, 2017)
Abstract The Caribbean low‐level jet (CLLJ) is an important modulator of regional climate, especially precipitation, in the Caribbean and Central America. Previous work has inferred, due to their semiannual cycle, an association between CLLJ strength and meridional sea surface temperature (SST) gradients in the Caribbean Sea, suggesting that the SST gradients may control the intensity and vertical shear of the CLLJ. In addition, both the horizontal and vertical structure of the jet have been related to topographic effects via interaction with the mountains in Northern South America (NSA), including funneling effects and changes in the meridional geopotential gradient. Here we test these hypotheses, using an atmospheric general circulation model to perform a set of sensitivity experiments to examine the impact of both SST gradients and topography on the CLLJ. In one sensitivity experiment, we remove the meridional SST gradient over the Caribbean Sea and in the other, we flatten the mountains over NSA. Our results show that the SST gradient and topography have little or no impact on the jet intensity, vertical, and horizontal wind shears, contrary to previous works. However, our findings do not discount a possible one‐way coupling between the SST and the wind over the Caribbean Sea through friction force. We also examined an alternative approach based on barotropic instability to understand the CLLJ intensity, vertical, and horizontal wind shears. Our results show that the current hypothesis about the CLLJ must be reviewed in order to fully understand the atmospheric dynamics governing the Caribbean region. , Key Points Atmospheric dynamics in the Caribbean SST over the Caribbean Sea is examined as kinetic energy source for the CLLJ Impact of meridional SST gradient on the vertical structure of CLLJ

Understanding the Mechanisms behind the Northward Extension of the West African Monsoon during the Mid-Holocene - Gaetani, Marco; Messori, Gabriele; Zhang, Qiong; Flamant, Cyrille; Pausata, Francesco S. R. (Journal of Climate, 2017)
Abstract Understanding the West African monsoon (WAM) dynamics in the mid-Holocene (MH) is a crucial issue in climate modeling, because numerical models typically fail to reproduce the extensive precipitation suggested by proxy evidence. This discrepancy may be largely due to the assumption of both unrealistic land surface cover and atmospheric aerosol concentration. In this study, the MH environment is simulated in numerical experiments by imposing extensive vegetation over the Sahara and the consequent reduction in airborne dust concentration. A dramatic increase in precipitation is simulated across the whole of West Africa, up to the Mediterranean coast. This precipitation response is in better agreement with proxy data, in comparison with the case in which only changes in orbital forcing are considered. Results show a substantial modification of the monsoonal circulation, characterized by an intensification of large-scale deep convection through the entire Sahara, and a weakening and northward shift (~6.5°) of the African easterly jet. The greening of the Sahara also leads to a substantial reduction in the African easterly wave activity and associated precipitation. The reorganization of the regional atmospheric circulation is driven by the vegetation effect on radiative forcing and associated heat fluxes, with the reduction in dust concentration to enhance this response. The results for the WAM in the MH present important implications for understanding future climate scenarios in the region and in teleconnected areas, in the context of projected wetter conditions in West Africa.

Greening of the Sahara suppressed ENSO activity during the mid-Holocene - Pausata, Francesco S. R.; Zhang, Qiong; Muschitiello, Francesco; Lu, Zhengyao; Chafik, Léon; Niedermeyer, Eva M.; Stager, J. Curt; Cobb, Kim M.; Liu, Zhengyu (Nature Communications, 2017)
Abstract The evolution of the El Niño-Southern Oscillation (ENSO) during the Holocene remains uncertain. In particular, a host of new paleoclimate records suggest that ENSO internal variability or other external forcings may have dwarfed the fairly modest ENSO response to precessional insolation changes simulated in climate models. Here, using fully coupled ocean-atmosphere model simulations, we show that accounting for a vegetated and less dusty Sahara during the mid-Holocene relative to preindustrial climate can reduce ENSO variability by 25%, more than twice the decrease obtained using orbital forcing alone. We identify changes in tropical Atlantic mean state and variability caused by the momentous strengthening of the West Africa Monsoon (WAM) as critical factors in amplifying ENSO’s response to insolation forcing through changes in the Walker circulation. Our results thus suggest that potential changes in the WAM due to anthropogenic warming may influence ENSO variability in the future as well.

The PMIP4 contribution to CMIP6 – Part 2: Two interglacials, scientific objective and experimental design for Holocene and Last Interglacial simulations - Otto-Bliesner, Bette L.; Braconnot, Pascale; Harrison, Sandy P.; Lunt, Daniel J.; Abe-Ouchi, Ayako; Albani, Samuel; Bartlein, Patrick J.; Capron, Emilie; Carlson, Anders E.; Dutton, Andrea; Fischer, Hubertus; Goelzer, Heiko; et al. (Geoscientific Model Development, 2017)
Abstract. Two interglacial epochs are included in the suite of Paleoclimate Modeling Intercomparison Project (PMIP4) simulations in the Coupled Model Intercomparison Project (CMIP6). The experimental protocols for simulations of the mid-Holocene (midHolocene, 6000 years before present) and the Last Interglacial (lig127k, 127 000 years before present) are described here. These equilibrium simulations are designed to examine the impact of changes in orbital forcing at times when atmospheric greenhouse gas levels were similar to those of the preindustrial period and the continental configurations were almost identical to modern ones. These simulations test our understanding of the interplay between radiative forcing and atmospheric circulation, and the connections among large-scale and regional climate changes giving rise to phenomena such as land–sea contrast and high-latitude amplification in temperature changes, and responses of the monsoons, as compared to today. They also provide an opportunity, through carefully designed additional sensitivity experiments, to quantify the strength of atmosphere, ocean, cryosphere, and land-surface feedbacks. Sensitivity experiments are proposed to investigate the role of freshwater forcing in triggering abrupt climate changes within interglacial epochs. These feedback experiments naturally lead to a focus on climate evolution during interglacial periods, which will be examined through transient experiments. Analyses of the sensitivity simulations will also focus on interactions between extratropical and tropical circulation, and the relationship between changes in mean climate state and climate variability on annual to multi-decadal timescales. The comparative abundance of paleoenvironmental data and of quantitative climate reconstructions for the Holocene and Last Interglacial make these two epochs ideal candidates for systematic evaluation of model performance, and such comparisons will shed new light on the importance of external feedbacks (e.g., vegetation, dust) and the ability of state-of-the-art models to simulate climate changes realistically.

Enhanced ice sheet melting driven by volcanic eruptions during the last deglaciation - Muschitiello, Francesco; Pausata, Francesco S. R.; Lea, James M.; Mair, Douglas W. F.; Wohlfarth, Barbara (Nature Communications, 2017)
Abstract Volcanic eruptions can impact the mass balance of ice sheets through changes in climate and the radiative properties of the ice. Yet, empirical evidence highlighting the sensitivity of ancient ice sheets to volcanism is scarce. Here we present an exceptionally well-dated annual glacial varve chronology recording the melting history of the Fennoscandian Ice Sheet at the end of the last deglaciation (∼13,200–12,000 years ago). Our data indicate that abrupt ice melting events coincide with volcanogenic aerosol emissions recorded in Greenland ice cores. We suggest that enhanced ice sheet runoff is primarily associated with albedo effects due to deposition of ash sourced from high-latitude volcanic eruptions. Climate and snowpack mass-balance simulations show evidence for enhanced ice sheet runoff under volcanically forced conditions despite atmospheric cooling. The sensitivity of past ice sheets to volcanic ashfall highlights the need for an accurate coupling between atmosphere and ice sheet components in climate models.

On the low-frequency variability of wintertime Euro-Atlantic planetary wave-breaking - Messori, Gabriele; Davini, Paolo; Alvarez-Castro, M. Carmen; Pausata, Francesco S. R.; Yiou, Pascal; Caballero, Rodrigo (Climate Dynamics, 2019)

The water cycle of the mid‐Holocene West African monsoon: The role of vegetation and dust emission changes - Messori, Gabriele; Gaetani, Marco; Zhang, Qiang; Zhang, Qiong; Pausata, Francesco S. R. (International Journal of Climatology, 2019)
During the mid‐Holocene (6 kyr BP), West Africa experienced a much stronger and geographically extensive monsoon than in the present day. Changes in orbital forcing, vegetation and dust emissions from the Sahara have been identified as key factors driving this intensification. Here, we analyse how the timing, origin and convergence of moisture fluxes contributing to the monsoonal precipitation change under a range of scenarios: orbital forcing only; orbital and vegetation forcings (Green Sahara); orbital, vegetation and dust forcings (Green Sahara‐reduced dust). We further compare our results to a range of reconstructions of mid‐Holocene precipitation from palaeoclimate archives. In our simulations, the greening of the Sahara leads to a cyclonic water vapour flux anomaly over North Africa with an anomalous westerly flow bringing large amounts of moisture into the Sahel from the Atlantic Ocean. Changes in atmospheric dust under a vegetated Sahara shift the anomalous moisture advection pattern northwards, increasing both moisture convergence and precipitation recycling over the northern Sahel and Sahara and the associated precipitation during the boreal summer. During this season, under both the Green Sahara and Green Sahara‐reduced dust scenarios, local recycling in the Saharan domain exceeds that of the Sahel. This points to local recycling as an important factor modulating vegetation‐precipitation feedbacks and the impact of Saharan dust emissions. Our results also show that temperature and evapotranspiration over the Sahara in the mid‐Holocene are close to Sahelian pre‐industrial values. This suggests that pollen‐based paleoclimate reconstructions of precipitation during the Green Sahara period are likely not biased by possible large evapotranspiration changes in the region.

Tropical cyclone activity affected by volcanically induced ITCZ shifts - Pausata, Francesco S. R.; Camargo, Suzana J. (Proceedings of the National Academy of Sciences, 2019)
Significance Volcanic eruptions can inject a large amount of aerosol particles, which interact with solar radiation and consequently can affect the climate worldwide, hence the intensity and frequency of extreme events for a few years following the eruption. However, only a handful of studies have investigated the impacts of volcanic eruptions on tropical cyclone activity. Through a set of sensitivity modeling experiments, our study demonstrates that volcanic eruptions by shifting the Intertropical convergence zone can impact tropical cyclone activity up to 4 years following the eruption. These results will prove valuable to society, allowing us to better prepare for the consequences of changes in tropical cyclone activity following large volcanic eruptions. , Volcanic eruptions can affect global climate through changes in atmospheric and ocean circulation, and therefore could impact tropical cyclone (TC) activity. Here, we use ensemble simulations performed with an Earth System Model to investigate the impact of strong volcanic eruptions occurring in the tropical Northern (NH) and Southern (SH) Hemisphere on the large-scale environmental factors that affect TCs. Such eruptions cause a strong asymmetrical hemispheric cooling, either in the NH or SH, which shifts the Intertropical Convergence Zone (ITCZ) southward or northward, respectively. The ITCZ shift and the associated surface temperature anomalies then cause changes to the genesis potential indices and TC potential intensity. The effect of the volcanic eruptions on the ITCZ and hence on TC activity lasts for at least 4 years. Finally, our analysis suggests that volcanic eruptions do not lead to an overall global reduction in TC activity but rather a redistribution following the ITCZ movement. On the other hand, the volcanically induced changes in El Niño-Southern Oscillation (ENSO) or sea-surface temperature do not seem to have a significant impact on TC activity as previously suggested.

Enhanced Himalayan Glacial Melting During YD and H1 Recorded in the Northern Bay of Bengal - Weldeab, Syee; Rühlemann, Carsten; Bookhagen, Bodo; Pausata, Francesco S. R.; Perez‐Lua, Fabiola M. (Geochemistry, Geophysics, Geosystems, 2019)
Abstract Ocean‐land thermal feedback mechanisms in the Indian Summer Monsoon (ISM) domain are an important but not well understood component of regional climate dynamics. Here we present a δ 18 O record analyzed in the mixed‐layer dwelling planktonic foraminifer Globigerinoides ruber ( sensu stricto ) from the northernmost Bay of Bengal (BoB). The δ 18 O time series provides a spatially integrated measure of monsoonal precipitation and Himalayan meltwater runoff into the northern BoB and reveals two brief episodes of anomalously low δ 18 O values between 16.3±0.4 and 16±0.5 and 12.6±0.4 and 12.3±0.4 thousand years before present. The timing of these events is centered at Heinrich event 1 and the Younger Dryas, well‐known phases of weak northern hemisphere monsoon systems. Numerical climate model experiments, simulating Heinrich event‐like conditions, suggest a surface warming over the monsoon‐dominated Himalaya and foreland in response to ISM weakening. Corroborating the simulation results, our analysis of published moraine exposure ages in the monsoon‐dominated Himalaya indicates enhanced glacier retreats that, considering age model uncertainties, coincide and overlap with the episodes of anomalously low δ 18 O values in the northernmost BoB. Our climate proxy and simulation results provide insights into past regional climate dynamics, suggesting reduced cloud cover, increased solar radiation, and air warming of the Himalaya and foreland areas and, as a result, glacier mass losses in response to weakened ISM. , Plain Language Summary Indian Summer Monsoon rainfall and Himalayan glacier/snow melts constitute the main water source for the densely populated Indian subcontinent. Better understanding of how future climate changes will affect the monsoon rainfall and Himalayan glaciers requires a long climate record. In this study, we create a 13,000‐year‐long climate record that allows us to better understand the response of Indian Summer Monsoon rainfall and Himalayan glaciers to past climate changes. The focus of our study is the time window between 9,000 and 22,000 years ago, an episode where the global climate experienced large and rapid changes. Our sediment record from the northern Bay of Bengal and climate change simulation indicate that during episodes of weak monsoon, the melting of the Himalayan glaciers increases substantially significantly. This is because the weakening of the monsoon results in less cloud cover and, as a result, the surface receives more sunlight and causes glacier melting. , Key Points Core sediments from the northern Bay of Bengal are a viable archive to reconstruct past changes in monsoonal and Himalayan meltwater runoff Weak monsoon reduces cloud cover and leads to increased radiative flux over the Himalaya and foreland areas and causes glacier mass loss A spatially integrated record of monsoon and Himalayan climate provides insights into regional climate dynamics

Northern Hemisphere Land Monsoon Precipitation Increased by the Green Sahara During Middle Holocene - Sun, Weiyi; Wang, Bin; Zhang, Qiong; Pausata, Francesco S. R.; Chen, Deliang; Lu, Guonian; Yan, Mi; Ning, Liang; Liu, Jian (Geophysical Research Letters, 2019)
Abstract Changes in land cover and dust emission may significantly influence the Northern Hemisphere land monsoon precipitation (NHLMP), but observations are too short to fully evaluate their impacts. The “Green Sahara” during the mid‐Holocene (6,000 years BP) provides an opportunity to unravel these mechanisms. Here we show that during the mid‐Holocene, most of the NHLMP changes revealed by proxy data are reproduced by the Earth System model results when the Saharan vegetation cover and dust reduction are taken into consideration. The simulated NHLMP significantly increases by 33.10% under the effect of the Green Sahara. The North African monsoon precipitation increases most significantly. Additionally, the Saharan vegetation (dust reduction under vegetated Sahara) alone remotely intensifies the Asian (North American) monsoon precipitation through large‐scale atmospheric circulation changes. These findings imply that future variations in land cover and dust emissions may appreciably influence the NHLMP. , Plain Language Summary Northern Hemisphere land monsoon precipitation (NHLMP) provides water resources for about two thirds of the world's population, which is vital for infrastructure planning, disaster mitigation, food security, and economic development. Changes in land cover and dust emissions may significantly influence the NHLMP, but observations are too short to understand the mechanisms. The Sahara Desert was once covered by vegetation and dust emission was substantially reduced during the mid‐Holocene (6,000 years BP), which provides an opportunity to test the models' capability and unravel these mechanisms. Here we use an Earth System model and find that when the Saharan vegetation and dust reduction are taken into consideration, the simulated annual mean precipitation over most of the NHLM regions shows a closer agreement with proxy records. The sensitivity experiments show that the North African monsoon precipitation increases most significantly under the regional effects of “Green Sahara.” The Saharan vegetation (dust reduction under vegetated Sahara) alone also remotely increases the Asian (North American) monsoon precipitation through large‐scale atmospheric circulation changes. The knowledge gained from this study is critical for improved understanding of the potential impacts of the land cover and dust changes on the projected future monsoon change. , Key Points The first study of the impact of Saharan vegetation and dust reduction on the NHLMP Comparison with proxy records shows the effect of the Green Sahara improves the simulated NHLMP The Saharan vegetation and dust reduction significantly increase the NHLMP by 33.10%

Hydroclimate in the Pamirs Was Driven by Changes in Precipitation‐Evaporation Seasonality Since the Last Glacial Period - Aichner, Bernhard; Makhmudov, Zafar; Rajabov, Ilhomjon; Zhang, Qiong; Pausata, Francesco S. R.; Werner, Martin; Heinecke, Liv; Kuessner, Marie L.; Feakins, Sarah J.; Sachse, Dirk; Mischke, Steffen (Geophysical Research Letters, 2019)
Abstract The Central Asian Pamir Mountains (Pamirs) are a high‐altitude region sensitive to climatic change, with only few paleoclimatic records available. To examine the glacial‐interglacial hydrological changes in the region, we analyzed the geochemical parameters of a 31‐kyr record from Lake Karakul and performed a set of experiments with climate models to interpret the results. δD values of terrestrial biomarkers showed insolation‐driven trends reflecting major shifts of water vapor sources. For aquatic biomarkers, positive δD shifts driven by changes in precipitation seasonality were observed at ca. 31–30, 28–26, and 17–14 kyr BP. Multiproxy paleoecological data and modelling results suggest that increased water availability, induced by decreased summer evaporation, triggered higher lake levels during those episodes, possibly synchronous to northern hemispheric rapid climate events. We conclude that seasonal changes in precipitation‐evaporation balance significantly influenced the hydrological state of a large waterbody such as Lake Karakul, while annual precipitation amount and inflows remained fairly constant. , Plain Language Summary Lakes in arid Central Asia are particularly susceptible to the rise and fall of lake levels as a consequence of climatic changes. To evaluate drivers behind this phenomenon, we developed a record of humidity and lake levels throughout the last 31,000 years from a high‐altitude lake in the Pamir Mountains. Herefore, we combined hydrological and ecological reconstructions with climate model experiments. Results show that neither the enhanced inflow by melting glaciers nor the significantly increased precipitation amount was responsible for higher lake levels during the studied interval. Instead, reduced summer evaporation during cold episodes was the major trigger for lake transgressions. These fluctuations were driven by changes in radiative forcing (i.e., insolation and hence temperature change) as a consequence of changes in the Earth's orbit around the Sun. As such, our results suggest that a significant impact on lake levels in arid regions is also to be expected by the current anthropogenically driven global warming. , Key Points Proxies for hydroclimate and catchment ecology show insolation‐driven trends, with higher δD values during the LGM similar to outputs from climate models Reduced summer evaporation during cold episodes increased water availability Increased summer moisture caused higher lake levels at 31–30, 28–26, and 17–14 kyr BP coinciding with northern hemispheric rapid climate events

Mountain Weather Research and Forecasting: Recent Progress and Current Challenges - Chow, Fotini K.; De Wekker, Stephan F.J.; Snyder, Bradley J. (Springer Netherlands, 2013)

On the Dependence of Winter Precipitation Types on Temperature, Precipitation Rate, and Associated Features - Thériault, Julie M.; Stewart, Ronald E.; Henson, William (Journal of Applied Meteorology and Climatology, 2010)
Abstract The phase of precipitation formed within the atmosphere is highly dependent on the vertical temperature profile through which it falls. In particular, several precipitation types can form in an environment with a melting layer aloft and a refreezing layer below. These precipitation types include freezing rain, ice pellets, wet snow, and slush. To examine the formation of such precipitation, a bulk microphysics scheme was used to compare the characteristics of the hydrometeors produced by the model and observed by a research aircraft flight during the 1998 ice storm near Montreal, Canada. The model reproduced several of the observed key precipitation characteristics. Sensitivity tests on the precipitation types formed during the ice storm were also performed. These tests utilized temperature profiles produced by the North American Regional Reanalysis. The results show that small variations (±0.5°C) in the temperature profiles as well as in the precipitation rate can have major impacts on the types of precipitation formed at the surface. These results impose strong requirements on the accuracy needed by prediction models.

A Parameterization of the Microphysical Processes Forming Many Types of Winter Precipitation - Thériault, Julie M.; Stewart, Ronald E. (Journal of the Atmospheric Sciences, 2010)
Abstract Several types of precipitation, such as freezing rain, ice pellets, and wet snow, are commonly observed during winter storms. The objective of this study is to better understand the formation of these winter precipitation types. To address this issue, detailed melting and refreezing of precipitation was added onto an existing bulk microphysics scheme. These modifications allow the formation of mixed-phase particles and these particles in turn lead to, or affect, the formation of many of the other types of precipitation. The precipitation type characteristics, such as the mass content, liquid fraction, and threshold diameters formed during a storm over St John’s, Newfoundland, Canada, are studied and compared with observations. Many of these features were reproduced by the model. Sensitivity experiments with the model were carried out to examine the dependence of precipitation characteristics in this event on thresholds of particle evolution in the new parameterization.

The 1998 Ice Storm: Local flow fields and linkages to precipitation - Henson, William; Stewart, Ronald; Kochtubajda, Bohdan; Thériault, Julie (Atmospheric Research, 2011)

Environmental conditions favoring ice pellet aggregation - Carmichael, H.E.; Stewart, R.E.; Henson, W.; Thériault, J.M. (Atmospheric Research, 2011)

Impacts of terminal velocity on the trajectory of winter precipitation types - Thériault, Julie M.; Stewart, Ronald E.; Henson, William (Atmospheric Research, 2012)

How Well Are We Measuring Snow: The NOAA/FAA/NCAR Winter Precipitation Test Bed - Rasmussen, Roy; Baker, Bruce; Kochendorfer, John; Meyers, Tilden; Landolt, Scott; Fischer, Alexandre P.; Black, Jenny; Thériault, Julie M.; Kucera, Paul; Gochis, David; Smith, Craig; Nitu, Rodica; et al. (Bulletin of the American Meteorological Society, 2012)

A Case Study of Processes Impacting Precipitation Phase and Intensity during the Vancouver 2010 Winter Olympics - Thériault, Julie M.; Rasmussen, Roy; Smith, Trevor; Mo, Ruping; Milbrandt, Jason A.; Brugman, Melinda M.; Joe, Paul; Isaac, George A.; Mailhot, Jocelyn; Denis, Bertrand (Weather and Forecasting, 2012)
Abstract Accurate forecasting of precipitation phase and intensity was critical information for many of the Olympic venue managers during the Vancouver 2010 Olympic and Paralympic Winter Games. Precipitation forecasting was complicated because of the complex terrain and warm coastal weather conditions in the Whistler area of British Columbia, Canada. The goal of this study is to analyze the processes impacting precipitation phase and intensity during a winter weather storm associated with rain and snow over complex terrain. The storm occurred during the second day of the Olympics when the downhill ski event was scheduled. At 0000 UTC 14 February, 2 h after the onset of precipitation, a rapid cooling was observed at the surface instrumentation sites. Precipitation was reported for 8 h, which coincided with the creation of a nearly 0°C isothermal layer, as well as a shift of the valley flow from up valley to down valley. Widespread snow was reported on Whistler Mountain with periods of rain at the mountain base despite the expectation derived from synoptic-scale models (15-km grid spacing) that the strong warm advection would maintain temperatures above freezing. Various model predictions are compared with observations, and the processes influencing the temperature, wind, and precipitation types are discussed. Overall, this case study provided a well-observed scenario of winter storms associated with rain and snow over complex terrain.

Reexamination of the State of the Art of Cloud Modeling Shows Real Improvements - Muhlbauer, Andreas; Grabowski, Wojciech W.; Malinowski, Szymon P.; Ackerman, Thomas P.; Bryan, George H.; Lebo, Zachary J.; Milbrandt, Jason A.; Morrison, Hugh; Ovchinnikov, Mikhail; Tessendorf, Sarah; Thériault, Julie M.; Thompson, Greg (Bulletin of the American Meteorological Society, 2013)

Weather observations on Whistler Mountain during five storms - Thériault, Julie M.; Rasmussen, Kristen L.; Fisico, Teresa; Stewart, Ronald E.; Joe, Paul; Gultepe, Ismail; Clément, Marilys; Isaac, George A. (Pure and Applied Geophysics, 2014)

The Monitoring Network of the Vancouver 2010 Olympics - Joe, Paul; Scott, Bill; Doyle, Chris; Isaac, George; Gultepe, Ismail; Forsyth, Douglas; Cober, Stewart; Campos, Edwin; Heckman, Ivan; Donaldson, Norman; Hudak, David; Rasmussen, Roy; et al. (Pure and Applied Geophysics, 2014)

Roundhouse (RND) Mountain Top Research Site: Measurements and Uncertainties for Winter Alpine Weather Conditions - Gultepe, I.; Isaac, G. A.; Joe, P.; Kucera, P. A.; Theriault, J. M.; Fisico, T. (Pure and Applied Geophysics, 2014)

Modeling the Phase Transition Associated with Melting Snow in a 1D Kinematic Framework: Sensitivity to the Microphysics - Milbrandt, J. A.; Thériault, J.; Mo, R. (Pure and Applied Geophysics, 2014)

Perspectives for Very High-Resolution Climate Simulations with Nested Models: Illustration of Potential in Simulating St. Lawrence River Valley Channelling Winds with the Fifth-Generation Canadian Regional Climate Model - Cholette, Mélissa; Laprise, René; Thériault, Julie (Climate, 2015)
With the refinement of grid meshes in regional climate models permitted by the increase in computing power, the grid telescoping or cascade method, already used in numerical weather prediction, can be applied to achieve very high-resolution climate simulations. The purpose of this study is two-fold: (1) to illustrate the perspectives offered by climate simulations on kilometer-scale grid meshes using the wind characteristics in the St. Lawrence River Valley (SLRV) as the test-bench; and (2) to establish some constraints to be satisfied for the physical realism and the computational affordability of these simulations. The cascade method is illustrated using a suite of five one-way nested, time-slice simulations carried out with the fifth-generation Canadian Regional Climate Model, with grid meshes varying from roughly 81 km, successively to 27, 9, 3 and finally 1 km, over domains centered on the SLRV. The results show the added value afforded by very high-resolution meshes for a realistic simulation of the SLRV winds. Kinetic energy spectra are used to document the spin-up time and the effective resolution of the simulations as a function of their grid meshes. A pragmatic consideration is developed arguing that kilometer-scale simulations could be achieved at a reasonable computational cost with time-slice simulations of high impact climate events. This study lends confidence to the idea that climate simulations and projections at kilometer-scale could soon become operationally feasible, thus offering interesting perspectives for resolving features that are currently out of reach with coarser-mesh models.

On the Characteristics of and Processes Producing Winter Precipitation Types near 0°C - Stewart, Ronald E.; Thériault, Julie M.; Henson, William (Bulletin of the American Meteorological Society, 2015)
Abstract This article examines the types of winter precipitation that occur near 0°C, specifically rain, freezing rain, freezing drizzle, ice pellets, snow pellets, and wet snow. It follows from a call by M. Ralph et al. for more attention to be paid to this precipitation since it represents one of the most serious wintertime quantitative precipitation forecasting (QPF) issues. The formation of the many precipitation types involves ice-phase and/or liquid-phase processes, and thresholds in the degree of melting and/or freezing often dictate the types occurring at the surface. Some types can occur simultaneously so that, for example, ensuing collisions between supercooled raindrops and ice pellets that form ice pellet aggregates can lead to substantial reductions in the occurrence of freezing rain at the surface, and ice crystal multiplication processes can lead to locally produced ice crystals in the subfreezing layer below inversions. Highly variable fall velocities within the background temperature and wind fields of precipitation-type transition regions lead to varying particle trajectories and significant alterations in the distribution of precipitation amount and type at the surface. Physically based predictions that account for at least some of the phase changes and particle interactions are now in operation. Outstanding issues to be addressed include the impacts of accretion on precipitation-type formation, quantification of melting and freezing rates of the highly variable precipitation, the consequences of collisions between the various types, and the onset of ice nucleation and its effects. The precipitation physics perspective of this article furthermore needs to be integrated into a comprehensive understanding involving the surrounding and interacting environment.

Impact of melting snow on the valley flow field and precipitation phase transition - Thériault, Julie M.; Milbrandt, Jason A.; Doyle, Jonathan; Minder, Justin R.; Thompson, Gregory; Sarkadi, Noemi; Geresdi, Istvan (Atmospheric Research, 2015)

Clarification of the Water Saturation Represented on Ice Crystal Growth Diagrams - St-Pierre, Médéric; Thériault, Julie M. (Journal of the Atmospheric Sciences, 2015)
It has been known for a long time that the shape of ice crystals depends on both the air temperature and the relative humidity of the environment. The relationships among these factors have been summarized in classification diagrams and are intensively referred to in the cloud physics literature. To put in perspective the atmospheric conditions in which the different ice crystal habits grow with respect to the level of saturation in the atmosphere, the vapor density excess and supersaturation with respect to ice at liquid water saturation have been included on those diagrams as a function of air temperature. Over the years, the definition of the water saturation included in those types of diagrams has been misdefined. The goal of this study is to show that an error has been introduced in the definition of the excess of water vapor with respect to ice.

The June 2013 Alberta catastrophic flooding event – part 2: fine‐scale precipitation and associated features - Kochtubajda, B.; Stewart, R. E.; Boodoo, S.; Thériault, J. M.; Li, Y.; Liu, A.; Mooney, C.; Goodson, R.; Szeto, K. (Hydrological Processes, 2016)
Abstract Data obtained from a variety of sources including the Canadian Lightning Detection Network, weather radars, weather stations and operational numerical weather model analyses were used to address the evolution of precipitation during the June 2013 southern Alberta flood. The event was linked to a mid‐level closed low pressure system to the west of the region and a surface low pressure region initially to its south. This configuration brought warm, moist unstable air into the region that led to dramatic, organized convection with an abundance of lightning and some hail. Such conditions occurred in the southern parts of the region whereas the northern parts were devoid of lightning. Initially, precipitation rates were high (extreme 15‐min rainfall rates up to 102 mm h −1 were measured) but decreased to lower values as the precipitation shifted to long‐lived stratiform conditions. Both the convective and stratiform precipitation components were affected by the topography. Similar flooding events, such as June 2002, have occurred over this region although the 2002 event was colder and precipitation was not associated with substantial convection over southwest Alberta. Copyright © 2016 Her Majesty the Queen in Right of Canada. Hydrological Processes. © John Wiley & Sons, Ltd.

The June 2013 Alberta Catastrophic Flooding Event: Part 1—Climatological aspects and hydrometeorological features - Liu, A. Q.; Mooney, C.; Szeto, K.; Thériault, J. M.; Kochtubajda, B.; Stewart, R. E.; Boodoo, S.; Goodson, R.; Li, Y.; Pomeroy, J. (Hydrological Processes, 2016)
Abstract In June 2013, excessive rainfall associated with an intense weather system triggered severe flooding in southern Alberta, which became the costliest natural disaster in Canadian history. This article provides an overview of the climatological aspects and large‐scale hydrometeorological features associated with the flooding event based upon information from a variety of sources, including satellite data, upper air soundings, surface observations and operational model analyses. The results show that multiple factors combined to create this unusually severe event. The event was characterized by a slow‐moving upper level low pressure system west of Alberta, blocked by an upper level ridge, while an associated well‐organized surface low pressure system kept southern Alberta, especially the eastern slopes of the Rocky Mountains, in continuous precipitation for up to two days. Results from air parcel trajectory analysis show that a significant amount of the moisture originated from the central Great Plains, transported into Alberta by a southeasterly low level jet. The event was first dominated by significant thunderstorm activity, and then evolved into continuous precipitation supported by the synoptic‐scale low pressure system. Both the thunderstorm activity and upslope winds associated with the low pressure system produced large rainfall amounts. A comparison with previous similar events occurring in the same region suggests that the synoptic‐scale features associated with the 2013 rainfall event were not particularly intense; however, its storm environment was the most convectively unstable. The system also exhibited a relatively high freezing level, which resulted in rain, rather than snow, mainly falling over the still snow‐covered mountainous areas. Melting associated with this rain‐on‐snow scenario likely contributed to downstream flooding. Furthermore, above‐normal snowfall in the preceding spring helped to maintain snow in the high‐elevation areas, which facilitated the rain‐on‐snow event. Copyright © 2016 John Wiley & Sons, Ltd.

The Collection Efficiency of Shielded and Unshielded Precipitation Gauges. Part II: Modeling Particle Trajectories - Colli, Matteo; Lanza, Luca G.; Rasmussen, Roy; Thériault, Julie M. (Journal of Hydrometeorology, 2016)
Abstract The use of windshields to reduce the impact of wind on snow measurements is common. This paper investigates the catching performance of shielded and unshielded gauges using numerical simulations. In Part II, the role of the windshield and gauge aerodynamics, as well as the varying flow field due to the turbulence generated by the shield–gauge configuration, in reducing the catch efficiency is investigated. This builds on the computational fluid dynamics results obtained in Part I, where the airflow patterns in the proximity of an unshielded and single Alter shielded Geonor T-200B gauge are obtained using both time-independent [Reynolds-averaged Navier–Stokes (RANS)] and time-dependent [large-eddy simulation (LES)] approaches. A Lagrangian trajectory model is used to track different types of snowflakes (wet and dry snow) and to assess the variation of the resulting gauge catching performance with the wind speed. The collection efficiency obtained with the LES approach is generally lower than the one obtained with the RANS approach. This is because of the impact of the LES-resolved turbulence above the gauge orifice rim. The comparison between the collection efficiency values obtained in case of shielded and unshielded gauge validates the choice of installing a single Alter shield in a windy environment. However, time-dependent simulations show that the propagating turbulent structures produced by the aerodynamic response of the upwind single Alter blades have an impact on the collection efficiency. Comparison with field observations provides the validation background for the model results.

The Collection Efficiency of Shielded and Unshielded Precipitation Gauges. Part I: CFD Airflow Modeling - Colli, Matteo; Lanza, Luca G.; Rasmussen, Roy; Thériault, Julie M. (Journal of Hydrometeorology, 2016)
Abstract The aerodynamic response of snow gauges when exposed to the wind is responsible for a significant reduction of their collection performance. The modifications induced by the gauge and the windshield onto the space–time patterns of the undisturbed airflow deviate the snowflake trajectories. In Part I, the disturbed air velocity field in the vicinity of shielded and unshielded gauge configurations is investigated. In Part II, the airflow is the basis for a particle tracking model of snowflake trajectories to estimate the collection efficiency. A Geonor T-200B gauge inside a single Alter shield is simulated for wind speeds varying from 1 to 8 m s−1. Both time-averaged and time-dependent computational fluid dynamics simulations are performed, based on Reynolds-averaged Navier–Stokes (RANS) and large-eddy simulation (LES) models, respectively. A shear stress tensor k–Ω model (where k is the turbulent kinetic energy and Ω is the turbulent specific dissipation rate) is used for the RANS formulation and solved within a finite-volume method. The LES is implemented with a Smagorinsky subgrid-scale method that models the subgrid stresses as a gradient-diffusion process. The RANS simulations confirm the attenuation of the airflow velocity above the gauge when using a single Alter shield, but the generated turbulence above the orifice rim is underestimated. The intensity and spatial extension of the LES-resolved turbulent region show a dependency on the wind speed that was not detected by the RANS. The time-dependent analysis showed the propagation of turbulent structures and the impact on the turbulent kinetic energy above the gauge collecting section.

Spatial spin-up of fine scales in a regional climate model simulation driven by low-resolution boundary conditions - Matte, Dominic; Laprise, René; Thériault, Julie M.; Lucas-Picher, Philippe (Climate Dynamics, 2017)

On the relationship between the snowflake type aloft and the surface precipitation types at temperatures near 0 °C - Sankaré, Housseyni; Thériault, Julie M. (Atmospheric Research, 2016)

Comparison between high-resolution climate simulations using single- and double-nesting approaches within the Big-Brother experimental protocol - Matte, Dominic; Laprise, René; Thériault, Julie Mireille (Climate Dynamics, 2016)

Evaluating the Ability of CRCM5 to Simulate Mixed Precipitation - Bresson, É.; Laprise, R.; Paquin, D.; Thériault, J.M.; De Elía, R. (Atmosphere-Ocean, 2017)

A Numerical Study of the June 2013 Flood-Producing Extreme Rainstorm over Southern Alberta - Li, Yanping; Szeto, Kit; Stewart, Ronald E.; Thériault, Julie M.; Chen, Liang; Kochtubajda, Bohdan; Liu, Anthony; Boodoo, Sudesh; Goodson, Ron; Mooney, Curtis; Kurkute, Sopan (Journal of Hydrometeorology, 2017)
Abstract A devastating, flood-producing rainstorm occurred over southern Alberta, Canada, from 19 to 22 June 2013. The long-lived, heavy rainfall event was a result of complex interplays between topographic, synoptic, and convective processes that rendered an accurate simulation of this event a challenging task. In this study, the Weather Research and Forecasting (WRF) Model was used to simulate this event and was validated against several observation datasets. Both the timing and location of the model precipitation agree closely with the observations, indicating that the WRF Model is capable of reproducing this type of severe event. Sensitivity tests with different microphysics schemes were conducted and evaluated using equitable threat and bias frequency scores. The WRF double-moment 6-class microphysics scheme (WDM6) generally performed better when compared with other schemes. The application of a conventional convective/stratiform separation algorithm shows that convective activity was dominant during the early stages, then evolved into predominantly stratiform precipitation later in the event. The HYSPLIT back-trajectory analysis and regional water budget assessments using WRF simulation output suggest that the moisture for the precipitation was mainly from recycling antecedent soil moisture through evaporation and evapotranspiration over the Canadian Prairies and the U.S. Great Plains. This analysis also shows that a small fraction of the moisture can be traced back to the northeastern Pacific, and direct uptake from the Gulf of Mexico was not a significant source in this event.

Improving the Explicit Prediction of Freezing Rain in a Kilometer-Scale Numerical Weather Prediction Model - Barszcz, Agnieszka; Milbrandt, Jason A.; Thériault, Julie M. (Weather and Forecasting, 2018)
Abstract A freezing rain event, in which the Meteorological Centre of Canada’s 2.5-km numerical weather prediction system significantly underpredicted the quantity of freezing rain, is examined. The prediction system models precipitation types explicitly, directly from the Milbrandt–Yau microphysics scheme. It was determined that the freezing rain underprediction for this case was due primarily to excessive refreezing of rain, originating from melting snow and graupel, in and under the temperature inversion of the advancing warm front ultimately depleting the supply of rain reaching the surface. The refreezing was caused from excessive collisional freezing between rain and graupel. Sensitivity experiments were conducted to examine the effects of a temperature threshold for collisional freezing and on varying the values of the collection efficiencies between rain and ice-phase hydrometeors. It was shown that by reducing the rain–graupel collection efficiency and by imposing a temperature threshold of −5°C, above which collisional freezing is not permitted, excessive rain–graupel collection and graupel formation can be controlled in the microphysics scheme, leading to an improved simulation of freezing rain at the surface.

Mixed precipitation occurrences over southern Québec, Canada, under warmer climate conditions using a regional climate model - Matte, Dominic; Thériault, Julie M.; Laprise, René (Climate Dynamics, 2019)

Precipitation characteristics and associated weather conditions on the eastern slopes of the Canadian Rockies during March–April 2015 - Thériault, Julie M.; Hung, Ida; Vaquer, Paul; Stewart, Ronald E.; Pomeroy, John W. (Hydrology and Earth System Sciences, 2018)
Abstract. Precipitation events that bring rain and snow to the Banff–Calgary area of Alberta are a critical aspect of the region's water cycle and can lead to major flooding events such as the June 2013 event that was the second most costly natural disaster in Canadian history. Because no special atmospheric-oriented observations of these events have been made, a field experiment was conducted in March and April 2015 in Kananaskis, Alberta, to begin to fill this gap. The goal was to characterize and better understand the formation of the precipitation at the surface during spring 2015 at a specific location in the Kananaskis Valley. Within the experiment, detailed measurements of precipitation and weather conditions were obtained, a vertically pointing Doppler radar was deployed and weather balloons were released. Although 17 precipitation events occurred, this period was associated with much less precipitation than normal (−35 %) and above-normal temperatures (2.5 ∘C). Of the 133 h of observed precipitation, solid precipitation occurred 71 % of the time, mixed precipitation occurred 9 % and rain occurred 20 %. An analysis of 17 504 precipitation particles from 1181 images showed that a wide variety of crystals and aggregates occurred and approximately 63 % showed signs of riming. This was largely independent of whether flows aloft were upslope (easterly) or downslope (westerly). In the often sub-saturated surface conditions, hydrometeors containing ice occurred at temperatures as high as 9 ∘C. Radar structures aloft were highly variable with reflectivity sometimes >30 dBZe and Doppler velocity up to −1 m s−1, which indicates upward motion of particles within ascending air masses. Precipitation was formed in this region within cloud fields sometimes having variable structures and within which supercooled water at least sometimes existed to produce accreted particles massive enough to reach the surface through the relatively dry sub-cloud region.

Parameterization of the Bulk Liquid Fraction on Mixed-Phase Particles in the Predicted Particle Properties (P3) Scheme: Description and Idealized Simulations - Cholette, Mélissa; Morrison, Hugh; Milbrandt, Jason A.; Thériault, Julie M. (Journal of the Atmospheric Sciences, 2019)
Abstract Bulk microphysics parameterizations that are used to represent clouds and precipitation usually allow only solid and liquid hydrometeors. Predicting the bulk liquid fraction on ice allows an explicit representation of mixed-phase particles and various precipitation types, such as wet snow and ice pellets. In this paper, an approach for the representation of the bulk liquid fraction into the predicted particle properties (P3) microphysics scheme is proposed and described. Solid-phase microphysical processes, such as melting and sublimation, have been modified to account for the liquid component. New processes, such as refreezing and condensation of the liquid portion of mixed-phase particles, have been added to the parameterization. Idealized simulations using a one-dimensional framework illustrate the overall behavior of the modified scheme. The proposed approach compares well to a Lagrangian benchmark model. Temperatures required for populations of ice crystals to melt completely also agree well with previous studies. The new processes of refreezing and condensation impact both the surface precipitation type and feedback between the temperature and the phase changes. Overall, prediction of the bulk liquid fraction allows an explicit description of new precipitation types, such as wet snow and ice pellets, and improves the representation of hydrometeor properties when the temperature is near 0°C.

Influence of the Model Horizontal Resolution on Atmospheric Conditions Leading to Freezing Rain in Regional Climate Simulations - St-Pierre, Médéric; Thériault, Julie M.; Paquin, Dominique (Atmosphere-Ocean, 2019)

Role of sublimation and riming in the precipitation distribution in the Kananaskis Valley, Alberta, Canada - Poirier, Émilie; Thériault, Julie M.; Leriche, Maud (Hydrology and Earth System Sciences, 2019)
Abstract. The phase of precipitation and its distribution at the surface can affect water resources and the regional water cycle of a region. A field project was held in March–April 2015 on the eastern slope of the Canadian Rockies to document precipitation characteristics and associated atmospheric conditions. During the project, 60 % of the particles documented were rimed in relatively warm and dry conditions. Rain–snow transitions also occurred aloft and at the surface in sub-saturated conditions. Ice-phase precipitation falling through a saturated atmospheric layer with temperatures > 0 ∘C will start melting. In contrast, if the melting layer is sub-saturated, the ice-phase precipitation undergoes sublimation, which increases the depth of the rain–snow transition. In this context, this study investigates the role of sublimation and riming in precipitation intensity and type reaching the surface in the Kananaskis Valley, Alberta, during March–April 2015. To address this, a set of numerical simulations of an event of mixed precipitation observed at the surface was conducted. This event on 31 March 2015 was documented with a set of devices at the main observation site (Kananaskis Emergency Services, KES), including a precipitation gauge, disdrometer, and micro rain radar. Sensitivity experiments were performed to assess the impacts of temperature changes from sublimation and the role of the production of graupel (riming) aloft in the surface precipitation evolution. A warmer environment associated with no temperature changes from sublimation leads to a peak in the intensity of graupel at the surface. When the formation of graupel is not considered, the maximum snowfall rate occurred at later times. Results suggest that unrimed snow reaching the surface is formed on the western flank and is advected eastward. In contrast, graupel would form aloft in the Kananaskis Valley. The cooling from sublimation and melting by rimed particles increases the vertical shear near KES. Overall, this study illustrated that the presence of graupel influenced the surface evolution of precipitation type in the valley due to the horizontal transport of precipitation particles.

Dynamical downscaling with the fifth-generation Canadian regional climate model (CRCM5) over the CORDEX Arctic domain: effect of large-scale spectral nudging and of empirical correction of sea-surface temperature - Takhsha, Maryam; Nikiéma, Oumarou; Lucas-Picher, Philippe; Laprise, René; Hernández-Díaz, Leticia; Winger, Katja (Climate Dynamics, 2018)

A metrics‐based analysis of seasonal daily precipitation and near‐surface temperature within seven Coordinated Regional Climate Downscaling Experiment domains - Glisan, Justin M.; Jones, Richard; Lennard, Chris; Castillo Pérez, Nadia I.; Lucas‐Picher, Philippe; Rinke, Annette; Solman, Silvina; Gutowski, William J. (Atmospheric Science Letters, 2019)
We compare ensemble mean daily precipitation and near‐surface temperatures from regional climate model simulations over seven Coordinated Regional Climate Downscaling Experiment domains for the winter and summer seasons. We use Taylor diagrams to show the domain‐wide pattern similarity between the model ensemble and the observational data sets. We use the Climatic Research Unit (CRU) and the University of Delaware gridded observations and ERA‐Interim reanalysis data as an additional observationally based estimate of historical climatology. Taylor diagrams determine the relative skill of the seven sets of simulations and quantify these results in terms of center pattern root‐mean square error and correlation coefficient. Results suggest that there is good agreement between the models and the CRU, in terms of their respective seasonal cycles, as shown in Taylor diagrams and bias plots. There is also good agreement between both gridded observation sets. In addition, downscaled ERA‐Interim precipitation is closer to observations than raw ERA‐Interim precipitation. Domains located in the low latitudes and those having high topography appear to have larger biases, especially precipitation.

A Decade of Climate Scenarios: The Ouranos Consortium Modus Operandi - Huard, David; Chaumont, Diane; Logan, Travis; Sottile, Marie-France; Brown, Ross D.; St-Denis, Blaise Gauvin; Grenier, Patrick; Braun, Marco (Bulletin of the American Meteorological Society, 2014)

Quantifying Vulnerability to Extreme Heat in Time Series Analyses: A Novel Approach Applied to Neighborhood Social Disparities under Climate Change - Benmarhnia, Tarik; Grenier, Patrick; Brand, Allan; Fournier, Michel; Deguen, Séverine; Smargiassi, Audrey (International Journal of Environmental Research and Public Health, 2015)
Objectives: We propose a novel approach to examine vulnerability in the relationship between heat and years of life lost and apply to neighborhood social disparities in Montreal and Paris. Methods: We used historical data from the summers of 1990 through 2007 for Montreal and from 2004 through 2009 for Paris to estimate daily years of life lost social disparities (DYLLD), summarizing social inequalities across groups. We used Generalized Linear Models to separately estimate relative risks (RR) for DYLLD in association with daily mean temperatures in both cities. We used 30 climate scenarios of daily mean temperature to estimate future temperature distributions (2021–2050). We performed random effect meta-analyses to assess the impact of climate change by climate scenario for each city and compared the impact of climate change for the two cities using a meta-regression analysis. Results: We show that an increase in ambient temperature leads to an increase in social disparities in daily years of life lost. The impact of climate change on DYLLD attributable to temperature was of 2.06 (95% CI: 1.90, 2.25) in Montreal and 1.77 (95% CI: 1.61, 1.94) in Paris. The city explained a difference of 0.31 (95% CI: 0.14, 0.49) on the impact of climate change. Conclusion: We propose a new analytical approach for estimating vulnerability in the relationship between heat and health. Our results suggest that in Paris and Montreal, health disparities related to heat impacts exist today and will increase in the future.

Toward daily climate scenarios for Canadian Arctic coastal zones with more realistic temperature‐precipitation interdependence - Gennaretti, Fabio; Sangelantoni, Lorenzo; Grenier, Patrick (Journal of Geophysical Research: Atmospheres, 2015)
Abstract The interdependence between climatic variables should be taken into account when developing climate scenarios. For example, temperature‐precipitation interdependence in the Arctic is strong and impacts on other physical characteristics, such as the extent and duration of snow cover. However, this interdependence is often misrepresented in climate simulations. Here we use two two‐dimensional (2‐D) methods for statistically adjusting climate model simulations to develop plausible local daily temperature ( T mean ) and precipitation ( Pr ) scenarios. The first 2‐D method is based on empirical quantile mapping (2Dqm) and the second on parametric copula models (2Dcopula). Both methods are improved here by forcing the preservation of the modeled long‐term warming trend and by using moving windows to obtain an adjustment specific to each day of the year. These methods were applied to a representative ensemble of 13 global climate model simulations at 26 Canadian Arctic coastal sites and tested using an innovative cross‐validation approach. Intervariable dependence was evaluated using correlation coefficients and empirical copula density plots. Results show that these 2‐D methods, especially 2Dqm, adjust individual distributions of climatic time series as adequately as one common one‐dimensional method (1Dqm) does. Furthermore, although 2Dqm outperforms the other methods in reproducing the observed temperature‐precipitation interdependence over the calibration period, both 2Dqm and 2Dcopula perform similarly over the validation periods. For cases where temperature‐precipitation interdependence is important (e.g., characterizing extreme events and the extent and duration of snow cover), both 2‐D methods are good options for producing plausible local climate scenarios in Canadian Arctic coastal zones. , Key Points We improved two methods for adjusting T mean , Pr , and their dependence in scenarios Methods are tested at Arctic coastal sites where T mean ‐ Pr dependence is crucial Both methods improve the plausibility of the local climate scenarios

Partitioning prediction uncertainty in climate-dependent population models - Gauthier, Gilles; Péron, Guillaume; Lebreton, Jean-Dominique; Grenier, Patrick; Van Oudenhove, Louise (Proceedings of the Royal Society B: Biological Sciences, 2016)
The science of complex systems is increasingly asked to forecast the consequences of climate change. As a result, scientists are now engaged in making predictions about an uncertain future, which entails the efficient communication of this uncertainty. Here we show the benefits of hierarchically decomposing the uncertainty in predicted changes in animal population size into its components due to structural uncertainty in climate scenarios (greenhouse gas emissions and global circulation models), structural uncertainty in the demographic model, climatic stochasticity, environmental stochasticity unexplained by climate–demographic trait relationships, and sampling variance in demographic parameter estimates. We quantify components of uncertainty surrounding the future abundance of a migratory bird, the greater snow goose ( Chen caeruslescens atlantica ), using a process-based demographic model covering their full annual cycle. Our model predicts a slow population increase but with a large prediction uncertainty. As expected from theoretical variance decomposition rules, the contribution of sampling variance to prediction uncertainty rapidly overcomes that of process variance and dominates. Among the sources of process variance, uncertainty in the climate scenarios contributed less than 3% of the total prediction variance over a 40-year period, much less than environmental stochasticity. Our study exemplifies opportunities to improve the forecasting of complex systems using long-term studies and the challenges inherent to predicting the future of stochastic systems.

Probabilistic climate change scenarios for viticultural potential in Québec - Roy, Philippe; Grenier, Patrick; Barriault, Evelyne; Logan, Travis; Blondlot, Anne; Bourgeois, Gaétan; Chaumont, Diane (Climatic Change, 2017)

Impact of climate change on Ostrinia nubilalis (Lepidoptera: Crambidae) phenology and its implications on pest management - Gagnon, Annie‐Ève; Bourgeois, Gaétan; Bourdages, Line; Grenier, Patrick; Blondlot, Anne (Agricultural and Forest Entomology, 2019)
Abstract Climate change can cause negative impacts to the agricultural sector by increasing pest damage to crops. The European corn borer (ECB) is a major insect pest of corn in North America. Its speed of development could potentially accelerate under a warmer climate, leading to an earlier development of the first generation and an increase in the number of generations per year. The main objective of this study was to assess the potential impacts of climate change on ECB management for the future period 2041–2070 in Quebec, Canada, using bioclimatic modelling and climate analogues. First flight of ECB moths could occur about 15 days earlier in the season in 2041–2070 compared to the reference period 1970–1999. The window for insecticide interventions may be reduced under climate change by 15.6% to 27.8% for univoltine ECB and by 13.8% to 52.7% for bivoltine ECB. Climate change could promote the development of an additional generation in the southern region for both races, considering temperature increases and factors inducing the overwintering diapause. ECB management could become more costly both economically and environmentally under the future climate, and it should be revised according to the results of this study.

The issue of properly ordering climate indices calculation and bias correction before identifying spatial analogs for agricultural applications - Grenier, Patrick; Firlej, Annabelle; Blondlot, Anne; Logan, Travis; Ricard, Marie-Pier (Climate Services, 2019)

Investigating added value of regional climate modeling in North American winter storm track simulations - Poan, E. D.; Gachon, P.; Laprise, R.; Aider, R.; Dueymes, G. (Climate Dynamics, 2018)

Predicted Northward Expansion of the Geographic Range of the Tick Vector Amblyomma americanum in North America under Future Climate Conditions - Sagurova, Irina; Ludwig, Antoinette; Ogden, Nicholas H.; Pelcat, Yann; Dueymes, Guillaume; Gachon, Philippe (Environmental Health Perspectives, 2019)

Considerations of Domain Size and Large-Scale Driving for Nested Regional Climate Models: Impact on Internal Variability and Ability at Developing Small-Scale Details - Laprise, René; Kornic, Dragana; Rapaić, Maja; Šeparović, Leo; Leduc, Martin; Nikiema, Oumarou; Di Luca, Alejandro; Diaconescu, Emilia; Alexandru, Adelina; Lucas-Picher, Philippe; De Elía, Ramón; Caya, Daniel; et al. (Climate Change, 2012)

Potential for added value in precipitation simulated by high-resolution nested Regional Climate Models and observations - Di Luca, Alejandro; De Elía, Ramón; Laprise, René (Climate Dynamics, 2012)

Potential for small scale added value of RCM’s downscaled climate change signal - Di Luca, Alejandro; De Elía, Ramón; Laprise, René (Climate Dynamics, 2013)

The atmospheric component of the Mediterranean Sea water budget in a WRF multi-physics ensemble and observations - Di Luca, Alejandro; Flaounas, Emmanouil; Drobinski, Philippe; Brossier, Cindy Lebeaupin (Climate Dynamics, 2014)

Resolution Sensitivity of Cyclone Climatology over Eastern Australia Using Six Reanalysis Products* - Di Luca, Alejandro; Evans, Jason P.; Pepler, Acacia; Alexander, Lisa; Argüeso, Daniel (Journal of Climate, 2015)
Abstract The climate of the eastern seaboard of Australia is strongly influenced by the passage of low pressure systems over the adjacent Tasman Sea due to their associated precipitation and their potential to develop into extreme weather events. The aim of this study is to quantify differences in the climatology of east coast lows derived from the use of six global reanalyses. The methodology is explicitly designed to identify differences between reanalyses arising from differences in their horizontal resolution and their structure (type of forecast model, assimilation scheme, and the kind and number of observations assimilated). As a basis for comparison, reanalysis climatologies are compared with an observation-based climatology. Results show that reanalyses, specially high-resolution products, lead to very similar climatologies of the frequency, intensity, duration, and size of east coast lows when using spatially smoothed (about 300-km horizontal grid meshes) mean sea level pressure fields as input data. Moreover, at these coarse horizontal scales, monthly, interannual, and spatial variabilities appear to be very similar across the various reanalyses with a generally stronger agreement between winter events compared with summer ones. Results also show that, when looking at cyclones using reanalysis data at their native resolution (approaching 50-km grid spacing for the most recent products), uncertainties related to the frequency, intensity, and size of lows are very large and it is not clear which reanalysis, if any, gives a better description of cyclones. Further work is needed in order to evaluate the usefulness of the finescale information in modern reanalyses and to better understand the sources of their differences.

Using large-scale diagnostic quantities to investigate change in East Coast Lows - Ji, Fei; Evans, Jason P.; Argueso, Daniel; Fita, Lluis; Di Luca, Alejandro (Climate Dynamics, 2015)

Impact of Identification Method on the Inferred Characteristics and Variability of Australian East Coast Lows - Pepler, Acacia S.; Di Luca, Alejandro; Ji, Fei; Alexander, Lisa V.; Evans, Jason P.; Sherwood, Steven C. (Monthly Weather Review, 2015)
Abstract The Australian east coast low (ECL) is both a major cause of damaging severe weather and an important contributor to rainfall and dam inflow along the east coast, and is of interest to a wide range of groups including catchment managers and emergency services. For this reason, several studies in recent years have developed and interrogated databases of east coast lows using a variety of automated cyclone detection methods and identification criteria. This paper retunes each method so that all yield a similar event frequency within the ECL region, to enable a detailed intercomparison of the similarities, differences, and relative advantages of each method. All methods are shown to have substantial skill at identifying ECL events leading to major impacts or explosive development, but the choice of method significantly affects both the seasonal and interannual variation of detected ECL numbers. This must be taken into consideration in studies on trends or variability in ECLs, with a subcategorization of ECL events by synoptic situation of key importance.

Challenges in the Quest for Added Value of Regional Climate Dynamical Downscaling - Di Luca, Alejandro; De Elía, Ramón; Laprise, René (Current Climate Change Reports, 2015)

Effects of City Expansion on Heat Stress under Climate Change Conditions - Argüeso, Daniel; Evans, Jason P.; Pitman, Andrew J.; Di Luca, Alejandro (PLOS ONE, 2015)

Quantifying the overall added value of dynamical downscaling and the contribution from different spatial scales - Di Luca, Alejandro; Argüeso, Daniel; Evans, Jason P.; De Elía, Ramón; Laprise, René (Journal of Geophysical Research: Atmospheres, 2016)
Abstract This study evaluates the added value in the representation of surface climate variables from an ensemble of regional climate model (RCM) simulations by comparing the relative skill of the RCM simulations and their driving data over a wide range of RCM experimental setups and climate statistics. The methodology is specifically designed to compare results across different variables and metrics, and it incorporates a rigorous approach to separate the added value occurring at different spatial scales. Results show that the RCMs' added value strongly depends on the type of driving data, the climate variable, and the region of interest but depends rather weakly on the choice of the statistical measure, the season, and the RCM physical configuration. Decomposing climate statistics according to different spatial scales shows that improvements are coming from the small scales when considering the representation of spatial patterns, but from the large‐scale contribution in the case of absolute values. Our results also show that a large part of the added value can be attained using some simple postprocessing methods. , Key Points A rigorous methodology that allows evaluating the overall benefits of high‐resolution simulations The most reliable source of added value is the better representation of the spatial variability Substantial added value can also be attained using simple postprocessing methods

Evaluation of long-term precipitation and temperature Weather Research and Forecasting simulations for southeast Australia - Ji, F; Evans, Jp; Teng, J; Scorgie, Y; Argüeso, D; Di Luca, A (Climate Research, 2016)

The NARCliM project: model agreement and significance of climate projections - Olson, R; Evans, Jp; Di Luca, A; Argüeso, D (Climate Research, 2016)

Projected changes in east Australian midlatitude cyclones during the 21st century - Pepler, Acacia S.; Di Luca, Alejandro; Ji, Fei; Alexander, Lisa V.; Evans, Jason P.; Sherwood, Steven C. (Geophysical Research Letters, 2016)
Abstract The east coast of Australia is regularly influenced by midlatitude cyclones known as East Coast Lows. These form in a range of synoptic situations and are both a cause of severe weather and an important contributor to water security. This paper presents the first projections of future cyclone activity in this region using a regional climate model ensemble, with the use of a range of cyclone identification methods increasing the robustness of results. While there is considerable uncertainty in projections of cyclone frequency during the warm months, there is a robust agreement on a decreased frequency of cyclones during the winter months, when they are most common in the current climate. However, there is a potential increase in the frequency of cyclones with heavy rainfall and those closest to the coast and accordingly those with potential for severe flooding. , Key Points Winter cyclones are projected to decrease on the Australian east coast Cyclones associated with heavy rainfall may increase in frequency Projections of warm season cyclones remain uncertain

Cyclone contribution to the Mediterranean Sea water budget - Flaounas, E.; Di Luca, A.; Drobinski, P.; Mailler, S.; Arsouze, T.; Bastin, S.; Beranger, K.; Lebeaupin Brossier, C. (Climate Dynamics, 2016)

Precipitation over urban areas in the western Maritime Continent using a convection-permitting model - Argüeso, Daniel; Di Luca, Alejandro; Evans, Jason P. (Climate Dynamics, 2016)

Seasonal mean temperature changes control future heat waves - Argüeso, Daniel; Di Luca, Alejandro; Perkins‐Kirkpatrick, Sarah E.; Evans, Jason P. (Geophysical Research Letters, 2016)
Abstract Increased temperature will result in longer, more frequent, and more intense heat waves. Changes in temperature variability have been deemed necessary to account for future heat wave characteristics. However, this has been quantified only in Europe and North America, while the rest of the globe remains unexplored. Using late century global climate projections, we show that annual mean temperature increases is the key factor defining heat wave changes in most regions. We find that commonly studied areas are an exception rather than the standard and the mean climate change signal generally outweighs any influence from variability changes. More importantly, differences in warming across seasons are responsible for most of the heat wave changes and their consideration relegates the contribution of variability to a marginal role. This reveals that accurately capturing mean seasonal changes is crucial to estimate future heat waves and reframes our interpretation of future temperature extremes. , Key Points The influence of projected temperature variability changes on future heat waves varies across the globe Future heat waves are primarily controlled by annual mean changes, except in Europe and North America Mean seasonal warming is responsible for over 95% of projected heat wave changes in most region

Bias-corrected regional climate projections of extreme rainfall in south-east Australia - Evans, Jason P.; Argueso, D.; Olson, R.; Di Luca, A. (Theoretical and Applied Climatology, 2017)

Australian snowpack in the NARCliM ensemble: evaluation, bias correction and future projections - Luca, Alejandro Di; Evans, Jason P.; Ji, Fei (Climate Dynamics, 2018)

Independently assessing the representation of midlatitude cyclones in high‐resolution reanalyses using satellite observed winds - Pepler, Acacia S.; Di Luca, Alejandro; Evans, Jason P. (International Journal of Climatology, 2018)
ABSTRACT High‐resolution reanalyses offer the potential to improve our understanding of midlatitude cyclones, particularly smaller‐scale systems and those with complex structures. However, previous studies have demonstrated large variations in the frequency and characteristics of Australian midlatitude cyclones between reanalyses when using their native resolution. In this paper we use satellite observations of winds and rainfall in order to evaluate the ability of the ERA‐Interim, JRA55, MERRA and CFSR reanalyses to reproduce Australian east coast cyclones. The MERRA reanalysis produces a large number of erroneous small‐scale lows without cyclonic wind patterns using a simple pressure‐difference‐based cyclone identification and tracking method. Consequently, we recommend the ERA‐Interim reanalysis when using such methods, or applying more complex tracking methods that are able to compensate for these issues.

Projected change in characteristics of near surface temperature inversions for southeast Australia - Ji, Fei; Evans, Jason Peter; Di Luca, Alejandro; Jiang, Ningbo; Olson, Roman; Fita, Lluis; Argüeso, Daniel; Chang, Lisa T.-C.; Scorgie, Yvonne; Riley, Matt (Climate Dynamics, 2019)

Evaluating reanalysis-driven CORDEX regional climate models over Australia: model performance and errors - Di Virgilio, Giovanni; Evans, Jason P.; Di Luca, Alejandro; Olson, Roman; Argüeso, Daniel; Kala, Jatin; Andrys, Julia; Hoffmann, Peter; Katzfey, Jack J.; Rockel, Burkhardt (Climate Dynamics, 2019)

Review of Australian east coast low pressure systems and associated extremes - Dowdy, Andrew J.; Pepler, Acacia; Di Luca, Alejandro; Cavicchia, Leone; Mills, Graham; Evans, Jason P.; Louis, Simon; McInnes, Kathleen L.; Walsh, Kevin (Climate Dynamics, 2019)

An Out-of-Sample Analysis of Investment Guarantees for Equity-Linked Products: Lessons from the Financial Crisis of the Late 2000s - Augustyniak, Maciej; Boudreault, Mathieu (North American Actuarial Journal, 2012)

Contagion effect on bond portfolio risk measures in a hybrid credit risk model - Boudreault, Mathieu; Gauthier, Geneviève; Thomassin, Tommy (Finance Research Letters, 2014)

Risk models with dependence between claim occurrences and severities for Atlantic hurricanes - Boudreault, Mathieu; Cossette, Hélène; Marceau, Étienne (Insurance: Mathematics and Economics, 2014)

Changes in large-scale controls of Atlantic tropical cyclone activity with the phases of the Atlantic multidecadal oscillation - Caron, Louis-Philippe; Boudreault, Mathieu; Bruyère, Cindy L. (Climate Dynamics, 2015)

On the Variability and Predictability of Eastern Pacific Tropical Cyclone Activity* - Caron, Louis-Philippe; Boudreault, Mathieu; Camargo, Suzana J. (Journal of Climate, 2015)
Abstract Variability in tropical cyclone activity in the eastern Pacific basin has been linked to a wide range of climate factors, yet the dominant factors driving this variability have yet to be identified. Using Poisson regressions and a track clustering method, the authors analyze and compare the climate influence on cyclone activity in this region. The authors show that local sea surface temperature and upper-ocean heat content as well as large-scale conditions in the northern Atlantic are the dominant influence in modulating eastern North Pacific tropical cyclone activity. The results also support previous findings suggesting that the influence of the Atlantic Ocean occurs through changes in dynamical conditions over the eastern Pacific. Using model selection algorithms, the authors then proceed to construct a statistical model of eastern Pacific tropical cyclone activity. The various model selection techniques used agree in selecting one predictor from the Atlantic (northern North Atlantic sea surface temperature) and one predictor from the Pacific (relative sea surface temperature) to represent the best possible model. Finally, we show that this simple model could have predicted the anomalously high level of activity observed in 2014.

Estimation of correlations in portfolio credit risk models based on noisy security prices - Boudreault, Mathieu; Gauthier, Geneviève; Thomassin, Tommy (Journal of Economic Dynamics and Control, 2015)

Mitigating Interest Rate Risk in Variable Annuities: An Analysis of Hedging Effectiveness under Model Risk - Augustyniak, Maciej; Boudreault, Mathieu (North American Actuarial Journal, 2017)

Reanalysis of climate influences on Atlantic tropical cyclone activity using cluster analysis - Boudreault, Mathieu; Caron, Louis‐Philippe; Camargo, Suzana J. (Journal of Geophysical Research: Atmospheres, 2017)
Abstract We analyze, using Poisson regressions, the main climate influences on North Atlantic tropical cyclone activity. The analysis is performed using not only various time series of basin‐wide storm counts but also various series of regional clusters, taking into account shortcomings of the hurricane database through estimates of missing storms. The analysis confirms that tropical cyclones forming in different regions of the Atlantic are susceptible to different climate influences. We also investigate the presence of trends in these various time series, both at the basin‐wide and cluster levels, and show that, even after accounting for possible missing storms, there remains an upward trend in the eastern part of the basin and a downward trend in the western part. Using model selection algorithms, we show that the best model of Atlantic tropical cyclone activity for the recent past is constructed using Atlantic sea surface temperature and upper tropospheric temperature, while for the 1878–2015 period, the chosen covariates are Atlantic sea surface temperature and El Niño–Southern Oscillation. We also note that the presence of these artificial trends can impact the selection of the best covariates. If the underlying series shows an upward trend, then the mean Atlantic sea surface temperature captures both interannual variability and the upward trend, artificial or not. The relative sea surface temperature is chosen instead for stationary counts. Finally, we show that the predictive capability of the statistical models investigated is low for U.S. landfalling hurricanes but can be considerably improved when forecasting combinations of clusters whose hurricanes are most likely to make landfall. , Key Points Estimates of missing storms are not sufficient to account for the increase in hurricane activity in the eastern tropical Atlantic Recent upward trends, artificial or not, affect the selection of key determinants of tropical cyclone activity, especially the SST variable Despite previous results to that effect, the May–June NAO does not provide predictive skill for Atlantic landfalling hurricanes

Firm-specific credit risk estimation in the presence of regimes and noisy prices - Bégin, Jean-François; Boudreault, Mathieu; Gauthier, Geneviève (Finance Research Letters, 2017)

Maximum Likelihood Estimation of the Markov-Switching GARCH Model Based on a General Collapsing Procedure - Augustyniak, Maciej; Boudreault, Mathieu; Morales, Manuel (Methodology and Computing in Applied Probability, 2018)

Impact of reanalysis boundary conditions on downscaled Atlantic hurricane activity - Baudouin, Jean-Philippe; Caron, Louis-Philippe; Boudreault, Mathieu (Climate Dynamics, 2019)

Maximum likelihood estimation of first-passage structural credit risk models correcting for the survivorship bias - Amaya, Diego; Boudreault, Mathieu; McLeish, Don L. (Journal of Economic Dynamics and Control, 2019)

Credit and Systemic Risks in the Financial Services Sector: Evidence From the 2008 Global Crisis - Bégin, Jean‐François; Boudreault, Mathieu; Doljanu, Delia Alexandra; Gauthier, Geneviève (Journal of Risk and Insurance, 2019)
Abstract We develop a portfolio credit risk model that includes firm‐specific Markov‐switching regimes as well as individual stochastic and endogenous recovery rates. Using weekly credit default swap premiums for 35 financial firms, we analyze the credit risk of each of these companies and their statistical linkages, putting emphasis on the 2005–2012 period. Moreover, we study the systemic risk affecting both the banking and insurance subsectors.

Investigation of the sulphate‐induced freezing inhibition effect from CloudSat and CALIPSO measurements - Grenier, Patrick; Blanchet, Jean‐Pierre (Journal of Geophysical Research: Atmospheres, 2010)
The hypothesis according to which higher sulphate concentrations favor ice clouds made of larger ice crystals is tested using data sets from the CloudSat and Cloud‐Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellites. This is a potential consequence of the sulphate‐induced freezing inhibition (SIFI) effect, namely, the hypothesis that sulphates contribute to inhibit the onset of ice crystal formation by deactivating ice‐forming nuclei during Arctic winter. A simple index based on the backscattering at 532 nm and the color ratio from the CALIPSO lidar measurements is compared against in situ sulphate concentration time series and used as a proxy for this variable. An algorithm using the lidar data and the CloudSat radar microphysical retrievals is also developed for identifying cloud types, focusing on those supposedly favored by the SIFI effect. The analysis includes the effect of the lidar off‐nadir angle on the sulphate index and the cloud classification, the validation of the index, as well as the production of circum‐Arctic maps of the sulphate index and of the SIFI‐favored clouds fraction. The increase of the lidar off‐nadir angle is shown to cause an increase in the measured depolarization ratio and hence in the ability to detect ice crystals. The index correlates positively with both sulphates and sea salt concentrations, with a Pearson correlation coefficient ( ) varying from 0.10 to 0.42 for the different comparisons performed. Ultimate findings are the results of two correlation tests of the SIFI effect, which allow for a new outlook on its possible role in the Arctic troposphere during winter.

On the relationship between Arctic ice clouds and polluted air masses over the North Slope of Alaska in April 2008 - Jouan, C.; Pelon, J.; Girard, E.; Ancellet, G.; Blanchet, J. P.; Delanoë, J. (Atmospheric Chemistry and Physics, 2014)
Abstract. Recently, two types of ice clouds (TICs) properties have been characterized using the Indirect and Semi-Direct Aerosol Campaign (ISDAC) airborne measurements (Alaska, April 2008). TIC-2B were characterized by fewer (< 10 L−1) and larger (> 110 μm) ice crystals, and a larger ice supersaturation (> 15%) compared to TIC-1/2A. It has been hypothesized that emissions of SO2 may reduce the ice nucleating properties of ice nuclei (IN) through acidification, resulting in a smaller concentration of larger ice crystals and leading to precipitation (e.g., cloud regime TIC-2B). Here, the origin of air masses forming the ISDAC TIC-1/2A (1 April 2008) and TIC-2B (15 April 2008) is investigated using trajectory tools and satellite data. Results show that the synoptic conditions favor air masses transport from three potential SO2 emission sources into Alaska: eastern China and Siberia where anthropogenic and biomass burning emissions, respectively, are produced, and the volcanic region of the Kamchatka/Aleutians. Weather conditions allow the accumulation of pollutants from eastern China and Siberia over Alaska, most probably with the contribution of acidic volcanic aerosol during the TIC-2B period. Observation Monitoring Instrument (OMI) satellite observations reveal that SO2 concentrations in air masses forming the TIC-2B were larger than in air masses forming the TIC-1/2A. Airborne measurements show high acidity near the TIC-2B flight where humidity was low. These results support the hypothesis that acidic coating on IN could be at the origin of the formation of TIC-2B.

Spatio-temporal models to estimate daily concentrations of fine particulate matter in Montreal: Kriging with external drift and inverse distance-weighted approaches - Ramos, Yuddy; St-Onge, Benoît; Blanchet, Jean-Pierre; Smargiassi, Audrey (Journal of Exposure Science & Environmental Epidemiology, 2016)

Towards the Thin Ice Clouds in the Far-InfraRed Experiment (TICFIRE) - Libois, Quentin; Blanchet, Jean-Pierre; Proulx, Christian; Ivanescu, Liviu; Pelletier, Ludovick S. (Light, Energy and the Environment, 2016)

Spatial modeling of daily concentrations of ground-level ozone in Montreal, Canada: A comparison of geostatistical approaches - Ramos, Yuddy; Requia, Weeberb J.; St-Onge, Benoît; Blanchet, Jean-Pierre; Kestens, Yan; Smargiassi, Audrey (Environmental Research, 2018)

Overview paper: New insights into aerosol and climate in the Arctic - Abbatt, Jonathan P. D.; Leaitch, W. Richard; Aliabadi, Amir A.; Bertram, Allan K.; Blanchet, Jean-Pierre; Boivin-Rioux, Aude; Bozem, Heiko; Burkart, Julia; Chang, Rachel Y. W.; Charette, Joannie; Chaubey, Jai P.; Christensen, Robert J.; et al. (Atmospheric Chemistry and Physics, 2019)
Abstract. Motivated by the need to predict how the Arctic atmosphere will change in a warming world, this article summarizes recent advances made by the research consortium NETCARE (Network on Climate and Aerosols: Addressing Key Uncertainties in Remote Canadian Environments) that contribute to our fundamental understanding of Arctic aerosol particles as they relate to climate forcing. The overall goal of NETCARE research has been to use an interdisciplinary approach encompassing extensive field observations and a range of chemical transport, earth system, and biogeochemical models. Several major findings and advances have emerged from NETCARE since its formation in 2013. (1) Unexpectedly high summertime dimethyl sulfide (DMS) levels were identified in ocean water (up to 75 nM) and the overlying atmosphere (up to 1 ppbv) in the Canadian Arctic Archipelago (CAA). Furthermore, melt ponds, which are widely prevalent, were identified as an important DMS source (with DMS concentrations of up to 6 nM and a potential contribution to atmospheric DMS of 20 % in the study area). (2) Evidence of widespread particle nucleation and growth in the marine boundary layer was found in the CAA in the summertime, with these events observed on 41 % of days in a 2016 cruise. As well, at Alert, Nunavut, particles that are newly formed and grown under conditions of minimal anthropogenic influence during the months of July and August are estimated to contribute 20 % to 80 % of the 30–50 nm particle number density. DMS-oxidation-driven nucleation is facilitated by the presence of atmospheric ammonia arising from seabird-colony emissions, and potentially also from coastal regions, tundra, and biomass burning. Via accumulation of secondary organic aerosol (SOA), a significant fraction of the new particles grow to sizes that are active in cloud droplet formation. Although the gaseous precursors to Arctic marine SOA remain poorly defined, the measured levels of common continental SOA precursors (isoprene and monoterpenes) were low, whereas elevated mixing ratios of oxygenated volatile organic compounds (OVOCs) were inferred to arise via processes involving the sea surface microlayer. (3) The variability in the vertical distribution of black carbon (BC) under both springtime Arctic haze and more pristine summertime aerosol conditions was observed. Measured particle size distributions and mixing states were used to constrain, for the first time, calculations of aerosol–climate interactions under Arctic conditions. Aircraft- and ground-based measurements were used to better establish the BC source regions that supply the Arctic via long-range transport mechanisms, with evidence for a dominant springtime contribution from eastern and southern Asia to the middle troposphere, and a major contribution from northern Asia to the surface. (4) Measurements of ice nucleating particles (INPs) in the Arctic indicate that a major source of these particles is mineral dust, likely derived from local sources in the summer and long-range transport in the spring. In addition, INPs are abundant in the sea surface microlayer in the Arctic, and possibly play a role in ice nucleation in the atmosphere when mineral dust concentrations are low. (5) Amongst multiple aerosol components, BC was observed to have the smallest effective deposition velocities to high Arctic snow (0.03 cm s−1).

Carbon emission limits required to satisfy future representative concentration pathways of greenhouse gases: ALLOWABLE FUTURE CARBON EMISSIONS - Arora, V. K.; Scinocca, J. F.; Boer, G. J.; Christian, J. R.; Denman, K. L.; Flato, G. M.; Kharin, V. V.; Lee, W. G.; Merryfield, W. J. (Geophysical Research Letters, 2011)

Objective Calibration of Regional Climate Models: Application over Europe and North America - Bellprat, Omar; Kotlarski, Sven; Lüthi, Daniel; De Elía, Ramón; Frigon, Anne; Laprise, René; Schär, Christoph (Journal of Climate, 2016)
Abstract An important source of model uncertainty in climate models arises from unconfined model parameters in physical parameterizations. These parameters are commonly estimated on the basis of manual adjustments (expert tuning), which carries the risk of overtuning the parameters for a specific climate region or time period. This issue is particularly germane in the case of regional climate models (RCMs), which are often developed and used in one or a few geographical regions only. This study addresses the role of objective parameter calibration in this context. Using a previously developed objective calibration methodology, an RCM is calibrated over two regions (Europe and North America) and is used to investigate the transferability of the results. A total of eight different model parameters are calibrated, using a metamodel to account for parameter interactions. The study demonstrates that the calibration is effective in reducing model biases in both domains. For Europe, this concerns in particular a pronounced reduction of the summer warm bias and the associated overestimation of interannual temperature variability that have persisted through previous expert tuning efforts and are common in many global and regional climate models. The key process responsible for this improvement is an increased hydraulic conductivity. Higher hydraulic conductivity increases the water availability at the land surface and leads to increased evaporative cooling, stronger low cloud formation, and associated reduced incoming shortwave radiation. The calibrated parameter values are found to be almost identical for both domains; that is, the parameter calibration is transferable between the two regions. This is a promising result and indicates that models may be more universal than previously considered.

Natural hazards in Australia: storms, wind and hail - Walsh, Kevin; White, Christopher J.; McInnes, Kathleen; Holmes, John; Schuster, Sandra; Richter, Harald; Evans, Jason P.; Di Luca, Alejandro; Warren, Robert A. (Climatic Change, 2016)

Correcting the overestimate of forest biomass carbon on the national scale - Zhou, Xiaolu; Lei, Xiangdong; Peng, Changhui; Wang, Weifeng; Zhou, Carl; Liu, Caixia; Liu, Zhenggang (Methods in Ecology and Evolution, 2016)
Summary For decades, researchers have thought it was difficult to remove the uncertainty from the estimates of forest carbon storage and its changes on national sales. This is not only because of stochasticity in the data but also the bias to overcome in the computations. Most studies of the estimation, however, ignore quantitative analyses for the latter uncertainty. This bias primarily results from the widely used volume‐biomass method via scaling up forest biomass from limited sample plots to large areas. This paper addresses (i) the mechanism of scaling‐up error occurrence, and (ii) the quantitative effects of the statistical factors on the error. The error compensators were derived, and expressed by ternary functions with three variables: expectation, variance and the power in the volume‐biomass equation. This is based on analysing the effect of power‐law function convexity on scaling‐up error by solving the difference of both sides of the weighted Jensen inequality. The simulated data and the national forest inventory of China were used for algorithm testing and application, respectively. Scaling‐up error occurrence stems primarily from an effect of the distribution heterogeneity of volume density on the total biomass amount, and secondarily from the extent of function nonlinearities. In our experiments, on average 94·2% of scaling‐up error can be reduced for the statistical populations of forest stands in a region. China's forest biomass carbon was estimated as approximately 6·0 PgC or less at the beginning of the 2010s after on average 1·1% error compensation. The results of both the simulated data experiment and national‐scale estimation suggest that the biomass is overestimated for young forests more than others. It implies a necessity to compensate scaling‐up error, especially for the areas going through extensive afforestation and reforestation in past decades. This study highlights the importance of understanding how both the function nonlinearity and the statistics of the variables quantitatively affect the scaling‐up error. Generally, the presented methods will help to translate fine‐scale ecological relationships to estimate coarser scale ecosystem properties by correcting aggregation errors.

A microbolometer-based far infrared radiometer to study thin ice clouds in the Arctic - Libois, Quentin; Proulx, Christian; Ivanescu, Liviu; Coursol, Laurence; Pelletier, Ludovick S.; Bouzid, Yacine; Barbero, Francesco; Girard, Éric; Blanchet, Jean-Pierre (Atmospheric Measurement Techniques, 2016)
Abstract. A far infrared radiometer (FIRR) dedicated to measuring radiation emitted by clear and cloudy atmospheres was developed in the framework of the Thin Ice Clouds in Far InfraRed Experiment (TICFIRE) technology demonstration satellite project. The FIRR detector is an array of 80 × 60 uncooled microbolometers coated with gold black to enhance the absorptivity and responsivity. A filter wheel is used to select atmospheric radiation in nine spectral bands ranging from 8 to 50 µm. Calibrated radiances are obtained using two well-calibrated blackbodies. Images are acquired at a frame rate of 120 Hz, and temporally averaged to reduce electronic noise. A complete measurement sequence takes about 120 s. With a field of view of 6°, the FIRR is not intended to be an imager. Hence spatial average is computed over 193 illuminated pixels to increase the signal-to-noise ratio and consequently the detector resolution. This results in an improvement by a factor of 5 compared to individual pixel measurements. Another threefold increase in resolution is obtained using 193 non-illuminated pixels to remove correlated electronic noise, leading an overall resolution of approximately 0.015 W m−2 sr−1. Laboratory measurements performed on well-known targets suggest an absolute accuracy close to 0.02 W m−2 sr−1, which ensures atmospheric radiance is retrieved with an accuracy better than 1 %. Preliminary in situ experiments performed from the ground in winter and in summer on clear and cloudy atmospheres are compared to radiative transfer simulations. They point out the FIRR ability to detect clouds and changes in relative humidity of a few percent in various atmospheric conditions, paving the way for the development of new algorithms dedicated to ice cloud characterization and water vapor retrieval.
Keywords: Arctique; Atmosphère; Radiométrie

Airborne observations of far-infrared upwelling radiance in the Arctic - Libois, Quentin; Ivanescu, Liviu; Blanchet, Jean-Pierre; Schulz, Hannes; Bozem, Heiko; Leaitch, W. Richard; Burkart, Julia; Abbatt, Jonathan P. D.; Herber, Andreas B.; Aliabadi, Amir A.; Girard, Éric (Atmospheric Chemistry and Physics, 2016)
Abstract. The first airborne measurements of the Far-InfraRed Radiometer (FIRR) were performed in April 2015 during the panarctic NETCARE campaign. Vertical profiles of spectral upwelling radiance in the range 8–50 µm were measured in clear and cloudy conditions from the surface up to 6 km. The clear sky profiles highlight the strong dependence of radiative fluxes to the temperature inversion typical of the Arctic. Measurements acquired for total column water vapour from 1.5 to 10.5 mm also underline the sensitivity of the far-infrared greenhouse effect to specific humidity. The cloudy cases show that optically thin ice clouds increase the cooling rate of the atmosphere, making them important pieces of the Arctic energy balance. One such cloud exhibited a very complex spatial structure, characterized by large horizontal heterogeneities at the kilometre scale. This emphasizes the difficulty of obtaining representative cloud observations with airborne measurements but also points out how challenging it is to model polar clouds radiative effects. These radiance measurements were successfully compared to simulations, suggesting that state-of-the-art radiative transfer models are suited to study the cold and dry Arctic atmosphere. Although FIRR in situ performances compare well to its laboratory performances, complementary simulations show that upgrading the FIRR radiometric resolution would greatly increase its sensitivity to atmospheric and cloud properties. Improved instrument temperature stability in flight and expected technological progress should help meet this objective. The campaign overall highlights the potential for airborne far-infrared radiometry and constitutes a relevant reference for future similar studies dedicated to the Arctic and for the development of spaceborne instruments.
Keywords: Arctique; Radiométrie

Added value of far‐infrared radiometry for remote sensing of ice clouds - Libois, Quentin; Blanchet, Jean‐Pierre (Journal of Geophysical Research: Atmospheres, 2017)
Abstract Several cloud retrieval algorithms based on satellite observations in the infrared have been developed in the last decades. However, these observations only cover the midinfrared (MIR, λ < 15 μm) part of the spectrum, and none are available in the far‐infrared (FIR, λ ≥ 15 μm). Using the optimal estimation method, we show that adding a few FIR channels to existing spaceborne radiometers would significantly improve their ability to retrieve ice cloud radiative properties. For clouds encountered in the polar regions and the upper troposphere, where the atmosphere is sufficiently transparent in the FIR, using FIR channels would reduce by more than 50% the uncertainties on retrieved values of optical thickness, effective particle diameter, and cloud top altitude. Notably, this would extend the range of applicability of current retrieval methods to the polar regions and to clouds with large optical thickness, where MIR algorithms perform poorly. The high performance of solar reflection‐based algorithms would thus be reached in nighttime conditions. Since the sensitivity of ice cloud thermal emission to effective particle diameter is approximately 5 times larger in the FIR than in the MIR, using FIR observations is a promising venue for studying ice cloud microphysics and precipitation processes. This is highly relevant for cirrus clouds and convective towers. This is also essential to study precipitation in the driest regions of the atmosphere, where strong feedbacks are at play between clouds and water vapor. The deployment in the near future of a FIR spaceborne radiometer is technologically feasible and should be strongly supported. , Plain Language Summary The size of ice cloud particles can be estimated from space by measuring the infrared emission of ice clouds. However, this method no longer works when clouds are too thick or when particles are too large, although such clouds are encountered in many regions of the Earth and are critical for the Earth's climate. Using new sensors that measure cloud emission at longer wavelengths, in the so‐called far‐infrared region, would extend the potential of satellite observations to thick clouds, to clouds made of larger particles, and to clouds found in the polar regions which are very poorly known. These new sensors have become available in the last years, but none is deployed in space so far. We show that a satellite equipped with a few channels in the far‐infrared would greatly increase our capacity to observe ice clouds. This is promising for our understanding of cloud microphysics and precipitation in general, and for studying the water cycle in the polar regions in particular. For these reasons, it is highly recommended to deploy a far‐infrared radiometer in space. , Key Points Ice cloud remote sensing would be greatly improved by adding far‐infrared channels to existing midinfrared spaceborne radiometers Far‐infrared radiometry is well suited to study ice clouds in the polar regions and upper troposphere Using far‐infrared radiometry extends current infrared capabilities to large optical thickness and large cloud particles
Keywords: Atmosphère; Radiométrie

Urban surface effects on current and future climate - Garuma, Gemechu Fanta; Blanchet, Jean-Pierre; Girard, Éric; Leduc, Martin (Urban Climate, 2018)

Simulating Arctic Ice Clouds during Spring Using an Advanced Ice Cloud Microphysics in the WRF Model - Keita, Setigui; Girard, Eric; Raut, Jean-Christophe; Pelon, Jacques; Blanchet, Jean-Pierre; Lemoine, Olivier; Onishi, Tatsuo (Atmosphere, 2019)
Two Types of Ice Clouds (TICs) have been characterized in the Arctic during the polar night and early spring. TIC-1 are composed by non-precipitating small ice crystals of less than 30 µm in diameter. The second type, TIC-2, are characterized by a low concentration of large precipitating ice crystals (>30 µm). Here, we evaluate the Weather Research and Forecasting (WRF) model performance both in space and time after implementing a parameterization based on a stochastic approach dedicated to the simulation of ice clouds in the Arctic. Well documented reference cases provided us in situ data from the spring of 2008 Indirect and Semi-Direct Aerosol Campaign (ISDAC) campaign over Alaska. Simulations of the microphysical properties of the TIC-2 clouds on 15 and 25 April 2008 (polluted or acidic cases) and TIC-1 clouds on non-polluted cases are compared to DARDAR (raDAR/liDAR) satellite products. Our results show that the stochastic approach based on the classical nucleation theory, with the appropriate contact angle, is better than the original scheme in WRF model to represent TIC-1 and TIC-2 properties (ice crystal concentration and size) in response to the IN acidification.
Keywords: Arctique; Atmosphère